Performance Evaluation of Recently Constructed Ponds for Flood Mitigation in Erbil City and their Impacts on the Environment (Global NEST Journal, 2025)
This study investigates the performance of 35 recent ponds (which are under tendering, under construction, and finished in Erbil City), focusing on their role in flood mitigation across 11 distinct catchment areas. The total storage capacity of these ponds is approximately 9,926,394 m³, significantly enhancing the city's ability to manage stormwater runoff and reduce flood risks. The Watershed Modeling System (WMS), along with the Soil Conservation Service Curve Number (SCS-CN) method, was utilized for hydrological modeling to evaluate runoff behavior and water retention performance. Calculated Retention Capacity Ratio (RCR) values vary from as low as 21 % in the smallest system to 136 % in the Kasnazan catchment, with Chamarga similarly exceeding full capacity at 131 %. These over-capacity networks not only attenuate peak flows but also promote groundwater recharge, improve downstream water quality by trapping sediments and nutrients, and create valuable aquatic and riparian habitats. Our findings demonstrate the multifaceted benefits of high-capacity retention ponds and provide a replicable model for integrating green infrastructure into urban planning to build flood resilience and sustainable water management in rapidly urbanizing regions.

Natural Disasters and Rehabilitation: Post‐Disaster Aid, Corruption, Misallocation, and Mistargeting - Ahmad, Muhammad Irshad; Shen, Qiong; Boota, Muhammad Waseem; Liu, Ruifeng; Ma, Hengyun (Sustainable Development, 2025)
ABSTRACT The increasing frequency of natural disasters, such as floods, droughts, and tsunamis, has made vulnerable communities less resilient, pushing them toward long‐term poverty and food insecurity. Effective post‐disaster rehabilitation is critical to restoring livelihoods, infrastructure, and food security. However, challenges such as corruption, misallocation, and mistargeting undermine post‐disaster aid programs. This study systematically reviews 86 peer‐reviewed articles (1990–2023) using the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) protocol to investigate aid inefficiencies in disaster recovery. The findings reveal that aid often fails to reach the most affected communities, being diverted to unaffected areas due to political influence and local elites, exacerbating inequalities. Corruption further hampers institutional performance and long‐term disaster resilience efforts. The study calls for transparent, accountable, and inclusive strategies for aid distribution, aligning with SDG 10 (reduced inequalities) and SDG 11 (sustainable cities and communities). Future research should focus on gender‐sensitive strategies, local governance, and technological innovations to enhance aid transparency and effectiveness.
Keywords: Scopus_Alert_12_Septembre_2025

Integrated hydrologic-economic modeling for urban flood risk mitigation using SWMM, HEC-RAS, and HAZUS: a case study of the Bronx river watershed, NYC - Javidi Sabbaghian, Reza; Fereshtehpour, Mohammad; Goli Hosseinabad, Mohammad Reza (Sustainable Water Resources Management, 2025)
Rapid urban expansion has significantly altered land use patterns, resulting in a decrease in pervious surface areas and a disruption of hydrologic connectivity between surface water and groundwater systems. Combined with inadequate drainage systems and poorly managed runoff, these changes have intensified urban flooding, leading to fatalities and significant infrastructure damage in many rapidly growing and climate-vulnerable urban areas around the world. This study presents an integrated economic-hydrologic model to assess the effectiveness of Low Impact Development (LID) measures—specifically permeable pavement, infiltration trenches, bio-retention cells, and rain barrels—in mitigating flood damage in the Bronx river watershed, NYC. The Storm Water Management Model (SWMM) was employed to simulate flood events and assess the effectiveness of various LIDs, applied individually and in combination, in reducing peak discharge. Flood inundation maps generated using HEC-GeoRAS were integrated with the HAZUS damage estimation model to quantify potential flood damages. A benefit-to-cost (BC) ratio was then calculated by comparing the monetary savings from reduced flood damage against the implementation costs of LID measures. Results indicate that the combined LID scenario offers the highest peak flow reduction, with permeable pavement alone reducing flow by 57%, outperforming other techniques under equal area coverage. Among all individual options, permeable pavement yields the highest cumulative BC ratio under all scenarios (4.6), whereas rain barrels are the least effective (2.6). The proposed evaluation framework highlights the importance of economic efficiency in flood mitigation planning and provides a structured foundation for informed decision-making to enhance urban resilience through LID implementation. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Scopus_Alert_5_Septembre_2025

River basin urban flood resilience: A multi-dimensional framework for risk mitigation to adaptive management and ecosystem protection under changing climate - Soomro, Shan-e-hyder; Wei, Huaibin; Boota, Muhammad Waseem; Soomro, Nishan-E-hyder; Faisal, Muhammad; Nazli, Sana; sarwari, Soraya; Shi, Xiaotao; Hu, Caihong; Guo, Jiali; Li, Yinghai (Ecological Informatics, 2025)
Study region: This study aims at the Kunhar River Basin, Pakistan, that has been facing repeated flood occurrences on a recurring basis. As the flood susceptibility of this area is high, its topographic complexity demands correct predictive modeling for strategic flood planning. Study focus: We developed a system of flood susceptibility mapping based on Geographic Information Systems (GIS), Principal Component Analysis (PCA), and Support Vector Machine (SVM) classification. Four kernel functions were applied, and the highest-performing was the Radial Basis Function (SVM-RBF). The model was validated and trained using historical flood inventories, morphometric parameters, and hydrologic variables, and feature dimensionality was reduced via PCA for increased efficiency. New hydrological insights: The SVM-RBF model recorded an AUC of 0.8341, 88.02% success, 84.97% predictability, 0.89 Kappa value, and F1-score of 0.86, all of which indicated high predictability. Error analysis yielded a PBIAS of +2.14%, indicating negligible overestimation bias but within limits acceptable in hydrological modeling. The results support the superiority of the SVM-RBF approach compared to conventional bivariate methods in modeling flood susceptibility over the complex terrain of mountains. The results can be applied in guiding evidence-based flood mitigation, land-use planning, and adaptive management in the Kunhar River Basin. © 2025 The Author(s)
Keywords: Scopus_Alert_5_Septembre_2025

Integrative strategies for urban flood resilience and risk: A meta-analysis of policy, infrastructural, and ecosystem-based interventions - Wang, Shitao; Bi, Xuehao (Physics and Chemistry of the Earth, 2025)
Urban flooding, intensified by climate change and rapid urbanization, demands robust and operationally effective resilience strategies. However, empirical evidence on the comparative effectiveness of such strategies remains limited. This study presents the first meta-analytic synthesis evaluating urban flood resilience interventions across institutional, infrastructural, and socio-ecological domains. By synthesizing data from 29 peer-reviewed studies (2000–2024), this study applies standardized effect sizes (Cohen's d) and meta-regression models to assess the effectiveness of different strategies. Results reveal a substantial overall effect (pooled d = 2.96, 95 % CI: [1.92, 3.99]) with high heterogeneity (I2 = 93.8 %). Institutional mechanisms, such as policy coordination, regulatory frameworks, and risk governance, consistently show the strongest and most statistically significant impacts (d ≈ 2.96). Low Impact Development (LID) demonstrates limited, non-significant effects (d ≈ 0.08). The study introduces a novel hierarchical resilience framework spanning different dimensions and establishes an evidence-based typology of urban flood resilience strategies. These findings highlight the importance of integrated, multi-level governance and context-specific planning in enhancing urban flood resilience. The study findings provides critical insights for implementing resilience strategies in flood-prone urban areas, and support the formulation of adaptive and sustainable urban policies. © 2025
Keywords: Scopus_Alert_5_Septembre_2025

Land Subsidence and Coastal Flood Impact Scenarios Based on Remote Sensing in Selangor, Malaysia - Batmanathan, Navakanesh M.; Pereira, Joy Jacqueline; Shah, Afroz Ahmad; Muhamad, Nurfashareena; Sian, Lim Choun (Journal of Marine Science and Engineering, 2025)
This study uses remote sensing data to assess susceptibility to hazards, which are then validated to model impact scenarios for land subsidence and coastal flooding in the Integrated Coastal Zone Management (ICZM) of Selangor, Malaysia, to support decision-making in urban planning and land management. Land subsidence and coastal floods affect a major proportion of the population in the ICZM, with subsidence being significant contributing factors, but information on the extent of susceptible areas, monitoring, and wide-area coverage is limited. Land subsidence distribution is demarcated using Interferometric Synthetic Aperture Radar (InSAR) time-series data (2015–2022), and integrated with coastal flood susceptibility derived from Analytic Hierarchy Process (AHP)-based weights to model impacts on land cover. Results indicate maximum subsidence rates of 46 mm/year (descending orbit) and 61 mm/year (ascending orbit); reflecting a gradual increase in subsidence trends with an average rate of 13 mm/year. In the worst-case scenario, within the ICZM area of 2262 km2, nearly 12% of the total built-up land cover with the highest population density is exposed to land subsidence, while exposure to coastal floods is relatively larger, covering nearly 34% of the built-up area. Almost 27% of the built-up area is exposed to the combined effects of both land subsidence and coastal floods, under present sea level conditions, with increasing risks of coastal floods over 2040, 2050 and 2100, due to both combinations. This research prioritizes areas for further study and provides a scientific foundation for resilience strategies aimed at ensuring sustainable coastal development within the ICZM. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Flood Exposure Assessment of Railway Infrastructure: A Case Study for Iowa - Alabbad, Yazeed; Cikmaz, Atiye Beyza; Yildirim, Enes; Demir, Ibrahim (Applied Sciences (Switzerland), 2025)
Floods pose a substantial risk to human well-being. These risks encompass economic losses, infrastructural damage, disruption of daily life, and potential loss of life. This study presents a state-wide and county-level spatial exposure assessment of the Iowa railway network, emphasizing the resilience and reliability of essential services during such disasters. In the United States, the railway network is vital for the distribution of goods and services. This research specifically targets the railway network in Iowa, a state where the impact of flooding on railways has not been extensively studied. We employ comprehensive GIS analysis to assess the vulnerability of the railway network, bridges, rail crossings, and facilities under 100- and 500-year flood scenarios at the state level. Additionally, we conducted a detailed investigation into the most flood-affected counties, focusing on the susceptibility of railway bridges. Our state-wide analysis reveals that, in a 100-year flood scenario, up to 9% of railroads, 8% of rail crossings, 58% of bridges, and 6% of facilities are impacted. In a 500-year flood scenario, these figures increase to 16%, 14%, 61%, and 13%, respectively. Furthermore, our secondary analysis using flood depth maps indicates that approximately half of the railway bridges in the flood zones of the studied counties could become non-functional in both flood scenarios. These findings are crucial for developing effective disaster risk management plans and strategies, ensuring adequate preparedness for the impacts of flooding on railway infrastructure. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Revolutionizing urban water resilience: Innovative strategies and advancements in sustainable urban drainage systems (SuDS) - Pachouri, Vikrant; Kothari, Prafull; Kathuria, Samta; Gehlot, Anita; Singh, Rajesh; Thakur, Amit Kumar; Gupta, Lovi Raj; Dogra, Sudhanshu; Priyadarshi, Neeraj; Mohamed, Heba G. (Desalination and Water Treatment, 2025)
Climate change and rapid urbanisation are straining urban stormwater management further, with floods and water pollution becoming more intense. SUDS is a nature-based alternative that solves these issues because it replicates natural hydrologic processes to create urban resilience. This systematic review summarises recent trends in SUDS technologies, performance, and policy frameworks, and their potential to mitigate flood risks, improve water quality, and enhance climate resilience. By the PRISMA methodology, 90 peer-reviewed studies published between 2014 and 2025 were considered, dealing with SUDS performance, cost-effectiveness, and overall difficulties with large-scale implementation of these systems. Main results are that bio-retention systems, permeable pavements, and green roofs are effective in controlling surface runoff and enhancing water quality. Moreover, the development of IoT-based monitoring and smart technologies has also considerably increased the scalability and efficiency of a SUDS. The review recommends the standardisation of SUDS performance, the incorporation of smart technologies, and more attractive policy incentives to speed up the uptake of SUDS in urban planning. One of the main contributions that this research is likely to make to the discourse concerning urban water resilience is that it offers evidence-based suggestions to policymakers and urban developers, and these suggestions argue in favour of taking urgent action in the area of climate adaptation by using SUDS extensively. © 2025 The Authors
Keywords: Scopus_Alert_5_Septembre_2025

Establishing a Sea Level Rise-Adjusted Design Flood Elevation for Buildings: A Comparative Study of Methods - Meguro, Wendy; Briones, Josephine I.; Teeples, Eric; Fletcher, Charles H. (Water (Switzerland), 2025)
Coastal high tide flooding doubled in the U.S. between 2000 and 2022 and sea level rise (SLR) due to climate change will dramatically increase exposure and vulnerability to flooding in the future. However, standards for elevating buildings in flood hazard areas, such as base flood elevations set by the Federal Emergency Management Agency, are based on historical flood data and do not account for future SLR. To increase flood resilience in flood hazard areas, federal, state, regional, and municipal planning initiatives are developing guidance to increase elevation requirements for occupied spaces in buildings. However, methods to establish a flood elevation that specifically accounts for rising sea levels (or sea level rise-adjusted design flood elevation (SLR-DFE)) are not standardized. Many municipalities or designers lack clear guidance on developing or incorporating SLR-DFEs. This study compares guidance documents, policies, and methods for establishing an SLR-DFE. The authors found that the initiatives vary in author, water level measurement starting point, SLR scenario and timeframe, SLR adjustment, freeboard, design flood elevation, application (geography and building type), and whether it is required or recommended. The tables and graph compare the different initiatives, providing a useful summary for policymakers and practitioners to develop SLR-DFE standards. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Exploring the potential of coastal cities to address climate change towards an inclusive, equitable and politically engaged orientation - Monckeberg, Elisa; Gómez, Sílvia (Anthropocene Coasts, 2025)
In the context of the global climate crisis, the analysis and strengthening of adaptive capacities in coastal urban environments has become imperative. Nearly 40% of the global population lives within 100 km of the coastline, making them critical research hotspots due to their particular vulnerability. This qualitative literature review takes a transdisciplinary approach and prioritizes research that addresses specific challenges and solutions for these vulnerable environments, with an emphasis on resilience to phenomena such as sea level rise, flooding and extreme weather events. The review analyzes articles that offer a holistic view, encompassing green and blue infrastructures, community needs and governance dynamics. It highlights studies that propose innovative strategies to foster citizen participation and explicitly address aspects such as climate justice. By synthesizing interdisciplinary perspectives and local knowledge, this review aims to provide a comprehensive framework for climate adaptation in coastal urban areas. The findings have the potential to inform public policy and urban planning practices. © The Author(s) 2025.
Keywords: Scopus_Alert_5_Septembre_2025

Copula-based joint distribution modelling of precipitation, temperature and humidity events in the assessments of agricultural risks, with a case study in Morocco - Latif, Shahid; El Ouadi, Ihssan; Ouarda, Taha B. M. J. (Stochastic Environmental Research and Risk Assessment, 2025)
The agriculture sector is profoundly impacted by the abiotic stresses in arid or semi-arid regions that experience extreme weather patterns related to temperature (T), precipitation (P), humidity (H), and other factors. This study adopts a flexible approach that incorporates the D-vine copula density to analyze trivariate (and bivariate) joint and conditional hazard risk. The methodology was applied to a case study in the Ait Ben Yacoub region of Morocco. Monthly series for T, H, and P were modeled using the Weibull-2P and Weibull-3P models, selected based on fitness statistics. The survival BB8 copula was best described as joint dependence for pair T–P, rotated BB8 270 degrees copula for T–H, while rotated Joe 270 degrees copula for P–H. The analysis of joint probability stress focused on both primary joint scenarios (for OR and AND-hazard conditions) and conditional return periods (RPs) for trivariate and bivariate case. Lower univariate RPs resulted in higher marginal quantiles for T and lower for H and P events. Lower trivariate (and bivariate) AND-joint RPs (or higher concurrence probabilities) were associated with higher T with lower P and H quantiles. The occurrence of trivariate (and bivariate) events was less frequent in the AND-joint case compared to the OR-joint case. The conditional joint RP of T (or T with P, or T with H) was significantly affected by different P (at 10th and 25th percentile) and H (at 5th and 25th percentile) (or P, or H) conditions. Lower conditional RPs of T (or T with H, or T with P) had resulted at given low P and H (or low P, or low H levels). In conclusion, the estimated risk statistics are vital for the study region, highlighting the need for effective adaptation and resilience planning in agriculture crop management.
Keywords: Infolettre_Septembre_2025

High-Resolution Daily XCH4 Prediction Using New Convolutional Neural Network Autoencoder Model and Remote Sensing Data - Awad, Mohamad M.; Homayouni, Saeid (Atmosphere, 2025)
Atmospheric methane (CH4) concentrations have increased to 2.5 times their pre-industrial levels, with a marked acceleration in recent decades. CH4 is responsible for approximately 30% of the global temperature rise since the Industrial Revolution. This growing concentration contributes to environmental degradation, including ocean acidification, accelerated climate change, and a rise in natural disasters. The column-averaged dry-air mole fraction of methane (XCH4) is a crucial indicator for assessing atmospheric CH4 levels. In this study, the Sentinel-5P TROPOMI instrument was employed to monitor, map, and estimate CH4 concentrations on both regional and global scales. However, TROPOMI data exhibits limitations such as spatial gaps and relatively coarse resolution, particularly at regional scales or over small areas. To mitigate these limitations, a novel Convolutional Neural Network Autoencoder (CNN-AE) model was developed. Validation was performed using the Total Carbon Column Observing Network (TCCON), providing a benchmark for evaluating the accuracy of various interpolation and prediction models. The CNN-AE model demonstrated the highest accuracy in regional-scale analysis, achieving a Mean Absolute Error (MAE) of 28.48 ppb and a Root Mean Square Error (RMSE) of 30.07 ppb. This was followed by the Random Forest (RF) regressor (MAE: 29.07 ppb; RMSE: 36.89 ppb), GridData Nearest Neighbor Interpolator (NNI) (MAE: 30.06 ppb; RMSE: 32.14 ppb), and the Radial Basis Function (RBF) Interpolator (MAE: 80.23 ppb; RMSE: 90.54 ppb). On a global scale, the CNN-AE again outperformed other methods, yielding the lowest MAE and RMSE (19.78 and 24.7 ppb, respectively), followed by RF (21.46 and 27.23 ppb), GridData NNI (25.3 and 32.62 ppb), and RBF (43.08 and 54.93 ppb).
Keywords: Infolettre_Septembre_2025

Multi-criteria decision analysis for flood hazard mapping in the Itang watershed, lower Baro-Akobo Basin, Southwest Ethiopia - Chengu, Shibiru; Assen, Mohammed; Gebeyehu, Elias (Discover Environment, 2025)
Flooding remains a critical hydrological hazard in the Itang watershed within the Lower Baro-Akobo Basin, requiring an in-depth assessment of flood susceptibility. This study employs a multi-criteria evaluation method, integrating key geospatial and hydrological parameters such as topographic slope, elevation, land use/land cover, River proximity, drainage network density, precipitation intensity, and soil properties. Utilizing a Multi-Criteria Decision Analysis (MCDA) approach within the ArcMap 10.3.1 environment, a flood hazard zonation map was generated, classifying the watershed into five risk categories: Very high, high, moderate, low, and very low. The findings reveal that approximately 69.69% of the watershed falls within the high to very high flood risk zones, predominantly influenced by low-lying Elevation, gentle slopes, proximity to the river, land cover dynamics, high drainage density, and precipitation variability. These insights emphasize the necessity of integrating robust flood mitigation measures, early warning mechanisms, and sustainable watershed management interventions to enhance flood resilience and reduce hydrological risks in the study watershed. © The Author(s) 2025.

Risk identification and prevention of multi-level flood and typhoon prevention emergency drills - Cao, Feifeng; Chen, Changhui; Zhang, Conglin; Xing, Jianwu (Progress in Disaster Science, 2025)
Amid increasing extreme weather events driven by global climate change, pre-emptive emergency drills are vital for strengthening disaster resilience. This paper focuses on risk identification and prevention in multi-level flood and typhoon prevention emergency drills, aiming to achieve effective risk management across administrative levels. Through literature review and expert consultation, 24 risk factors were hierarchically identified. A quantitative risk assessment model was developed by integrating the risk matrix and cloud model eigenvalues. The results show that risks are the most serious at municipal-level drills, with 20 risk factors (79.17 % of the total) at Level-III and above, decreasing at lower administrative levels (where risk level are categorized into Level-I (Major), Level-II (Large), Level-III (General), and Level-IV (Low) based on the risk matrix integrating likelihood and consequence levels, and Level-III and above risks may trigger resource wastage, drill failure, or even personnel casualties). Temporally, 39 risk factors at Level-III and above were concentrated in preparation stages across all administrative levels, declining to 3 such risk factors during rectification stage. Spatially, the number of risk factors peaked during the municipal-level and county-level preparation stages (11 risk factors respectively at Level-III and above), with their quantity gradually decreasing as the administrative level decreases and drill stages advance. Based on these findings, a systematic risk prevention matrix is proposed to offer targeted guidance for multi-level flood and typhoon prevention emergency drills in addressing climate change-induced disaster challenges. © 2025 The Authors

Developing rejuvenation strategies and artificial flood mitigation plans for Indrani River: a case study - Muhammed, Shaz P.; Holla, B.R.K.; Balakrishna, K.; Warrier, Anish Kumar (Scientific Reports, 2025)
Artificial flooding of rainwater is most common in urban areas due to various reasons, such as improper drainage systems, obstruction of natural drainage by building constructions, and encroachment of stormwater nallahs. Flash floods lead to significant losses, disrupt transportation, and cause inconvenience to the public. Udupi, characterized by its porous lateritic strata, undulating topography, and proximity to the sea, experiences artificial flooding during the peak monsoon season in its low-lying areas, primarily due to the overflow of the Indrani River, which is also a potential water resource for Udupi, Karnataka. Currently, the river faces significant challenges due to increasing anthropogenic activities. Revitalizing the Indrani River offers numerous benefits, including its potential use as a drinking water source during periods of water scarcity. This study aims to propose flood and stormwater management measures for the river catchment and to evaluate selected water quality parameters (pH, dissolved oxygen, and conductivity) at fifteen strategic locations along the river course. Higher conductivity observed at downstream stations is attributed to sewage discharge from urban settlements and a sewage treatment plant. The study suggests short-term measures such as targeted clean-up operations and stricter enforcement of pollution control regulations. Additionally, it recommends long-term strategies, including the development of a comprehensive river basin management plan, community engagement initiatives, and improvements to wastewater treatment infrastructure. To maintain the health of the Indrani River, this research emphasizes the importance of continuous monitoring and the implementation of integrated management practices. © The Author(s) 2025.

Effects of long-term wetland variations on flood risk assessments in the Yangtze River Basin - Guo, Ziying; Shi, Xiaogang; Zhang, Dingfan; Zhao, Qunshan (Environmental Impact Assessment Review, 2026)
Flooding is the most frequent natural disaster in the Yangtze River Basin (YRB), causing significant socio-economic damages. In recent decades, abundant wetland resources in the YRB have experienced substantial changes and played a significant role in strengthening the hydrological resilience to flood risks. However, wetland-related approaches remain underdeveloped for mitigating flood risks in the YRB due to the lack of considering long-term wetland effects in the flood risk assessment. Therefore, this study develops an wetland-related GIS-based spatial multi-index flood risk assessment model by incorporating the effects of wetland variations, to investigate the long-term implications of wetland variations on flood risks, to identify dominant flood risk indicators under wetland effects, and to provide wetland-related flood risk management suggestions. These findings indicate that wetlands in the Taihu Lake Basin, Wanjiang Plain, Poyang Lake Basin, and Dongting and Honghu Lake Basin could enhance flood control capacity and reduce flood risks in most years between 1985 and 2021 except years with extreme flood disasters. Wetlands in the Sichuan Basin have aggravated but limited impacts on flood risks. Precipitation in the Taihu Lake Basin and Poyang Lake Basin, runoff and vegetation cover in the Wanjiang Plain, GDP in the Taihu Lake Basin, population density in the Taihu lake Basin, Dongting and Honghu Lake Basin, and the Sichuan Basin are dominant flood risk indicators under wetland effects. Reasonably managing wetlands, maximizing stormwater storage capacity, increasing vegetation coverage in urbanized and precipitated regions are feasible suggestions for developing wetland-related flood resilience strategies in the YRB. © 2025 The Authors

Intrinsic drivers of urban flood disasters from the resilience perspective in China - Li, Xiaojuan; Chen, Rixin; Ren, Yifei; Jim, C.Y. (Reliability Engineering and System Safety, 2026)
Urban flood disasters pose substantial threats to public safety and urban development, with climate change exacerbating the intensity, frequency, and consequences of such events. While existing research has predominantly concentrated on flood control and disaster response, limited attention has been paid to the underlying drivers and evolutionary mechanisms of urban flood resilience. This study applies the resilience framework to develop an integrated methodology for assessing urban flood resilience. Focusing on three coastal provinces in China that frequently experience severe flooding, the study identifies fifteen key resilience drivers to construct a compound driver system. The evolution of flood resilience is examined through the lens of the Pressure-State-Response (PSR) model, which categorizes the drivers into three distinct dimensions. The Decision Making Trial and Evaluation Laboratory (DEMATEL) and Interpretative Structural Model (ISM) methods are employed to analyze the interrelationships and hierarchical structure among drivers. In parallel, a system dynamics (SD) modeling approach is used to construct causal-loop and stock-flow diagrams, revealing the complex interdependencies and critical pathways across resilience dimensions. The analysis identifies rainfall intensity as the most influential driver in shaping urban flood resilience. Scenario simulations based on the SD model explore variations in resilience performance under three developmental pathways. Findings suggest that enhancing response resilience is crucial under current flood control trajectories. This study contributes novel conceptual and methodological insights into the measurement and evolution of urban flood resilience. It offers actionable guidance for policymakers aiming to strengthen flood risk governance and urban safety. © 2025 Elsevier Ltd

Harnessing Vegetation as a Nature-Based Solution for Integrated River Corridor Management: A Path Towards Harmonized Human–Nature Synergy - Maurya, Om Prakash; Nandi, Ketan Kumar; Dutta, Subashisa (Ecohydrology, 2025)
This review examines the role of vegetation as a nature-based solution (NBS) for sustainable river corridor management, integrating a wide range of interdisciplinary domains. It synthesizes studies addressing global challenges in river systems, the worldwide adoption of vegetation-based solutions and location-specific field observations from major Indian rivers such as the Brahmaputra and Ganga. This paper also reviews flume-scale experiments on vegetation–flow interactions and explores the biomechanical properties of vegetation, such as root reinforcement that contribute to riverbank stability. In addition, it discusses the selection of suitable species based on specific climatic regions, as reported in the literature. Building on this interdisciplinary understanding, this review highlights the vital role of vegetation in mitigating bank erosion, regulating sediment transport, attenuating floods and enhancing the overall health and resilience of riverine ecosystems and communities. It proposes an integrated framework that combines vegetation with biodegradable materials such as bamboo fencing and geo-bags and conventional engineering measures to address high-flow conditions and ensure long-term riverbank stability. Additionally, a flume-scale physical model study was conducted to investigate near-bank hydrodynamics in the presence of a series of three spurs and a combination of rigid and flexible vegetation. The results indicate that vegetation significantly reduces streamwise velocity near the bank, achieving performance comparable to that of the spur arrangement. This study identifies key challenges, including appropriate species selection, long-term maintenance of vegetation-based solutions and the need for adaptive management strategies. It further emphasizes the importance of stakeholder engagement for successful and sustainable implementation. © 2025 John Wiley & Sons Ltd.

A systematic literature review of digital elevation models and hydrological models integration for advanced flood risk management - Ahmad, Raheel; Abdul Maulud, Khairul Nizam; Bin Zamir, Umair; Mohd Razali, Siti Fatin; Yaseen, Zaher Mundher; Pradhan, Biswajeet; Khan, Mohd Nazish; Eshquvvatov, Bekzod (Geomatics, Natural Hazards and Risk, 2025)
Floods are one of the most prevalent natural disasters, and advancements in geospatial technologies have revolutionized flood management, particularly the use of Digital Elevation Models (DEMs) in hydrological modelling. However, a comprehensive analysis DEMs integration in flood risk management is lacking. This study addresses this gap through a thorough Systematic Literature Review focusing on the combined application of DEMs and hydrological models in flood mitigation and risk management. The SLR scrutinized 21 articles, revealing eight key themes: DEM data sources and characteristics, DEM integration with hydrological models, flood hazard mapping applications, terrain impact assessment, model performance evaluation, machine learning in flood management, ecosystem services and resilience, and policy and governance implications. These findings emphasize the importance of precise DEM selection and correction for successful flood modelling, highlighting Advanced Land Observing Satellite as the most effective freely available DEM for use with the HEC-RAS unsteady flood model. This integration significantly enhances flood mitigation efforts and strengthens management strategies. Finally, this study underscores the pivotal role of DEM integration in crafting effective flood mitigation strategies, especially in addressing climate change challenges and bolstering community and ecosystem resilience. © 2025 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.

Role of the internet of things in flood risk management: a critical review on current practices and future directions - Bakhtiari, Vahid; Kerchi, Hamed Darabi; Piadeh, Farzad; Behzadian, Kourosh; Nasirzadeh, Farnad (Natural Hazards, 2025)
The Internet of Things (IoT) has become increasingly important in flood risk management (FRM). This trend emerged as climate change intensified flooding events, driving the urgent need for localised early warning systems. Previous studies demonstrated the effectiveness of IoT sensors in forecasting potential floods and supporting flood modelling. However, comprehensive research addressing all FRM stages - prevention, mitigation, preparedness, response, and recovery - has remained limited. To address this research gap, this study identified five key IoT sensor categories: water quantity, water quality, rainfall intensity, weather conditions, and catchment characteristics. The roles, objectives, and applications of these sensors across FRM stages were then investigated. Results showed that water quantity sensors were the most common, accounting for 48% of documented IoT applications. Weather condition sensors (27%) and rainfall intensity sensors (21%) were also widely used, especially after 2021. Additionally, IoT-based FRM had three primary Objectives flood modelling (61%), alerting (25%), and visualisation (14%). Most cases (42%) focused on the preparedness stage, while prevention (8%) and recovery (5%) were underrepresented, highlighting clear gaps in existing research. The review also revealed several overlooked sensor types, including groundwater level, biochemical oxygen demand, and nitrite sensors. Despite their potential to enhance quality-based flood modelling, these sensors were rarely utilised. Consequently, the study emphasised the need for broader integration of IoT sensors throughout all FRM stages. Such integration could support more resilient, data-driven flood management strategies, particularly in regions where IoT deployment has remained limited. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.

Research on the Comprehensive Evaluation Model of Risk in Flood Disaster Environments - Yu, Yan; Zhou, Tianhua (Water (Switzerland), 2025)
Losses from floods and the wide range of impacts have been at the forefront of hazard-triggered disasters in China. Affected by large-scale human activities and the environmental evolution, China’s defense flood situation is undergoing significant changes. This paper constructs a comprehensive flood disaster risk assessment model through systematic analysis of four key factors—hazard (H), exposure (E), susceptibility/sensitivity (S), and disaster prevention capabilities (C)—and establishes an evaluation index system. Using the Analytic Hierarchy Process (AHP), we determined indicator weights and quantified flood risk via the following formula R = H × E × V × C. After we applied this model to 16 towns in coastal Zhejiang Province, the results reveal three distinct risk tiers: low (R < 0.04), medium (0.04 ≤ R ≤ 0.1), and high (R > 0.1). High-risk areas (e.g., Longxi and Shitang towns) are primarily constrained by natural hazards and socioeconomic vulnerability, while low-risk towns benefit from a robust disaster mitigation capacity. Risk typology analysis further classifies towns into natural, social–structural, capacity-driven, or mixed profiles, providing granular insights for targeted flood management. The spatial risk distribution offers a scientific basis for optimizing flood control planning and resource allocation in the district. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Assessing Community Perception, Preparedness, and Adaptation to Urban Flood Risks in Malaysia - Kumaresen, Maniyammai; Teo, Fang Yenn; Selvarajoo, Anurita; Sivapalan, Subarna; Falconer, Roger A. (Water (Switzerland), 2025)
Urban flooding has significantly impacted the livelihoods of households and communities worldwide. It highlights the urgency of focusing on both flood preparedness and adaptation strategies to understand the community’s perception and adaptive capacity. This study investigates the levels of risk perception, flood preparedness, and adaptive capacity, while also exploring the inter-relationships among these factors within the context of urban flooding in Malaysia. A quantitative approach was employed, involving a structured questionnaire administered to residents in flood-prone urban areas across Greater Kuala Lumpur, Malaysia. A total of 212 responses were analysed using descriptive statistics, categorical index classification, and Spearman correlation analysis. The findings indicate that residents generally reported high levels of risk perception and preparedness, although adaptive capacity exhibited greater variability, with a mean score of 3.97 (SD = 0.64). Positive associations were found among risk perception, flood preparedness, and adaptive capacity. This study contributes to the existing knowledge by providing evidence on community resilience and highlighting key factors that can guide flood management policies and encourage adaptive planning at the community level. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Assessing Hydropower Impacts on Flood and Drought Hazards in the Lancang–Mekong River Using CNN-LSTM Machine Learning - Zhang, Muzi; Chi, Boying; Gu, Hongbin; Zhou, Jian; Chen, Honggang; Wang, Weiwei; Wang, Yicheng; Chen, Juanjuan; Yang, Xueqian; Zhang, Xuan (Water (Switzerland), 2025)
The efficient and rational development of hydropower in the Lancang–Mekong River Basin can promote green energy transition, reduce carbon emissions, prevent and mitigate flood and drought disasters, and ensure the sustainable development of the entire basin. In this study, based on publicly available hydrometeorological observation data and satellite remote sensing monitoring data from 2001 to 2020, a machine learning model of the Lancang–Mekong Basin was developed to reconstruct the basin’s hydrological processes, and identify the occurrence patterns and influencing mechanisms of water-related hazards. The results show that, against the background of climate change, the Lancang–Mekong Basin is affected by the increasing frequency and intensity of extreme precipitation events. In particular, Rx1day, Rx5day, R10mm, and R95p (extreme precipitation indicators determined by the World Meteorological Organization’s Expert Group on Climate Change Monitoring and Extreme Climate Events) in the northwestern part of the Mekong River Basin show upward trends, with the average maximum daily rainfall increasing by 1.8 mm/year and the total extreme precipitation increasing by 18 mm/year on average. The risks of flood and drought disasters will continue to rise. The flood peak period is mainly concentrated in August and September, with the annual maximum flood peak ranging from 5600 to 8500 m3/s. The Stung Treng Station exhibits longer drought duration, greater severity, and higher peak intensity than the Chiang Saen and Pakse Stations. At the Pakse Station, climate change and hydropower development have altered the non-drought proportion by −12.50% and +15.90%, respectively. For the Chiang Saen Station, the fragmentation degree of the drought index time series under the baseline, naturalized, and hydropower development scenarios is 0.901, 1.16, and 0.775, respectively. These results indicate that hydropower development has effectively reduced the frequency of rapid drought–flood transitions within the basin, thereby alleviating pressure on drought management efforts. The regulatory role of the cascade reservoirs in the Lancang River can mitigate risks posed by climate change, weaken adverse effects, reduce flood peak flows, alleviate hydrological droughts in the dry season, and decrease flash drought–flood transitions in the basin. The research findings can enable basin managers to proactively address climate change, develop science-based technical pathways for hydropower dispatch, and formulate adaptive disaster prevention and mitigation strategies. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Identification of Critical Exposed Elements and Strategies for Mitigating Secondary Hazards in Flood-Induced Coal Mine Accidents - Yang, Xue; Liu, Chen; Pan, Langxuan; Su, Xiaona; He, Ke; Mao, Ziyu (Water (Switzerland), 2025)
Natech events, involving multi-hazard coupling and cascading effects, pose serious threats to coal mine safety. This paper addresses flood-induced Natech scenarios in coal mining and introduces a two-stage cascading analysis framework based on hazard systems theory. A tri-layered network—comprising natural hazards, exposed elements, and secondary hazards—models hazard propagation. In Stage 1, an improved adjacency information entropy algorithm with multi-hazard coupling coefficients identifies critical exposed elements. In Stage 2, Dijkstra’s algorithm extracts key risk transmission paths. A dual-dimensional classification method, based on entropy and transmission risk, is then applied to prioritize emergency responses. This method integrates the criticality of exposed elements with the risk levels associated with secondary disaster propagation paths. Case studies validate the framework, revealing: (1) Hierarchical heterogeneity in the network, with surface facilities and surrounding hydrological systems as central hubs; shaft and tunnel systems and surrounding geological systems are significantly affected by propagation from these core nodes, exhibiting marked instability. (2) Strong risk polarization in secondary hazard propagation, with core-node-originated paths being more efficient and urgent. (3) The entropy-risk classification enables targeted hazard control, improving efficiency. The study proposes chain-breaking strategies for precise, hierarchical, and timely emergency management, enhancing coal mine resilience to flood-induced Natech events. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Response of Grain Yield to Extreme Precipitation in Major Grain-Producing Areas of China Against the Background of Climate Change—A Case Study of Henan Province - Sheng, Keding; Li, Rui; Zhang, Fengqiuli; Chen, Tongde; Liu, Peng; Hu, Yanan; Li, Bingyin; Song, Zhiyuan (Water (Switzerland), 2025)
Based on the panel data of daily meteorological stations and winter wheat yield in Henan Province from 2000 to 2023, this study comprehensively used the Mann–Kendall trend test, wavelet coherence analysis (WTC), and other methods to reveal the temporal and spatial evolution of extreme precipitation and its multi-scale stress mechanism on grain yield. The results showed the following: (1) Extreme precipitation showed the characteristics of ‘frequent fluctuation-gentle trend-strong spatial heterogeneity’, and the maximum daily precipitation in spring (RX1DAY) showed a significant uplift. The increase in rainstorm events (R95p/R99p) in the southern region during the summer is particularly prominent; at the same time, the number of consecutive drought days (CDDs > 15 d) in the middle of autumn was significantly prolonged. It was also found that 2010 is a significant mutation node. Since then, the synergistic effect of ‘increasing drought days–increasing rainstorm frequency’ has begun to appear, and the short-period coherence of super-strong precipitation (R99p) has risen to more than 0.8. (2) The spatial pattern of winter wheat in Henan is characterized by the three-level differentiation of ‘stable core area, sensitive transition zone and shrinking suburban area’, and the stability of winter wheat has improved but there are still local risks. (3) There is a multi-scale stress mechanism of extreme precipitation on winter wheat yield. The long-period (4–8 years) drought and flood events drive the system risk through a 1–2-year lag effect (short-period (0.5–2 years) medium rainstorm intensity directly impacted the production system). This study proposes a ‘sub-scale governance’ strategy, using a 1–2-year lag window to establish a rainstorm warning mechanism, and optimizing drainage facilities for high-risk areas of floods in the south to improve the climate resilience of the agricultural system against the background of climate change. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Hydrology and Climate Change in Africa: Contemporary Challenges, and Future Resilience Pathways - Adeyeri, Oluwafemi E. (Water, 2025)
African hydrological systems are incredibly complex and highly sensitive to climate variability. This review synthesizes observational data, remote sensing, and climate modeling to understand the interactions between fluvial processes, water cycle dynamics, and anthropogenic pressures. Currently, these systems are experiencing accelerating warming (+0.3 °C/decade), leading to more intense hydrological extremes and regionally varied responses. For example, East Africa has shown reversed temperature–moisture correlations since the Holocene onset, while West African rivers demonstrate nonlinear runoff sensitivity (a threefold reduction per unit decline in rainfall). Land-use and land-cover changes (LULCC) are as impactful as climate change, with analysis from 1959–2014 revealing extensive conversion of primary non-forest land and a more than sixfold increase in the intensity of pastureland expansion by the early 21st century. Future projections, exemplified by studies in basins like Ethiopia’s Gilgel Gibe and Ghana’s Vea, indicate escalating aridity with significant reductions in surface runoff and groundwater recharge, increasing aquifer stress. These findings underscore the need for integrated adaptation strategies that leverage remote sensing, nature-based solutions, and transboundary governance to build resilient water futures across Africa’s diverse basins.
Keywords: Scopus_Alert_22_Aout_2025

Nature-Based Solutions for Water Management in Europe: What Works, What Does Not, and What’s Next? - Santos, Eleonora (Water, 2025)
Nature-based solutions (NbS) are increasingly recognized as strategic alternatives and complements to grey infrastructure for addressing water-related challenges in the context of climate change, urbanization, and biodiversity decline. This article presents a critical, theory-informed review of the state of NbS implementation in European water management, drawing on a structured synthesis of empirical evidence from regional case studies and policy frameworks. The analysis found that while NbS are effective in reducing surface runoff, mitigating floods, and improving water quality under low- to moderate-intensity events, their performance remains uncertain under extreme climate scenarios. Key gaps identified include the lack of long-term monitoring data, limited assessment of NbS under future climate conditions, and weak integration into mainstream planning and financing systems. Existing evaluation frameworks are critiqued for treating NbS as static interventions, overlooking their ecological dynamics and temporal variability. In response, a dynamic, climate-resilient assessment model is proposed—grounded in systems thinking, backcasting, and participatory scenario planning—to evaluate NbS adaptively. Emerging innovations, such as hybrid green–grey infrastructure, adaptive governance models, and novel financing mechanisms, are highlighted as key enablers for scaling NbS. The article contributes to the scientific literature by bridging theoretical and empirical insights, offering region-specific findings and recommendations based on a comparative analysis across diverse European contexts. These findings provide conceptual and methodological tools to better design, evaluate, and scale NbS for transformative, equitable, and climate-resilient water governance.
Keywords: Scopus_Alert_22_Aout_2025

Identification of flood vulnerability areas using analytical hierarchy process techniques in the Wuseta watershed, Upper Blue Nile Basin, Ethiopia - Mulu, Arega; Kassa, Samuel Berihun; Wossene, Mindesilew Lakew; Adefris, Sintayehu; Meshesha, Taye Minchil (Scientific Reports, 2025)
Flooding, caused by the excessive accumulation of water on land, disrupts activities in floodplain regions, particularly during the rainy season. The main objective is to map Flood vulnerability areas and identify regions most vulnerable to flooding to inform effective flood management strategies using an integrated approach that combines remote sensing, geographic information systems (GIS), and the analytical hierarchy process (AHP) to assess Flood vulnerability in the Wuseta Watershed. The research was conducted in three phases: pre-fieldwork, fieldwork, and post-fieldwork. Key factors influencing Flood vulnerability such as drainage density, elevation, land use/land cover, and slope were hierarchically weighted to produce a Flood vulnerability map. Rainfall distribution was not considered as a contributing factor the Ethiopian Meteorological Agency has installed only one weather station in the study area, located in Wuseta watershed. As a result, the rainfall distribution is considered uniform throughout the watershed, making it unsuitable for flood susceptibility assessment. The Flood vulnerability map categorizes the watershed into five zones: very high (0.07 km2), high (4.65 km2), moderate (7.86 km2), slight (4.41 km2), and very slight (0.001 km2). The results show that the upstream, northern, northwestern, and northeastern areas of the watershed face slight to very slight Flood vulnerability, while the southern region is highly vulnerable to flooding. These findings provide valuable insights for policymakers and local communities, aiding in the development of targeted mitigation strategies and raising awareness of flood-prone areas. This study underscores the value of integrating geospatial technologies and multi-criteria decision analysis in flood risk assessment, particularly in data-scarce regions, to enhance disaster preparedness and climate resilience. © The Author(s) 2025.
Keywords: Scopus_Alert_15_Aout_2025

Multi-Criteria Decision Analysis for Managed Aquifer Recharge (MAR): A Flood-Responsive Approach in Milpa Alta, Mexico City - Areu-Rangel, Omar S.; Singh, Amrie; Bonasia, Rosanna (Environmental Quality Management, 2025)
Milpa Alta, located southeast of Mexico City, is a key region for environmental sustainability due to its volcanic soil, biodiversity, and critical role in aquifer recharge, which supports the city's water supply. However, rapid urbanization has severely impacted the area, causing reduced vegetation cover, increased runoff, and diminished groundwater recharge, which intensify flooding, soil erosion, and water scarcity. This study aims to identify optimal sites for managed aquifer recharge (MAR) structures in Milpa Alta through a multi-criteria analysis incorporating criteria such as topography, land use, proximity to urban areas, and drainage networks. Uniquely, hydraulic simulations of flood scenarios were integrated into the analysis to improve the precision of site selection. Geographic information systems (GIS) were used to assess and combine these criteria, providing a spatial evaluation of suitability. Results indicate that the central and northern regions of Milpa Alta, particularly around San Francisco Tecoxpa and San Antonio Tecómitl, are most suitable for MAR implementation due to their permeable soils, gentle slopes, and proximity to agricultural lands and drainage networks. These MAR structures can enhance groundwater recharge and mitigate flood risks during extreme rainfall events, with the potential to capture up to 300,000 m3 of surface runoff during a single high-intensity storm event. Despite its strengths, the study acknowledges limitations such as the absence of detailed water quality analyses and the need for sensitivity testing of the criteria weighting. This research provides an innovative approach to MAR site selection by integrating flood simulations, offering a replicable model for similar regions. Successful implementation of MAR in Milpa Alta requires addressing water quality concerns, engaging stakeholders, and ensuring compliance with regulatory frameworks. The findings emphasize MAR's potential to balance urbanization pressures with sustainable water management and flood mitigation strategies in Mexico City's rapidly developing areas. © 2025 Wiley Periodicals LLC.
Keywords: Scopus_Alert_15_Aout_2025

HyEco: A hybrid hydrodynamic-cum-ecological modelling framework to demystify flood and human-health risks over flood-prone metropolis - Deopa, Rahul; Mohanty, Mohit Prakash (Water Research X, 2025)
Urban flooding, exacerbated by climate change and unregulated urbanization, poses significant risks to the built environment. In addition to physical damage, floodwaters often mobilize a hazardous mix of untreated sewage, industrial effluents, and undesirable pollutants, leading to severe microbial contamination in the floodwaters. This study introduces “HyEco”-an integrated framework comprising high-fidelity 3-way coupled hydrodynamic and ecological modelling with an aim to capture the “unhidden tangible flood risks” and “hidden intangible public-health risks” in tandem. Focusing on Delhi, India, a densely populated metropolis prone to recurrent urban flooding and associated health crises, the framework simulates the 2023 mega-flood event. Results show that approximately 63.5 % of the region is categorized under ‘high’ to ‘very high’ flood risk zones, with over 20 % of these areas housing around 15 % of the city's dense population. The hydrodynamic model outputs were forced into the ecological model to simulate the fate and transport of microbial contamination in floodwaters. Escherichia coli concentrations ranged from 772,868 to 790,000 MPN/100 mL, far exceeding established safety thresholds. A Quantitative Microbial Risk Assessment (QMRA) reveals elevated infection probabilities, particularly among children, with risks up to 2.60×10⁻³ under repeated exposure and 8.38×10⁻⁴ to 8.57×10⁻⁴ for pedestrian splash exposures. Unlike prior approaches that examine flood and microbial risks in isolation or depend on static datasets, HyEco overcomes key methodological gaps by dynamically integrating flood and microbial processes at high spatio-temporal resolution. The HyEco framework offers a scalable and actionable tool for integrated flood risk management and climate-resilient public health planning. © 2025
Keywords: Scopus_Alert_15_Aout_2025

Climate-smart water management in rice paddies: a meta-synthesis on greenhouse gas emissions and yield impacts - Minamikawa, Kazunori (Paddy and Water Environment, 2025)
Water management practices in rice paddies, particularly alternate wetting and drying and midseason drainage followed by intermittent irrigation, are widely recognized for reducing methane (CH4) emissions and irrigation water use compared to continuous flooding (CF). However, these practices also increase nitrous oxide (N2O) emissions and their effect on rice yield remains unclear, especially in the context of technology dissemination to farmers. This study (1) reviews 11 recent meta-analyses on CH4 and N2O emissions and rice yield and (2) synthesizes their reported effects on rice growth and yield. Aggregated data show that CH4 emissions decreased by 31–62% (n = 10), while N2O emissions increased by 37–445% (n = 7), relative to CF. Rice yield change ranged from − 5.4% to + 11% with a mean of + 1.3% (n = 8). The impact of water management on rice yield varied depending on the timing and intensity of drainage events, with excessive water stress—particularly during the heading stage—and prolonged reductive soil conditions being key risk factors. Results indicate that mild-intensity drainage practices, such as ‘safe AWD,’ not only avoid yield penalties but can significantly enhance rice productivity when tailored to favorable environmental and agronomic conditions. For effective dissemination of these practices, leveraging yield improvement as an incentive for farmers is essential. Optimizing drainage schedules in accordance with rice physiological stages and local conditions is critical. With appropriate localization, water management can serve as a climate-smart strategy that simultaneously improves water efficiency, reduces greenhouse gas emissions, and maintains or increases rice productivity. © The Author(s) 2025.
Keywords: Scopus_Alert_15_Aout_2025

A REVIEW OF THE IMPACT OF EXTREME WEATHER EVENTS ON FRESHWATER, TERRESTRIAL AND MARINE ECOSYSTEMS - Eichelmann, Elke; Naber, Nadeem; Battamo, Ashenafi Yohannes; O’Sullivan, John J.; Salauddin; Kelly-Quinn, Mary (Biology and Environment, 2025)
Extreme weather events (EWEs), including floods, droughts, heatwaves and storms, are increasingly recognised as major drivers of biodiversity loss and ecosystem degradation. In this systematic review, we synthesise 251 studies documenting the impacts of extreme weather events on freshwater, terrestrial and marine ecosystems, with the goal of informing effective conservation and management strategies for areas of special conservation or protection focus in Ireland.Twenty-two of the reviewed studies included Irish ecosystems. In freshwater systems, flooding (34 studies) was the most studied EWE, often linked to declines in species richness, abundance and ecosystem function. In terrestrial ecosystems, studies predominantly addressed droughts (60 studies) and extreme temperatures (48 studies), with impacts including increase in mortality, decline in growth and shift in species composition. Marine and coastal studies focused largely on storm events (33 studies), highlighting physical damages linked to wave actions, behavioural changes in macrofauna, changes in species composition and distribution, and loss in habitat cover. Results indicate that most EWEs lead to negative ecological responses, although responses are context specific.While positive responses to EWEs are rare, species with adaptive traits displayed some resilience, especially in ecosystems with high biodiversity or refuge areas.These findings underscore the need for conservation strategies that incorporate EWE projections, particularly for protected habitats and species. © 2025 Royal Irish Academy. All rights reserved.
Keywords: Scopus_Alert_15_Aout_2025

Systematic review of flood resilience strategies in Lagos Metropolis: pathways toward the 2030 sustainable development agenda - Orimoogunje, Oluwagbenga; Aniramu, Opeyemi (Frontiers in Climate, 2025)
Flooding presents a significant challenge in the Lagos metropolis, driven by rapid urbanization, poor drainage infrastructure, and climate change. This study evaluates flood resilience strategies in Lagos, analyzing their effectiveness in mitigating flood risks and their alignment with the 2030 Agenda. The research utilizes the PICO (Population, Intervention, Control, and Outcomes) framework to refine research questions and follows PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines for study selection, search strategies, and data extraction. A thorough search across databases such as Google Scholar, SCOPUS, and government data repositories was conducted to ensure the inclusion of relevant studies while minimizing selection bias. The study emphasizes the severe impacts of flooding, referencing the 2022–2023 flood event which resulted in USD 262,500 damages and displaced 8000 residents in Lagos State. Current flood resilience strategies are inadequate to meet the Sustainable Development Goals (SDGs) due to insufficient urban flood infrastructure, poor waste disposal practices, and worsening climatic conditions. The livelihoods, income, health, and overall survival of vulnerable communities are at significant risk. Key gaps identified include the weak enforcement of urban planning regulations, limited community engagement, ineffective early warning systems, and poor intervention initiatives. This study suggests a multi-stakeholder approach that enhances both structural and non-structural flood resilience. Improving drainage systems, promoting sustainable waste management, improving climate adaptation policies, and fostering community-based flood mitigation strategies are crucial for achieving long-term urban resilience. These findings offer valuable insights for policymakers, urban planners, and climate resilience advocates working toward the Sustainable Development Agenda in Lagos metropolis. Copyright © 2025 Orimoogunje and Aniramu.
Keywords: Scopus_Alert_15_Aout_2025

Entendre et comprendre les expériences de désastre par la recherche narrative - Leclerc, Typhaine; Lessard, Lily; Saint-Charles, Johanne (Intervention, 2024)
Les événements météorologiques extrêmes (EME) et les désastres qu’ils entrainent provoquent des conséquences psychosociales qui sont modulées en fonction de différents facteurs sociaux. On constate aussi que les récits médiatiques et culturels qui circulent au sujet des EME ne sont pas représentatifs de l’ensemble des expériences de personnes sinistrées : celles qui en subissent les conséquences les plus sévères tendent aussi à être celles qu’on « entend » le moins dans l’espace public. Ces personnes sont ainsi susceptibles de vivre de l’injustice épistémique, ce qui a des effets délétères sur le soutien qu’elles reçoivent. Face à ces constats s’impose la nécessité de mieux comprendre la diversité des expériences d’EME et d’explorer des stratégies pour soutenir l’ensemble des personnes sinistrées dans leur rétablissement psychosocial. Cet article soutient que la recherche narrative peut contribuer à répondre à ces objectifs. En dépeignant des réalités multiples, la recherche narrative centrée sur les récits de personnes sinistrées présente aussi un intérêt significatif pour l’amélioration des pratiques d’intervention en contexte de désastre. , Extreme weather events (EWE) and their resulting disasters cause psychosocial consequences that are moderated by different social factors. Media and cultural accounts of EWEs do not represent the full range of disaster survivor experiences, that is, those who experienced the most severe consequences also tend to be those least “heard” in the public arena. These people are therefore most likely to experience forms of epistemic injustice that negatively impact the support offered to cope with disaster. Considering these findings, there is a need to better understand the diversity of EWE experiences and explore strategies for supporting all disaster survivors in their psychosocial recovery. This article argues that narrative research can help meet these needs. By portraying the multiple realities of people affected by EWEs, narrative research focusing on the stories of disaster survivors is also of significant interest for improving intervention practices in this context.

Enhancing Research-to-Operations in Hydrological Forecasting: Innovations across Scales and Horizons - Pechlivanidis, Ilias G.; Du, Yiheng; Bennett, James; Boucher, Marie-Amélie; Chang, Annie Y. Y.; Crochemore, Louise; Dasgupta, Antara; Di Baldassarre, Giuliano; Luterbacher, Jürg; Pappenberger, Florian; Ramos, Maria-Helena; Slater, Louise; et al. (Bulletin of the American Meteorological Society, 2025)
Abstract Over the past 20 years, the Hydrological Ensemble Prediction Experiment (HEPEX) international community of practice has advanced the science and practice of hydrological ensemble prediction and its application in impact- and risk-based decision-making, fostering innovations through cutting-edge techniques and data that enhance water-related sectors. Here, we present insights from those 20 years on the key priorities for (co)creating broadly applicable hydrological forecasting systems that add value across spatial scales and time horizons. We highlight the advancement of hydrological forecasting chains through rigorous data management that incorporates diverse, high-quality data sources, data assimilation techniques, and the application of artificial intelligence (AI) to improve predictive accuracy. HEPEX has played a critical role in enhancing the reliability of water resources and water-related risk management globally by standardizing ensemble forecasting. This effort complements HEPEX’s broader initiative to strengthen research to operations, making innovative forecasting solutions both practical and accessible. Additionally, efforts have been made toward supporting the United Nations Early Warnings for All initiative through developing robust and reliable early warning systems by means of global training, education and capacity development, and the sharing of technology. Finally, we note that the integration of advanced science, user-centric methods, and global collaboration can provide a solid framework for improving the prediction and management of hydrological extremes, aligning forecasting systems with the dynamic needs of water resource and risk management in a changing climate. To effectively meet future demands, it is crucial to accelerate the integration of innovative science within operational frameworks, fostering adaptable and resilient hydrological forecasting systems globally.
Keywords: Infolettre_Ete_2025

The Needs, Challenges, and Priorities for Advancing Global Flood Research - Samadi, Vidya; Fowler, Hayley J.; Lamond, Jessica; Wagener, Thorsten; Brunner, Manuela; Gourley, Jonathan; Moradkhani, Hamid; Popescu, Ioana; Wasko, Conrad; Wright, Daniel; Wu, Huan; Zhang, Ke; et al. (WIREs Water, 2025)
ABSTRACT In recent years, numerous flood events have caused loss of life, widespread disruption, and damage across the globe. These devastating impacts highlight the importance of a better understanding of flood generating processes, their impacts, and their variability under climate and landscape changes. Here, we argue that the ability to better model flooding is underpinned by the grand challenge of understanding flood generation mechanisms and potential impacts. To address this challenge, the World Meteorological Organization‐Global Energy and Water Exchanges (GEWEX) Hydrometeorology Panel (GHP) aims to establish a Global Flood Crosscutting project to propagate flood modeling and research knowledge across regions and to synthesize results at the global scale. This paper outlines a framework for understanding the dynamics and impacts of runoff generation processes and a rationale for the role of a Global Flood Crosscutting project to address these challenges. Within this Global Flood Crosscutting project, we will establish a common terminology and methods to enable the global research community to exchange knowledge and experiences, and to design experiments toward developing actionable recommendations for more effective flood management practices and policies for improved resilience. This harmonization of rich perspectives across disciplines will foster the co‐production of knowledge primed to advance flood research, particularly in the current period of heightened climate variability and rapid change. It will create a new transdisciplinary paradigm for flood science, wherein different dimensions of mechanistic understanding and processes are rigorously considered alongside socioeconomic impacts, early warning communications, and longer‐term adaptation to alleviate flood risks in society.
Keywords: Infolettre_Ete_2025

Full-scale characterization of the effects of a bioretention system on water quality and quantity following the replacement of a mixed stormwater and combined sewer system - Le Cauchois, Pia; Doucet, Samuel; Bouattour, Ons; McQuaid, Natasha; Beral, Henry; Kõiv-Vainik, Margit; Bichai, Françoise; McCarthy, David; St-Laurent, Julien; Dagenais, Danielle; Bennekrela, Nesrine; Guerra, Juan; et al. (Blue-Green Systems, 2025)
ABSTRACT Urbanization is leading to more frequent flooding as cities have more impervious surfaces and runoff exceeds the capacity of combined sewer systems. In heavy rainfall, contaminated excess water is discharged into the natural environment, damaging ecosystems and threatening drinking water sources. To address these challenges aggravated by climate change, urban blue-green water management systems, such as bioretention cells, are increasingly being adopted. Bioretention cells use substrate and plants adapted to the climate to manage rainwater. They form shallow depressions, allowing infiltration, storage, and gradual evacuation of runoff. In 2018, the City of Trois-Rivières (Québec, Canada) installed 54 bioretention cells along a residential street, several of which were equipped with access points to monitor performance. Groundwater quality was monitored through the installation of piezometers to detect potential contamination. This large-scale project aimed to improve stormwater quality and reduce sewer flows. The studied bioretention cells reduced the flow and generally improved water quality entering the sewer system, as well as the quality of stormwater, with some exceptions. Higher outflow concentrations were observed for contaminants such as manganese and nitrate. The results of this initiative provide useful recommendations for similar projects for urban climate change adaptation.
Keywords: Infolettre_Ete_2025

Impacts of Adjusting Solid Precipitation Amounts in the Canadian Precipitation Analysis System - Aubry, Catherine; Bélair, Stéphane; Thériault, Julie M.; Mekis, Eva; Feng, Pei-Ning; Lespinas, Franck; Khedhaouiria, Dikra; Beaudry, Florence (Journal of Applied Meteorology and Climatology, 2025)
Abstract Real-time precipitation data are essential for weather forecasting, flood prediction, drought monitoring, irrigation, fire prevention, and hydroelectric management. To optimize these activities, reliable precipitation estimates are crucial. Environment and Climate Change Canada (ECCC) leads the Canadian Precipitation Analysis (CaPA) project, providing near-real-time precipitation estimates across North America. However, during winter, CaPA’s 6-hourly accuracy is limited because many automatic surface observations are not assimilated due to wind-induced gauge undercatch. The objective of this study is to evaluate the added value of adjusted hourly precipitation amounts for gauge undercatch due to wind speed in CaPA. A recent ECCC dataset of hourly precipitation measurements from automatic precipitation gauges across Canada is included in CaPA as part of this study. Precipitation amounts are adjusted based on several types of transfer functions, which convert measured precipitation into what high-quality equipment would have measured with reduced undercatch. First, there are no notable differences in CaPA when comparing the performance of the universal transfer function with that of several climate-specific transfer functions based on wind speed and air temperature. However, increasing solid precipitation amounts using a specific type of transfer function that depends on snowfall intensity rather than near-surface air temperature is more likely to improve CaPA’s precipitation estimates during the winter season. This improvement is more evident when the objective evaluation is performed with direct comparison with the Adjusted Daily Rainfall and Snowfall (AdjDlyRS) dataset.
Keywords: Infolettre_Ete_2025

The Impact of Flood Adaptation Measures on Affected Population’s Mental Health: A mixed method Scoping Review - El-Mousawi, Fatima; Ortiz, Ariel Mundo; Berkat, Rawda; Nasri, Bouchra (Cold Spring Harbor Laboratory, 2023)
AbstractThe frequency and severity of floods has increased in different regions of the world due to climate change. Although the impact of floods on human health has been extensively studied, the increase in the segments of the population that are likely to be impacted by floods in the future makes it necessary to examine how adaptation measures impact the mental health of individuals affected by these natural disasters. The goal of this scoping review is to document the existing studies on flood adaptation measures and their impact on the mental health of affected populations, in order to identify the best preventive strategies as well as limitations that deserve further exploration. This study employed the methodology of the PRISMA-ScR extension for scoping reviews to systematically search the databases Medline and Web of Science to identify studies that examined the impact of adaptation measures on the mental health of flood victims. The database queries resulted in a total of 857 records from both databases. Following two rounds of screening, 9 studies were included for full-text analysis. Most of the analyzed studies sought to identify the factors that drive resilience in flood victims, particularly in the context of social capital (6 studies), whereas the remaining studies analyzed the impact of external interventions on the mental health of flood victims, either from preventive or post-disaster measures (3 studies). There is a very limited number of studies that analyze the impact of adaptation measures on the mental health of populations and individuals affected by floods, which complicates the generalizability of their findings. There is a need for public health policies and guidelines for the development of flood adaptation measures that adequately consider a social component that can be used to support the mental health of flood victims.

Éduquer aux risques dès l’école primaire: de la représentation à la conscientisation - Julien, Marie-Pierre; Bédouret, David; Chalmeau, Raphaël; Mainar, Christine Vergnolle; Léna, Jean-Yves; Calvet, Anne (VertigO - la revue électronique en sciences de l'environnement, 2021)
Le territoire de la vallée du Gave de Gavarnie a connu un épisode d’inondation/crue particulièrement catastrophique en 2013, ayant entrainé de forts dégâts matériels et des pertes humaines. Dans ce contexte, la culture du risque est un enjeu tant pour les acteurs de la gestion de ce territoire que pour les citoyens, d’autant plus que les risques présents y sont multiples (avalanches, glissements de terrain et séismes). Dans cette perspective, l’école peut jouer un rôle déterminant à travers la mise en place de projets d’éducations au(x) risque(s). Ce type d’éducation doit commencer par la perception et la conscience du (des) risque(s), rendues possibles par le vécu et/ou par la culture du groupe dans lequel l’élève vit. Cette étude a pour objectif d’examiner les représentations et la perception du risque des élèves d’une école élémentaire française située sur une commune fortement impactée par cette crue, et l’évolution de ces représentations et cette perception un an après la mise en œuvre du projet éducatif. Les résultats montrent une représentation plurielle du risque par les élèves avec des différences entre classes. La classe de CP-CE (enfants âgés de 6 à 8 ans) associe essentiellement le risque à l’aléa naturel (avalanche, inondation…) alors que les élèves en CM (enfants âgés de 9 à 10 ans) sont centrés sur ce qui pourrait leur arriver (accident, maladie…). Le risque inondation/crue est dans un premier temps très peu évoqué dans les représentations des élèves, mais lorsque les activités pédagogiques permettent de contextualiser cette notion sur leur territoire, il est alors plus fortement perçu.

Investigating incomplete mixing models in cross junctions under real-world conditions of water distribution networks - Yousefian, Reza; Duchesne, Sophie; Schwarz, Pierre-Olivier (Water Supply, 2024)
Questions have been raised about the correctness of water quality models with complete mixing assumptions in cross junctions of water distribution systems. Recent developments in the mixing phenomenon within cross junctions of water distribution networks (WDNs) have heightened the need for evaluating the existing incomplete mixing models under real-world conditions. Therefore, in this study, two cross junctions with pipe diameters of 100 Â 100 Â 100 Â 100 mm and 150 Â 150 Â 150 Â 150 mm were employed in laboratory experiments to evaluate six existing incomplete mixing models for 25 ﬂow rate scenarios ranging between 1.5 and 3.0 L/s. It was observed that within the same ﬂow rate scenario, the degree of mixing in a cross junction with a pipe relative roughness of 6.00 Â 10À5 (pipe diameter of 25 mm) was higher than that in a cross junction with a pipe relative roughness of 3.00 Â 10À5 (pipe diameter of 50 mm) and smaller. Considering the real-world size of pipes in evaluating the incomplete mixing models showed that two incomplete mixing models, AZRED and the one by Shao et al., had the best accordance with the results of the laboratory experiments.

Integration of Incomplete Mixing at Junctions of Water Distribution Networks in Contamination Source Identification Tools - Yousefian, Reza; Émond, Laurent; Duchesne, Sophie (Journal of Water Resources Planning and Management, 2025)
The water quality models used in contamination source identification (CSI) tools assume complete mixing at the junctions of drinking water distribution networks. Two extensions of the contamination status algorithm (CSA)—a CSI tool that employs water quality models in a reverse-time manner—were accordingly developed in this study, one assuming complete mixing (CSA-CMX) and the other assuming incomplete mixing (CSA-IMX) at cross-junctions. Both algorithms identified contamination sources based on the results of grab sampling at iteratively suggested locations. The performances of CSA-CMX and CSA-IMX were evaluated through laboratory experiments using three contamination identification problems: CSA-IMX identified the contamination source in all three problems, whereas CSA-CMX identified the contamination source in only one. Furthermore, the specificity (i.e., the ability to distinguish the real contamination source from other possible contamination sources) was higher for CSA-IMX than for CSA-CMX in two of the three problems. Therefore, the incomplete mixing assumption was confirmed to be a crucial factor in CSI tools.

Evaluating real-time control of stormwater drainage network and green stormwater infrastructure for enhancing flooding resilience under future rainfall projections - Li, Jiada; Burian, Steven J. (Resources, Conservation and Recycling, 2023)
Traditional stormwater control measures are designed to handle system loadings induced by fixed-size storm events. However, climate change is predicted to alter the frequency and intensity of flooding events, stimulating the need to explore another more adaptive flooding solution like real-time control (RTC). This study assesses the performance of RTC to mitigate impacts of climate change on urban flooding resilience. A simulated, yet realistic, urban drainage system in Salt Lake City, Utah, USA, shows that RTC improves the flooding resilience by up to 17% under climatic rainfall changes. Compared with green stormwater infrastructure (GSI), RTC exhibits a lower resistibility, lower flooding failure level, and higher recovery rate in system performance curves. Results articulate that keeping RTC's performance consistent under ‘back-to-back’ storms requires a tradeoff between upstream dynamical operation and downstream flooding functionality loss. This research suggests that RTC provides a path towards smart and resilient stormwater management strategy.

Adaptation of Dual Drainage to Control Flooding and Enhance Combined Sewer Systems in Highly Urbanized Areas - Ossa Ossa, Juan Esteban; Duchesne, Sophie; Pelletier, Geneviève (2024)
Combined sewer surcharges in densely urbanized areas have become more frequent due to the expansion of impervious surfaces and intensified precipitation caused by climate change. These surcharges can generate system overflows, causing urban flooding and pollution of urban areas. This paper presents a novel methodology to mitigate sewer system surcharges and control surface water. In this methodology, flow control devices and urban landscape retrofitting are proposed as strategies to reduce water inflow into the sewer network and manage excess water on the surface during extreme rainfall events. For this purpose, a 1D/2D dual drainage model was developed for two case studies located in Montreal, Canada. Applying the proposed methodology to these two sites led to a reduction of the volume of wastewater overflows by 100% and 86%, and a decrease in the number of surface overflows by 100% and 71%, respectively, at the two sites for a 100-year return period 3-h Chicago design rainfall. It also controlled the extent of flooding, reduced the volume of uncontrolled surface floods by 78% and 80% and decreased flooded areas by 68% and 42%, respectively, at the two sites for the same design rainfall.

Flood inundation modeling in ungauged basins using Unmanned Aerial Vehicles imagery - Yavari, Adel; Homayouni, Saeid; Oubennaceur, Khalid; Chokmani, Karem (Earth Observation and Geomatics Engineering, 2020)
This paper presents a new framework for floodplain inundation modeling in an ungauged basin using unmanned aerial vehicles (UAVs) imagery. This method is based on the integrated analysis of high-resolution ortho-images and elevation data produced by the structure from motion (SfM) technology. To this end, the Flood-Level Marks (FLMs) were created from high-resolution UAV ortho-images and compared to the flood inundated areas simulated using the HEC-RAS hydraulic model. The flood quantiles for 25, 50, 100, and 200 return periods were then estimated by synthetic hydrographs using the Natural Resources Conservation Service (NRCS). The proposed method was applied to UAV image data collected from the Khosban village, in Taleghan County, Iran, in the ungauged sub-basin of the Khosban River. The study area is located along one kilometre of the river in the middle of the village. The results showed that the flood inundation areas modeled by the HEC-RAS were 33%, 19%, and 8% less than those estimated from the UAV’s FLMs for 25, 50, and 100 years return periods, respectively. For return periods of 200 years, this difference was overestimated by more than 6%, compared to the UAV’s FLM. The maximum flood depth in our four proposed scenarios of hydraulic models varied between 2.33 to 2.83 meters. These analyses showed that this method, based on the UAV imagery, is well suited to improve the hydraulic modeling for seasonal inundation in ungauged rivers, thus providing reliable support to flood mitigation strategies

Impacts et coûts indirects des stresseurs secondaires sur la santé biopsychosociale des sinistrés des inondations de 2019 - Maltais, Danielle; Bourdeau-Brien, Michaël; Gilbert, Simon; Normandin, Julie-Maude; Tchassem Pinlap, Jonas; Généreux, Mélissa; Landaverde, Elsa; Boudreault, Mathieu (2023)
Les inondations de 2017 et 2019 au Québec ont affecté respectivement 293 et 240 municipalités. Ces inondations ont généré une cascade d’évènements stressants (stresseurs primaires et secondaires) qui ont eu des effets sur la santé mentale de la population et retardé le processus de rétablissement des individus. Cette période de rétablissement peut s’échelonner sur plusieurs mois voire plusieurs années. Cette étude s’inscrit dans la spécificité de la recherche mixte mise de l’avant à travers trois stratégies de recherche, réalisées de façon séquentielle : 1) sondage populationnelle réalisé auprès de 680 personnes, 2) analyse de documents produits par les organisations participant au processus de rétablissement social des sinistrés, ou sur des analyses externes portant sur ces interventions de rétablissement et 3) entrevues semi-dirigées auprès de 15 propriétaires occupants ayant complété une demande d’indemnisation à la suite des inondations de 2019 et auprès de 11 professionnels et gestionnaires participant au processus de rétablissement social. Les entrevues semi-dirigées et les questionnaires complétés par les personnes sinistrées lors des inondations de 2019 démontrent que les principales sources de stress ayant des impacts sur la santé et le bien-être des répondants sont : 1) l’absence d’avertissement et la vitesse de la montée des eaux; 2) l’obligation de se relocaliser et la peur d’être victime de pillage; 3) le manque de solidarité et d’empathie de la part de certains employés du MSP; 4) la gestion des conflits familiaux; 5) la gestion de problèmes de santé nouveaux ou préexistants; 6) la complexité des demandes d’indemnisation; 7) la lourdeur et les délais des travaux de nettoyage ou de restauration; 8) les indemnités inférieures aux coûts engendrés par l’inondation; 9) les pertes matérielles subies, particulièrement ceux d’une valeur de plus de 50 000 $; et 10) la diminution anticipée de la valeur de sa résidence. À cela s’ajoute l’insatisfaction à l’égard du programme d’indemnisation du gouvernement du Québec (PGIAF) qui fait plus que doubler la prévalence des symptômes de stress post-traumatique. Les inondations entraînent également une perte de satisfaction ou de bien-être statistiquement significative. La valeur monétaire de cette perte de jouissance peut être exprimée en équivalent salaires. En moyenne, cette diminution du bien-être équivaut à une baisse de salaire de 60 000$ pour les individus ayant vécu une première inondation et à 100 000$ pour les individus ayant vécu de multiples inondations. Ces résultats suggèrent que les coûts indirects et intangibles représentent une part importante des dommages découlant des inondations. Ce projet de recherche vise également à analyser l’application du PGIAF et son influence sur les stresseurs vécus par les sinistrés dans le contexte de la pandémie de COVID-19. La principale recommandation de cette étude repose sur une analyse de documents, un sondage populationnel et des entrevues semi-dirigées. Ainsi, s’attaquer à la réduction de principaux stresseurs nécessite 1) d’améliorer la gouvernance du risque d’inondation, 2) d’intensifier la communication et le support aux sinistrés, et 3) de revoir les mécanismes d’indemnisation existants.

Combining quadrat, rake, and echosounding to estimate submerged aquatic vegetation biomass at the ecosystem scale - Botrel, Morgan; Hudon, Christiane; Biron, Pascale M.; Maranger, Roxane (Limnology and Oceanography: Methods, 2023)
Abstract Measuring freshwater submerged aquatic vegetation (SAV) biomass at large spatial scales is challenging, and no single technique can cost effectively accomplish this while maintaining accuracy. We propose to combine and intercalibrate accurate quadrat‐scuba diver technique, fast rake sampling, and large‐scale echosounding. We found that the overall relationship between quadrat and rake biomass is moderately strong (pseudo R 2 = 0.61) and varies with substrate type and SAV growth form. Rake biomass was also successfully estimated from biovolume (pseudo R 2 = 0.57), a biomass proxy derived from echosounding. In addition, the relationship was affected, in decreasing relevance, by SAV growth form, flow velocity, acoustic data quality, depth, and wind conditions. Sequential application of calibrations yielded predictions in agreement with quadrat observations, but echosounding predictions underestimated biomass in shallow areas (< 1 m) while outperforming point estimation in deep areas (> 3 m). Whole‐system quadrat‐equivalent biomass from echosounding differed by a factor of two from point survey estimates, suggesting echosounding is more accurate at larger scales owing to the increased sample size and better representation of spatial heterogeneity. To decide when an individual or a combination of techniques is profitable, we developed a step‐by‐step guideline. Given the risks of quadrat‐scuba diver technique, we recommend developing a one‐time quadrat–rake calibration, followed by the use of rake and echosounding when sampling at larger spatial and temporal scales. In this case, rake sampling becomes a valid ground truthing method for echosounding, also providing valuable species information and estimates in shallow waters where echosounding is inappropriate.

Trajectoires et visées de l'hydrogéomorphologie au Québec - Buffin‐Bélanger, Thomas; Lachapelle, Félix; Biron, Pascale; Boivin, Maxime (Canadian Geographies / Géographies canadiennes, 2024)
Résumé L'hydrogéomorphologie étudie la dynamique des rivières en se concentrant sur les interactions liant la structure des écoulements, la mobilisation et le transport des sédiments et les morphologies qui caractérisent les cours d'eau et leur bassin‐versant. Elle offre un cadre d'analyse et des outils pour une meilleure intégration des connaissances sur la dynamique des rivières pour la gestion des cours d'eau au sens large, et plus spécifiquement, pour leur restauration, leur aménagement et pour l'évaluation et la prévention des risques liés aux aléas fluviaux. Au Québec, l'hydrogéomorphologie émerge comme contribution significative dans les approches de gestion et d'évaluation du risque et se trouve au cœur d'un changement de paradigme dans la gestion des cours d'eau par lequel la restauration des processus vise à augmenter la résilience des systèmes et des sociétés et à améliorer la qualité des environnements fluviaux. Cette contribution expose la trajectoire de l'hydrogéomorphologie au Québec à partir des publications scientifiques de géographes du Québec et discute des visées de la discipline en recherche et en intégration des connaissances pour la gestion des cours d'eau . , Abstract Hydrogeomorphology studies river dynamics, focusing on the interactions between flow structure, sediment transport, and the morphologies that characterize rivers and their watersheds. It provides an analytical framework and tools for better integrating knowledge of river dynamics into river management in the broadest sense, and more specifically, into river restoration as well as into the assessment and prevention of risks associated with fluvial hazards. In Quebec, hydrogeomorphology is emerging as a significant contribution to risk assessment and management approaches, and is at the heart of a paradigm shift in river management whereby process restoration aims to increase the resilience of fluvial systems and societies, and improve the quality of fluvial environments. This contribution outlines the trajectory of hydrogeomorphology in Quebec, based on scientific publications by Quebec geographers, and discusses the discipline's aims in research and knowledge integration for river management . , Messages clés Les géographes du Québec ont contribué fortement au développement des connaissances et outils de l'hydrogéomorphologie. L'hydrogéomorphologie a évolué d'une science fondamentale à une science où les connaissances fondamentales sont au service de la gestion des cours d'eau. L'hydrogéomorphologie et le cortège de connaissances et d'outils qu'elle promeut font de cette discipline une partenaire clé pour une gestion holistique des cours d'eau.

Flood Risk Management via Risk Communication, Cognitive Appraisal, Collective Efficacy, and Community Action - Lin, Carolyn A. (Sustainability, 2023)
Climate change and more frequent severe storms have caused persistent flooding, storm surges, and erosion in the northeastern coastal region of the United States. These weather-related disasters have continued to generate negative environmental consequences across many communities. This study examined how coastal residents’ exposure to flood risk information and information seeking behavior were related to their threat appraisal, threat-coping efficacy, and participation in community action in the context of building social resilience. A random sample of residents of a coastal community in the Northeastern United States was selected to participate in an online survey (N = 302). Key study results suggested that while offline news exposure was weakly related to flood vulnerability perception, online news exposure and mobile app use were both weakly associated with flood-risk information seeking. As flood vulnerability perception was strongly connected to flood severity perception but weakly linked to lower self-efficacy beliefs, flood severity perception was weakly and moderately associated with response-efficacy beliefs and information seeking, respectively. Furthermore, self-efficacy beliefs, response efficacy beliefs, and flood-risk information seeking were each a weak or moderate predictor of collective efficacy beliefs. Lastly, flood risk information-seeking was a strong predictor and collective efficacy beliefs were a weak predictor of community action for flood-risk management. This study tested a conceptual model that integrated the constructs from risk communication, information seeking, and protection motivation theory. Based on the modeling results reflecting a set of first-time findings, theoretical and practical implications are discussed.

The role of public relations in building community resilience to natural disasters: perspectives from Sri Lanka and New Zealand - Dharmasena, M. K. Gayadini Imesha; Toledano, Margalit; Weaver, C. Kay (Journal of Communication Management, 2020)
The paper identifies a role for public relations in disaster management by analysing disaster and communication managers' understanding of community resilience and their use of communication in the context of two different cultural environments.,The research study comprised 51 in-depth qualitative interviews with disaster managers in Sri Lanka and New Zealand, which were thematically analysed using the software programme NVivo 10.,The study identified cultural differences in Sri Lanka and New Zealand that impact on how managers' communicate in natural disaster situations. The findings indicated that public relations’ understanding of communities’ cultures, their communication, networking and lobbying skills could further enhance the effectiveness of efforts to build community resilience to disasters.,Nations are complex multicultural realities; the findings cannot be generalized to make claims about how natural disasters are managed in different national contexts.,The paper identifies the unrealized potential of public relations’ expertise in communication, community relations, networking and lobbying to contribute to building community resilience to natural disasters.,By supporting efforts to build community resilience to disasters, public relations practitioners can contribute to social well-being in times of catastrophic natural disasters.,The paper adds an innovative perspective to public relations crisis literature by identifying the potential contribution of public relations’ concepts and practices to build community resilience to natural disasters. It demonstrates how sociocultural differences may affect disaster communication strategies.

Seasonal Variation of the Physico-chemical Composition of Ottawa River Waters in the St. Lawrence River - Frenette, Jean-Jacques; Assani, Ali A. (2018)
The goal of this study is to compare the seasonal variability of 12 physicochemical characteristics of waters in the Ottawa and St. Lawrence Rivers (SLR). Water samples were collected on board the research vessel Lampsillis in the spring (May), summer (August), and fall (October) of 2006 at four stations located downstream from the confluence of the two rivers. Temperature and total nitrogen values varied significantly for the three seasons. In contrast, seasonal values of light extinction coefficient and turbidity do not show any significant variation. The values of the other characteristics varied significantly only for one season. Comparison of these data with those measured in 1994–1996 reveals a net warming of the waters and a significant increase in nitrite-nitrate concentrations due to the increasing use of nitrogen-bearing fertilizers by farmers in Quebec. Concentrations of these two substances are higher than the limits set by the government of Quebec for water quality in rivers.

Disaster risk reduction and the limits of truisms: Improving the knowledge and practice interface - Nohrstedt, Daniel; Parker, Charles F.; von Uexkull, Nina; Mård, Johanna; Nyberg, Lars; Petrova, Kristina; Albrecht, Frederike; Göteman, Malin; Hileman, Jacob; Messori, Gabriele; Di Baldassarre, Giuliano (International journal of disaster risk reduction, 2021)
Abstract Action toward strengthened disaster risk reduction (DRR) ideally builds from evidence-based policymaking to inform decisions and priorities. This is a guiding principle for the Sendai Framework for Disaster Risk Reduction (SFDRR), which outlines priorities for action to reduce disaster risk. However, some of these practical guidelines conceal oversimplified or unsubstantiated claims and assumptions, what we refer to as “truisms”, which, if not properly addressed, may jeopardize the long-term goal to reduce disaster risks. Thus far, much DRR research has focused on ways to bridge the gap between science and practice while devoting less attention to the premises that shape the understanding of DRR issues. In this article, written in the spirit of a perspective piece on the state of the DRR field, we utilize the SFDRR as an illustrative case to identify and interrogate ten selected truisms, from across the social and natural sciences, that have been prevalent in shaping DRR research and practice. The ten truisms concern forecasting, loss, conflict, migration, the local level, collaboration, social capital, prevention, policy change, and risk awareness. We discuss central claims associated with each truism, relate those claims to insights in recent DRR scholarship, and end with suggestions for developing the field through advances in conceptualization, measurement, and causal inference.

Multi-method Modeling Framework for Support of Integrated Water Resources Management - Nikolic, Vladimir V.; Simonovic, Slobodan P. (Environmental Processes, 2015)
The contemporary definition of integrated water resources management (IWRM) is introduced to promote a holistic approach in water engineering practices. IWRM deals with planning, design and operation of complex systems in order to control the quantity, quality, temporal and spatial distribution of water with the main objective of meeting human and ecological needs and providing protection from water related disasters. This paper examines the existing decision making support in IWRM practice, analyses the advantages and limitations of existing tools, and, as a result, suggests a generic multi-method modeling framework that has the main goal to capture all structural complexities of, and interactions within, a water resources system. Since the traditional tools do not provide sufficient support, this framework uses multi-method simulation technique to examine the codependence between water resources system and socioeconomic environment. Designed framework consists of (i) a spatial database, (ii) a traditional process-based model to represent the physical environment and changing conditions, and (iii) an agent-based spatially explicit model of socio-economic environment. The multi-agent model provides for building virtual complex systems composed of autonomous entities, which operate on local knowledge, possess limited abilities, affect and are affected by local environment, and thus, enact the desired global system behavior. Agent-based model is used in the presented work to analyze spatial dynamics of complex physical-social-economic-biologic systems. Based on the architecture of the generic multi-method modeling framework, an operational model for the Upper Thames River basin, Southwestern Ontario, Canada, is developed in cooperation with the local conservation authority. Six different experiments are designed by combining three climate and two socio-economic scenarios to analyze spatial dynamics of a complex physical-social-economic system of the Upper Thames River basin. Obtained results show strong dependence between changes in hydrologic regime, in this case surface runoff and groundwater recharge rates, and regional socio-economic activities.

Mapping SWE in near real time across a large territory using a particle filter - Odry, Jean; Boucher, Marie-Amélie; Lachance Cloutier, Simon; Turcotte, Richard; Saint-Louis, Pierre-Yves (2020)
In snow-prone regions, snowmelt is one of the main drivers of runoff. For operational flood forecasting and mitigation, the spatial distribution of snow water equivalent (SWE) in near real time is necessary. In this context, in situ observations of SWE provide a valuable information. Nonetheless, the high spatial variability of snowpack characteristics makes it necessary to implement some kind of snow modelling to get a spatially continuous estimation. Data assimilation is thus a useful approach to combine information from both observation and modeling in near real-time. For example, at the provincial government of Quebec (eastern Canada), the HYDROTEL Snowpack Model is applied on a daily basis over a 0.1 degree resolution mesh covering the whole province. The modelled SWE is corrected in real time by in situ manual snow survey which are assimilated using a spatial particles filter (Cantet et al., 2019). This assimilation method improves the reliability of SWE estimation at ungauged sites. The availability of manual snow surveys is however limited both in space and time. These measurements are conducted on a bi-weekly basis in a limited number of sites. In order to further improve the temporal and spatial observation coverage, alternative sources of data should be considered. In this research, it is hypothesized that data gathered by SR50 sonic sensors can be assimilated in the spatial particle filter to improve the SWE estimation. These automatic sensors provide hourly measurements of snow depth and have been deployed in Quebec since 2005. Beforehand, probabilistic SWE estimations were derived from the SR50 snow depth measurements using an ensemble of artificial neural networks (Odry et al. 2019). Considering the nature of the data and the conversion process, the uncertainty associated with this dataset is supposed larger than for the manual snow surveys. The objective of the research is to evaluate the potential interest of adding this lower-quality information in the assimilation framework. The addition of frequent but uncertain data in the spatial particle filter required some adjustments in term of assimilation frequency and particle resampling. A reordering of the particles was implemented to maintain the spatial coherence between the different particles. With these changes, the consideration of both manual snow surveys and SR50 data in the spatial particle filter reached performances that are comparable to the initial particle filter that combines only the model and manual snow survey for estimating SWE in ungauged sites. However, the addition of SR50 data in the particle filter allows for continuous information in time, between manual snow surveys. References: Cantet, P., Boucher, M.-A., Lachance-Coutier, S., Turcotte, R., Fortin, V. (2019). Using a particle filter to estimate the spatial distribution of the snowpack water equivalent. J. Hydrometeorol, 20. Odry, J., Boucher, M.-A., Cantet,P., Lachance-Cloutier, S., Turcotte, R., St-Louis, P.-Y. (2019). Using artificial neural networks to estimate snow water equivalent from snow depth. Canadian water ressources journal (under review)

An Entropy-Based Approach to Fuzzy Multi-objective Optimization of Reservoir Water Quality Monitoring Networks Considering Uncertainties - Pourshahabi, Shokoufeh; Nikoo, Mohammad Reza; Raei, Ehsan; Adamowski, Jan Franklin (Water Resources Management, 2018)

A comparative study of fuzzy logic-based models for groundwater quality evaluation based on irrigation indices - Vadiati, Meysam; Nalley, Deasy; Adamowski, Jan; Nakhaei, Mohammad; Asghari-Moghaddam, Asghar (Journal of Water and Land Development, 2019)
Abstract Groundwater quality modelling plays an important role in water resources management decision making processes. Accordingly, models must be developed to account for the uncertainty inherent in the modelling process, from the sample measurement stage through to the data interpretation stages. Artificial intelligence models, particularly fuzzy inference systems (FIS), have been shown to be effective in groundwater quality evaluation for complex aquifers. In the current study, fuzzy set theory is applied to groundwater-quality related decision-making in an agricultural production context; the Mamdani, Sugeno, and Larsen fuzzy logic-based models (MFL, SFL, and LFL, respectively) are used to develop a series of new, generalized, rule-based fuzzy models for water quality evaluation using widely accepted irrigation indices and hydrological data from the Sarab Plain, Iran. Rather than drawing upon physiochemical groundwater quality parameters, the present research employs widely accepted agricultural indices (e.g., irrigation criteria) when developing the MFL, SFL and LFL groundwater quality models. These newly-developed models, generated significantly more consistent results than the United States Soil Laboratory (USSL) diagram, addressed the inherent uncertainty in threshold data, and were effective in assessing groundwater quality for agricultural uses. The SFL model is recommended as it outperforms both MFL and LFL in terms of accuracy when assessing groundwater quality using irrigation indices.

A Canadian River Ice Database from National Hydrometric Program Archives - De Rham, Laurent; Dibike, Yonas; Beltaos, Spyros; Peters, Daniel; Bonsal, Barrie; Prowse, Terry (Hydrology and Soil Science – Hydrology, 2020)
Abstract. River ice is a common occurrence in cold climate hydrological systems. The annual cycle of river ice formation, growth, decay and clearance can include low flows and ice jams, as well as mid-winter and spring break-up events. Reports and associated data on river ice occurrence are often limited to site and season-specific studies. Within Canada, the National Hydrometric Program (NHP) operates a network of gauging stations with water level as the primary measured variable to derive discharge. In the late 1990s, the Water Science and Technology Directorate of Environment and Climate Change Canada initiated a long-term effort to compile, archive and extract river ice related information from NHP hydrometric records. This data article describes the original research data set produced by this near 20-year effort: the Canadian River Ice Database (CRID). The CRID holds almost 73,000 variables from a network of 196 NHP stations throughout Canada that were in operation within the period 1894 to 2015. Over 100,000 paper and digital files were reviewed representing 10,378 station-years of active operation. The task of compiling this database involved manual extraction and input of more than 460,000 data entries on water level, discharge, date, time and data quality rating. Guidelines on the data extraction, rating procedure and challenges are provided. At each location, a time series of up to 15 variables specific to the occurrence of freeze-up and winter-low events, mid-winter break-up, ice thickness, spring break-up and maximum open-water level were compiled. This database follows up on several earlier efforts to compile information on river ice, which are summarized herein, and expands the scope and detail for use in Canadian river ice research and applications. Following the Government of Canada Open Data initiative, this original river ice data set is available at: https://doi.org/10.18164/c21e1852-ba8e-44af-bc13-48eeedfcf2f4 (de Rham et al., 2020).

Entre héritage réglementaire et imaginaire du risque: gestion des zones inondables et pratiques d'adaptation au Québec et à Lachute - Gaudette, Marilyne; Germain, Daniel (Zenodo, 2025)
Floods, intensified by climate change, pose major challenges for flood zone management in Quebec. This report addresses these issues through two complementary aspects: a historical analysis of the evolution of flood zone management in Quebec and the projected impact of the cartographic and regulatory overhaul, as well as an exploration of the imaginary surrounding the flood-prone territory of the city of Lachute, which has faced recurrent floods for decades and yet continues to be inhabited. The historical analysis reveals that the major floods of 1974, 1976, 2017, and 2019 marked significant turning points in Quebec’s risk management, particularly by highlighting gaps in the regulatory framework and flood zone mapping. The adoption of the Act Respecting Land Use Planning and Development (LAU) in 1979 and the Policy for the Protection of Shorelines, Littorals, and Floodplains (PPRLPI) in 1987 represented a shift toward a preventive approach. However, inconsistencies, insufficient updates to maps, and uneven enforcement of standards have hindered their effectiveness. The catastrophic floods of 2017 and 2019 triggered a regulatory overhaul, a modernization of mapping, and measures to strengthen community resilience. In 2022, a transitional regime came into effect to tighten the regulation of activities in flood zones, pending the adoption of a risk-based management framework. However, to this day, the regulatory perimeters proposed in the modernization project fail to account for the adaptive capacities deployed by communities to live with water, thus providing a biased interpretation of flood risk. The second part explores the social and cultural representations associated with Lachute’s flood-prone territory. It highlights the complex relationships that have developed between residents and the Rivière du Nord through successive flooding episodes and the adaptation strategies implemented to cope, particularly by those who have repeatedly experienced flooding. These residents have come to live with overflow events and to (co)exist with water, challenging the persistent notion that flood-prone areas are inherently dangerous. While local strategies are sometimes innovative, they remain constrained by a regulatory framework that disregards the human experience of the territory and the specific ways in which people inhabit exposed areas to learn to manage flood risks. In summary, this report underscores the urgency of a territorialized, risk-based approach to modernizing flood zone management. It also highlights the need to look beyond cartographic boundaries and better integrate human and cultural dimensions into planning policies, as illustrated in the case of Lachute, to more accurately reflect the true level of risk. These reflections aim to promote more coherent, sustainable, and acceptable management, planning, and development of exposed territories in response to the growing challenges posed by climate change.
Keywords: Infolettre; Infolettre_Mai_2025

Strategies for integrating water management and spatial planning: Organising for spatial quality in the Dutch “Room for the River” program - Busscher, T.; Van Den Brink, M.; Verweij, S. (Journal of Flood Risk Management, 2019)
In response to extreme flood events and an increasing awareness that traditional flood control measures alone are inadequate to deal with growing flood risks, spatial flood risk management strategies have been introduced. These strategies do not only aim to reduce the probability and consequences of floods, they also aim to improve local and regional spatial qualities. To date, however, research has been largely ignorant as to how spatial quality, as part of spatial flood risk management strategies, can be successfully achieved in practice. Therefore, this research aims to illuminate how spatial quality is achieved in planning practice. This is done by evaluating the configurations of policy instruments that have been applied in the Dutch Room for the River policy program to successfully achieve spatial quality. This policy program is well known for its dual objective of accommodating higher flood levels as well as improving the spatial quality of the riverine areas. Based on a qualitative comparative analysis, we identified three successful configurations of policy instruments. These constitute three distinct management strategies: the “program‐as‐guardian”, the “project‐as‐driver,” and “going all‐in” strategies. These strategies provide important leads in furthering the development and implementation of spatial flood risk management, both in the Netherlands and abroad.
Keywords: Ouvrage_Collectif_Numéro1

Effects of Timber Harvesting and Related Management Practices on Water Quality in Forested Watersheds - Sopper, William E. (Journal of Environmental Quality, 1975)
Abstract Undisturbed forested watersheds are generally recognized as a primary source of high‐quality water. The physical and chemical nature of these waters fluctuate constantly in response to natural stresses but are most influenced by man's activities. Three major forest land management activities—timber harvesting, fertilization, and herbiciding—which may have an adverse affect on water quality are reviewed. In general, research results indicate that nutrient losses, particularly nitrogen, following forest clearcutting are small to negligible. Similarly, forest fertilization studies indicate that nitrogen concentrations in streams are not drastically increased. Large areal applications of selected herbicides in the West have demonstrated that, if carefully applied, they can be used without impairment of water quality.
Keywords: Ouvrage_Collectif_Numéro1

Estimation du débit en rivière à l’aide de l’imagerie RADARSAT en utilisant l’apprentissage profond. - Ziadi, Samar (Maîtrise en sciences de l'eau, 2023)
L’estimation du débit en rivières est un paramètre clé pour la gestion des ressources hydriques, la prévention des risques liés aux inondations et la planification des équipements hydroélectriques. Lorsque le débit d’eau est très élevé lors d'évènements extrêmes, les méthodes de jaugeage traditionnelles ne peuvent pas être utilisées. De plus, les stations du réseau hydrométrique sont généralement éparses et leur répartition spatiale n’est pas optimale. Par conséquent, de nombreuses sections de rivières ne peuvent être suivies par des mesures et observations du débit. Pour ces raisons, pendant la dernière décennie, les capteurs satellitaires ont été considérés comme une source d’observation complémentaire aux observations traditionnelles du niveau d’eau et du débit en rivières. L’utilisation d’une telle approche a fourni un moyen de maintenir et d’étendre le réseau d'observation hydrométrique. L’approche avec télédétection permet d’estimer le débit à partir des courbes de tarage qui met en relation le débit instantané (Q) et la géométrie d’une section transversale du chenal (la largeur ou la profondeur effective de la surface d’eau). En revanche, cette méthode est associée à des limitations, notamment, sa dépendance aux courbes de tarage. En effet, en raison de leurs natures empiriques, les courbes de tarage sont limitées à des sections spécifiques et ne peuvent être appliquées dans d’autres rivières. Récemment, des techniques d’apprentissage profond ont été appliquées avec succès dans de nombreux domaines, y compris en hydrologie. Dans le présent travail, l’approche d’apprentissage profond a été choisie, en particulier les réseaux de neurones convolutifs (CNN), pour estimer le débit en rivière. L’objectif principal de ce travail est de développer une approche d’estimation du débit en rivières à partir de l’imagerie RADARSAT 1&2 à l’aide de l’apprentissage profond. La zone d’étude se trouve dans l’ecozone du bouclier boréal à l’Est du Canada. Au total, 39 sites hydrographiques ont fait l’objet de cette étude. Dans le présent travail, une nouvelle architecture de CNN a été a été proposée, elle s'adapte aux données utilisées et permet d’estimer le débit en rivière instantané. Ce modèle donne un résultat du coefficient de détermination (R²) et de Nash-Sutcliffe égale à 0.91, le résultat d’erreur quadratique moyenne égale à 33 m³ /s. Cela démontre que le modèle CNN donne une solution appropriée aux problèmes d’estimation du débit avec des capteurs satellites sans intervention humaine. Estimating river flow is a key parameter for effective water resources management, flood risk prevention and hydroelectric facilities planning. In cases of very high flow of water or extreme events, traditional gauging methods cannot be reliable. In addition, hydrometric network stations are often sparse and their spatial distribution is not optimal. Therefore, many river sections cannot be monitored using traditional flow measurements and observations. For these reasons, satellite sensors are considered as a complementary observation source to traditional water level and flow observations in the last decades. The use of this kind of approach has provided a way to maintain and expand the hydrometric observation network. Remote sensing data can be used to estimate flow from rating curves that relate the instantaneous flow (Q) to the geometry of a channel cross-section (the effective width or depth of the water surface). On the other hand, remote sensing is also associated with limitations, notably its dependence on the rating curves. Indeed, due to their empirical nature, rating curves are limited to specific sections and cannot be applied in other rivers. Recently, deep learning techniques have been successfully applied in many fields, including hydrology. In the present work, the deep learning approach has been chosen, in particular convolutional neural networks (CNN), to estimate river flow. The main objective of this work is to develop an approach to estimate river flow from RADARSAT 1&2 imagery using deep learning. In this study, 39 hydrographic sites of the Boreal Shield ecozone in Eastern Canada were considered. A new CNN architecture was developed to provide a straightforward estimation of the instantaneous river flow rate. The achieved results demonstrated a coefficient of determination (R²) and Nash-Sutcliffe values of 0.91, and a root mean square error of 33m³ /s. This indicates the effectiveness of CNN in automatic flow estimation with satellite sensors.

Improving hydrological forecasting at multiple lead-times for hydropower reservoir management - Sabzipour, Behmard (École de technologie supérieure, 2023)
Streamflow forecasting is important for managing water resources in sectors like agriculture, hydropower, drought management, and urban flood prevention planning. Our study examines short and long lead-times to create a framework for streamflow forecasting that can benefit water resource management and related sectors. To improve streamflow forecasts for up to ten days of lead-time, the study first focuses on improving initial conditions using an ensemble Kalman filter as a data assimilation method. The goal is to regulate the hyperparameters of the ensemble Kalman filter for each season to produce more accurate forecasts. A sensitivity analysis is conducted to identify the best hyperparameter sets for each season, including uncertainty in temperature, precipitation, observed streamflow, and the water content of three state variables - vadose zone, saturated zone, and snowpack - from the CEQUEAU model. Results indicate that improving initial conditions with the ensemble Kalman filter produces more skillful forecasts until a 6-day leadtime. Temperature uncertainty is particularly sensitive and varies across seasons. The vadose zone state variable was identified as the most important and sensitive state variable, and updating all state variables systematically may not be necessary for improving forecast skill. Recent machine learning advances are improving short-term streamflow forecasting. One such method is the Long Short-Term Memory (LSTM) model. In general, neural networks learn from regression as relationships exist between input-output. However, LSTM models have a feature named ‘forget gate’, which enables them to learn the relationship between inputs (e.g., temperature and precipitation) and output (streamflow), and also to capture temporal dependencies in the data. The study aimed to compare the performance of the Long ShortTerm Memory (LSTM) model with data assimilation-based and process-based hydrological models in short-term streamflow forecasting. All three models were tested using the same ensemble weather forecasts. The LSTM model demonstrated good performance in forecasting streamflow, with a Kling-Gupta efficiency (KGE) greater than 0.88 for 9 lead-times. The LSTM model did not incorporate data assimilation, but it benefited from observed streamflow until the last day before the forecast. This is because the LSTM model learned and incorporated knowledge from the previous days while issuing forecasts, similar to how data assimilation updates initial conditions. The study results also showed that the LSTM model had better performance up to day 6 of lead-time compared to the data assimilation-based models. However, training the LSTM model separately for each lead-time is a time-consuming process and is a disadvantage compared to the data assimilation-based methods. Nonetheless, the study demonstrated the potential of machine learning techniques in improving streamflow forecasting. The forecasting of streamflow for long lead-times such as a month usually involves the use of historical meteorological data to create probable future scenarios, as meteorological forecasts become unreliable beyond this lead-time. In this study, we proposed a novel method for streamflow forecasting based on ensemble streamflow forecasting (ESP) filtering, using a Genetic Algorithm (GA) to filter forecast scenarios. This method quantifies the potential of historical data for each basin. This potential could be utilized to enhance the accuracy of streamflow forecasts. We sorted the selected and unselected scenarios to find out the common features between them, but the results did not help distinguish between the two groups. Nonetheless, the GA method can be used as a benchmark for future studies to improve longterm streamflow forecasting. This method can also be used to compare different forecast methods based on the potential shown by the GA method for a specific size of ESP members. For instance, if a method uses large-scale climate signals to filter ESP members, the forecast skill result could be compared with the potential of historical data for that particular size of ESP members.

Livelihood vulnerability to climatic stresses: A study of the northeastern floodplain communities of Bangladesh - Rahman, H.M. (2018)
Climatic stress vulnerability has cross-scaler influences on development interventions, particularly in developing countries. While most of climate adaptation plans and interventions are developed at national or international scales, relatively little attention has been paid to incorporate the contextual properties of climate vulnerability in adaptation-related decision making. Focusing on the wetland ecosystem dominated northeastern floodplain communities of Bangladesh, this exploratory research seeks to better understand how locally-specific socio-economic and biophysical properties serve to compound vulnerability to climatic stresses; how community members use their resources and assets in order to reduce their sensitivity to climatic stresses; and the extent to which government adaptation programmes reflect context-specific adaptation demands. Recognizing that Bangladesh is widely acknowledged to be one of the most climate-vulnerable countries in the world, this dissertation begins with a systematic literature review of the state of knowledge related to climate change impacts in Bangladesh. Results indicate a shortage of context specific scientific studies and identify that northeastern floodplain region is the most understudied area in the country. Issues related to multidisciplinary research approaches and geographic connectedness of research efforts point to potential limitations in the evidence base used to support public policy initiatives on climate change adaptation. A participatory climate stress exposure assessment reveals that local biophysical changes and resource use behaviors significantly contribute to compounding the impacts of climatic stresses. However, these observations are generally poorly represented in local-level climate model-based stress assessments. Results reveal that community stress perceptions are largely determined by the temporal occurrence of a climatic event, with a climatic event considered a stress if it occurs in their production period and causes losses to their productivity. Stress perceptions are also influenced by household resource ownership, local innovation and technological uses. Using the sustainable rural livelihood approach, a mixed method study is then used to better understand the actions taken by households to reduce their livelihood sensitivity to climatic stresses. Households were found to organize, transform and combine their capital assets for generating different livelihood portfolios. Using diverse combinations of assets, two strategies were observed: 1) extending external networks in order to create non-natural resource dependent livelihood opportunities; and 2) extending uses of available natural resources. Both of these strategies required external supports from government programmes or market mechanisms. Finally, a climate change policy analysis of Bangladesh, supported with key informant interviews, is presented to assess how different government policy interventions have supported local adaptation initiatives. The results reveal that despite recent advancements in climate change related policy making and institutional changes for supporting local adaptation actions in Bangladesh, plans and policies often fail to respond to local demands. More specifically, the existing climate change adaptation planning and policy processes tend to lack wider public participation and have inadequate coordination with natural resource management policies. This dissertation considers the diverse socio-economic and social-ecological contexts of climate vulnerability in rural Bangladesh. The results offer important research and policy insights to developing more a systematic understanding of climate vulnerability, and how local knowledge might be better integrated into national and international policy processes.

Conception d’un outil intégré de suivi du couvert de glace à l’aide de la télédétection pour la prévention du risque d’embâcles de glace. - Plante Lévesque, Valérie (Doctorat en sciences de l'eau, 2023)
Les instances responsables d’assurer la gestion des risques d’inondations reliés aux embâcles de glace sont toujours à la recherche d’outils visant à prévenir les risques et réduire les conséquences sur les populations et les infrastructures. Grâce à la modélisation de certains paramètres jouant un rôle dans la formation des embâcles de glace comme la prédisposition géomorphologique et les conditions hydrométéorologiques, la prévention de ceux-ci s’est grandement améliorée. Les modèles axés sur la force de mobilisation de la rivière et sa capacité à contraindre l’écoulement gagnerait en pertinence s’ils pouvaient inclure la résistance du couvert de glace. Les outils de télédétection sont une manière efficace de connaitre l’état du couvert de glace tant sur l’ensemble de la rivière qu'à différents endroits ciblés. Ceux-ci peuvent générer différents produits cartographiques utiles avant, pendant et après les événements. La présente thèse vise à intégrer le suivi du couvert de glace dans les méthodes de prévention des embâcles à l’aide d’outils provenant de la télédétection. Pour ce faire, quatre sous-objectifs ont été accomplis 1) créer une approche de suivi du couvert de glace à grande échelle en exploitant les données de télédétection optique, radar et acquises par drone, 2) développer une méthode de cartographie automatique du type de glace par estimation d’ensemble à partir d’imagerie radar, 3) concevoir un modèle de détection automatique des lieux à risque de débâcle en utilisant les connaissances de personnes expertes pour interpréter les cartes du type de glace et 4) intégrer les outils développés aux autres modèles conçus dans le cadre de DAVE (Dispositif d’alertes et de vigilance aux embâcles). Les contributions originales découlant de cette thèse touchent plusieurs aspects du suivi du couvert de glace. Elles incluent la démonstration de la pertinence des indicateurs de suivi de la glace par la télédétection, la conceptualisation d’une méthode de segmentation de la rivière en secteurs de production, transport et accumulation de la glace, l’élaboration d’un modèle de cartographie du type de glace par estimation d’ensemble plus performant et polyvalent que les classificateurs originaux, la construction d’une base de données de dégradation du couvert de glace à partir des connaissances de personnes expertes en cartographie de la glace et un modèle de classification de la dégradation du couvert de glace. Cette thèse se conclut par l’intégration conceptuelle à l’aide d’une analyse multicritères hiérarchique des différents outils développés au sein de DAVE. The authorities responsible for ice jam flood risk management are always looking for tools to prevent harm and reduce consequences on populations and infrastructure. Ice jam prevention has been greatly improved by modelling certain parameters—such as geomorphic predispositions and hydrometeorological conditions—that are central to ice jam formation. These models focusing on the strength of the river current and its ability to constrain the flow would gain in relevance if they could include ice cover strength. Remote sensing tools are an effective way of knowing the state of the ice cover over the whole river and at different target locations. These can be used to generate different map products to include in monitoring before, during and after hazard events. This dissertation therefore aims to integrate ice cover monitoring into ice jam prevention methods using remote sensing tools. To do so, three main sub-objectives were accomplished: 1) to create a large-scale ice cover monitoring approach using remote sensing data such as optical, radar and drone images, 2) to develop a method for automatic mapping of ice type by ensemble estimation from radar imagery, 3) to design an automatic detection model for breakup risk locations using ice type maps and expert judgment and 4) to integrate the tools developed with other models created within the Dispositif d’alertes et de vigilance des embâcles de glace (DAVE). The original contribution from this work covers multiple aspects of ice cover monitoring. This dissertation demonstrates the relevance of direct indicators of ice monitoring by remote sensing, conceptualizes a method for river segmentation into areas of ice production, transport and accumulation, develops an ensemble-based estimation ice type mapping model more efficient and versatile than the original algorithms, constructs an ice cover degradation database derived from the knowledge of ice mapping experts, and proposes a classification model of ice cover degradation. This dissertation concludes with the conceptual integration by analytic hierarchy process of the different tools developed within DAVE.

Essays on Water Infrastructure Investments and Infectious Diseases Management - Kouassi, Régis (2024)
En étant nécessaire à la vie humaine, l’eau est également nécessaire au fonctionnement des économies. Pour qu’elle soit utile à la société, l’eau doit être disponible en quantité et en qualité adéquates, caractéristiques qui ne sont pas toujours disponibles dans la nature. Ainsi, trop ou pas assez d’eau entraînerait des inondations ou des sécheresses, tandis qu’une eau contaminée pourrait être le vecteur de maladies contagieuses mortelles, chacun de ces fléaux entraînant des dommages économiques. Cette thèse est organisée en trois chapitres traitant de thématiques liées aux investissements dans les infrastructures d'eau et à la gestion des maladies infectieuses. Le premier chapitre étudie comment les améliorations apportées aux réseaux d’égouts atténuent les impacts économiques des inondations provoquées par la pluie. Pour estimer l’effet causal de ces investissements, ce chapitre utilise un resserrement inattendu du financement fédéral américain en faveur des réseaux d’égouts, à la suite de l’amendement de 1977 à la politique du Clean Water Act. L'analyse empirique combine un nouveau modèle statistique du risque d'inondation induit par la pluie avec des données horaires sur la quantité de pluie dans les comtés et les codes postaux américains de 1996 à 2019. Les résultats indiquent que des investissements plus importants dans les réseaux d'égouts ont conduit à des réductions substantielles des inondations locales. Les bénéfices de ces investissements sont supérieurs à leurs coûts, économisant près de 23 millions de dollars pour le comté moyen. Dans l’ensemble, ces résultats mettent en évidence à quel point la détérioration des infrastructures publiques peut exacerber les conséquences du changement climatique. Le deuxième chapitre étudie le rôle des épidémies locales de maladies infectieuses dans l'adoption de systèmes centralisés d'approvisionnement en eau dans les premières villes américaines au XIXe siècle. À l’aide d’un vaste corpus de données provenant d’archives de journaux de 1800 à 1896, je construis un nouvel indicateur capturant les épidémies de fièvre jaune, de choléra et de fièvre typhoïde au niveau des villes. Les résultats indiquent que (1) les épidémies locales de maladies infectieuses ont entraîné une augmentation du nombre systèmes d'approvisionnement en eau construits par les villes et ont joué un rôle crucial dans la décision de construire environ 12% des ouvrages d’adduction d’eau en activité en 1897 ; (2) La réponse des villes aux épidémies de typhoïde a été deux fois plus importante que celle qui a suivi les épidémies de fièvre jaune ou de choléra. (3) Les entreprises privées ont construit davantage de nouveaux réseaux d’adduction d’eau après les épidémies locales, tandis que les gouvernements locaux ont procédé à davantage d’améliorations et d’extensions des réseaux d’adduction d’eau publics existants ainsi qu’à des rachats de sociétés d’eau privées. Enfin, je discute du rôle potentiel de divers facteurs sociodémographiques. Le troisième chapitre étudie les coûts économiques associés à une stratégie utilisée pour gérer les épidémies locales lors de la récente pandémie de COVID-19. Dans ce travail en collaboration avec Jian Tang, nous quantifions les effets de la politique ‘zéro-COVID’ à l’aide d’un riche ensemble de données sur les confinements au niveau des comtés en Chine et d’images satellitaires nocturnes. Nous constatons que des confinements plus stricts induisent une forte baisse de la luminosité nocturne au cours de la même période, suivie d’une lente reprise, qui se produit au moins deux trimestres après l’instauration du confinement. En l’absence de contagions généralisées, un comté soumis à un confinement total subit en moyenne une perte de PIB de 6% par rapport aux comtés non confinés. L’effet négatif est particulièrement persistant dans les zones où la production est dominée par les services, par opposition aux zones où la production est dominée par l’activité manufacturière. L’on note par ailleurs la présence d’effets d’entraînement à proximité des comtés confinés, mais ces effets sont de courte durée.

Développement d'une nouvelle approche d'extraction du réseau de surface à partir d'un nuage de points LiDAR massif basée sur la théorie de Morse - Dahbi, Aymane (2023)
Aujourd'hui, la cartographie des réseaux hydrographiques est un sujet important pour la gestion et l'aménagement de l'espace forestier, la prévention contre les risques d'inondation, etc. Les données sources pour cartographier les cours d'eau sont des nuages de points obtenus par des lidars aéroportés. Cependant, les méthodes d'extraction des réseaux usuelles nécessitent des opérations de découpage, de rééchantillonnage et d'assemblage des résultats pour produire un réseau complet, altérant la qualité des résultats et limitant l'automatisation des traitements. Afin de limiter ces opérations, une nouvelle approche d'extraction est considérée. Cette approche propose de construire un réseau de crêtes et de talwegs à partir des points lidar, puis transforme ce réseau en réseau hydrographique. Notre recherche consiste à concevoir une méthode d'extraction robuste du réseau adaptée aux données massives. Ainsi, nous proposons d'abord une approche de calcul du réseau adaptée aux surfaces triangulées garantissant la cohérence topologique du réseau. Nous proposons ensuite une architecture s'appuyant sur des conteneurs pour paralléliser les calculs et ainsi traiter des données massives.

Gestion intégrée des catastrophes en Afrique Subsaharienne : rôle de l’assurance, pour un système de gestion performant et la résilience des populations au Bénin - Goundjo, Antoine (2018)
Les variabilités et changements climatiques et les incapacités pour faire face à leurs risques, à leurs effets et, plus précisément, à gérer les catastrophes hydrométéorologiques (inondation et sécheresse) qui les accompagnent, viennent en ajouter aux vulnérabilités et aux problèmes, qui sont déjà une préoccupation en Afrique Subsaharienne et au Bénin. Face à leurs manifestations de plus en plus récurrentes – la faiblesse des systèmes de financement local de la gestion des catastrophes et le déficit des systèmes de protection sociale, qui témoignent des limites des capacités de transfert des risques de catastrophe – cette étude a identifié la structure (gouvernance-ressources), comme le problème essentiel de la gestion des catastrophes au Bénin. Une étude synthétique, étude de cas multiples avec trois niveaux d’analyse imbriqués, dans une approche qualitative, a permis de mieux comprendre comment, dans un contexte de pauvreté, l’intégration de la micro assurance climatique, modifie la structure, le processus et le résultat de la gestion des catastrophes et assure la performance du système et la résilience des populations. Elle a documenté les différents aspects de la structure et des vulnérabilités des systèmes et des populations et a identifié l’absence d’intégration de la micro assurance climatique aux systèmes de gestion des catastrophes, comme un problème au coeur de la complexité des déterminants de la résilience, aussi confrontée à une autre complexité, celle de la diversité des interconnexions entre les différentes catégories de risques, qui place la santé au coeur de tous les risques. La nécessité d’une gestion holistique du risque global, ou d’une gestion tout risque, telle que retenue par le Cadre d’Action de Hyōgo et le Cadre d’Action de Sendai; et l’importance d’apporter une réponse en accord au contexte et à son profil de risques, qui prend l’option pour la "démocratisation" d’une micro assurance climatique, gouvernée sur la base de fondements idéologiques d’équité et d’efficience, cette recherche a préconisé – pour une gestion plus rationnelle, pertinente, efficace et efficiente des catastrophes – une intégration de trois systèmes : le système de la gestion des catastrophes; le système de protection sociale, y compris celui de la micro assurance climatique, et le système de la santé; tous reconnus outillés pour la gestion des risques. Elle a retenu, qu’une telle approche saurait aussi assurer une gestion efficace du changement qu’induirait l’intégration de la micro assurance climatique à la gestion des catastrophes; de ii même qu’une meilleure utilisation des outils et méthodes de sensibilisation, de prévention, de prévision et d’évaluation des risques et des dommages dont recèlent les pratiques en micro assurance climatique. Elle constate que la réussite de l’intégration de la MAC et son développement sont essentiellement plus déterminés par les acteurs et leurs intérêts, que par les ressources financières, même si elles sont aussi indispensables. Cette recherche préconise qu’à partir de choix de modèles et de modes d’intégration bien étudiés, son intégration ou sa prise en compte dans les différents programmes d’aide et de protection sociale mis en oeuvre au Bénin pourrait être, à travers les subventions de l’État, un moyen de mobilisation de fonds en faveur de son financement et de sa viabilité/durabilité. Ce financement pourra aussi s’appuyer sur les mécanismes traditionnels de financement de l’assurance, de la micro assurance, des changements climatiques et de la réduction des risques de catastrophe au Bénin, en Afrique et dans le monde. C’est pourquoi, en termes de gouvernance, ce travail soutien une restructuration avec une gestion entièrement centrée sur les communes, dans une approche des services de première ligne avec les réseaux de services ; en termes de ressources, il a aussi analysé les conditions et les possibilités de développement d’une micro assurance climatique, qui dépend avant tout de la qualité de la gestion des catastrophes (capacités à réduire les risques et limiter les pertes ou capacités à induire la résilience des systèmes et des populations). Cette approche puise dans les réalités et pratiques endogènes de gestion des catastrophes et surtout de protection sociale ou de transfert de risques ; elle s’inspire des bonnes pratiques d’ailleurs ; elle contribue à instaurer l’équité, comme principe de la gestion intégrée des catastrophes et, au-delà de la résilience, à susciter une convergence des efforts pour l’autonomisation de la structure et des populations, face aux manifestations catastrophiques des inondations et de la sécheresse. Cette recherche pense qu’il faut oser la micro assurance universelle pour la gestion des catastrophes hydrométéorologiques; qu’elle est réalisable ou faisable, même en contexte de pauvreté; et qu’il est aussi possible de combiner micro assurance climatique universelle et assurance médicale universelle, dans une dynamique qui mobilise des approches efficientes et les intérêts.

Étude des facteurs contrôlant la présence de l’algue Didymosphenia geminata et des impacts de sa présence sur le saumon atlantique juvénile. - Gillis, Carole-Anne (Université du Québec, Institut national de la recherche scientifique, 2018)
L’algue Didymosphenia geminata est une diatomée à potentiel envahissant. Cette algue microscopique, attachée au substrat, peut sécréter des quantités phénoménales de mucilage et créer de vaste amas fibreux tapissant le lit d’une rivière. Autrefois considérée très rare et représentative d’une qualité d’eau impeccable, elle est maintenant répertoriée omniprésente dans les rivières oligotrophes à travers le monde. Au cours des deux dernières décennies, son émergence a créé un intérêt marqué de la part des écologistes et gestionnaires de rivières puisque sa biologie et les facteurs régissant son occurrence et sa sévérité sont méconnus. Au Québec, c’est à l’été 2006 que les premières proliférations massives de l’algue didymo ont été observées dans la rivière Matapédia. Le manque de connaissances à son égard, plus précisément sur sa distribution, les causes de l’apparition des proliférations et de l’impact négatif possible de cet envahissement sur le réseau trophique mais surtout sur le cycle de vie du saumon atlantique en rivière a créé un état de panique chez les gestionnaires et les utilisateurs des rivières à saumon. Il existait dès lors un urgent besoin de combler ces lacunes. Afin de mieux comprendre les facteurs régissant tant la croissance cellulaire que la croissance des amas mucilagineux, un modèle conceptuel a été élaboré grâce à la collaboration de plusieurs chercheurs travaillant au Colorado, à l’île de Vancouver, en Nouvelle-Zélande et au Québec afin de colliger les observations et les données de terrain. Ce travail de synthèse a permis d’identifier les facteurs favorisant sa colonisation, sa croissance et sa persistance en rivière. La dynamique spatio-temporelle de l’algue didymo est dépendante de divers facteurs (ou conditions environnementales) dont les seuils critiques déterminent son comportement de prolifération. En rivière, la croissance d’algues benthiques est principalement déterminée par les variations saisonnières du débit, la température, la lumière et la chimie de l’eau. Ainsi, la connaissance des paramètres d’habitats favorables permet de déterminer si un bassin versant est favorable à la présence cellulaire de l’algue didymo et à la probabilité que celle-ci puisse y proliférer. Le modèle conceptuel permet d’établir la variabilité et la sévérité saisonnière du comportement envahissant de l’algue didymo en rivière. Afin d’appliquer le modèle conceptuel développé à l’échelle du bassin versant, nous avons mis sur pied un réseau de suivi volontaire des proliférations d’algue didymo dans le bassin versant de la rivière Restigouche. Vingt-deux organisations différentes totalisant 70 bénévoles ont été formés à identifier et quantifier les proliférations d’algue didymo. Entre 2010 et 2015, 1 228 observations ont été réalisées. L’analyse de cette base de données, nous a permis de déterminer que 71% de la variabilité de la sévérité des proliférations durant l’été est inversement proportionnelle à l’intensité de la crue printanière. À l’échelle du tronçon, l’analyse des proliférations pour différents types de faciès-substrat a permis de d’identifier une préférence accrue pour les seuils. Par la suite, afin d’appliquer le modèle conceptuel à l’échelle régionale, nous avons comparé la distribution de l’algue didymo dans trois régions de l’est du Québec (i.e. Gaspésie, Bas-St-Laurent et Côte-Nord) avec divers paramètres physico-chimiques de vingt-neuf rivières à saumon. Le principal facteur régissant la présence-absence de cellules est le pH. Les diatomées ont des optimums de pH très spécifiques et la géologie contrastante de la Côte-Nord (Bouclier canadien) par rapport aux basses terres du Saint-Laurent et les Appalaches en Gaspésie, a permis d’identifier que les eaux acides riches en tanins et lignines ne sont pas favorables à la survie et la croissance de l’algue didymo. Grâce à une meilleure connaissance des facteurs de contrôle de l’algue didymo à diverses échelles spatiales, nous pouvons déterminer les rivières à risque de proliférations massives. Au sein des rivières exhibant des proliférations, nous avons déterminé que les préférences d’habitat de l’algue didymo sont identiques à celles du saumon atlantique juvénile (i.e. eaux rapides, peu profondes, claires, froides, faible en nutriments avec un substrat grossier). Afin de déterminer l’ampleur de l’impact de la présence des proliférations sur le réseau trophique, nous avons vérifié son impact sur la communauté algale. La structure dense et fibreuse crée un environnement physique dans lequel plusieurs diatomées peuvent s’y loger. Nos résultats confirment que l’algue crée un habitat de choix pour les plus petites diatomées favorisant ainsi une plus grande diversité taxonomique. Malgré une augmentation de la complexité du biofilm suivant son épaississement, il n’y a pas d’impact supplémentaire sur la structure et la diversité taxonomique des échantillons. Puisque la structure de l’habitat est modifiée par les tapis et que ces derniers sont susceptibles d’altérer la structure et le fonctionnement de l’écosystème, nous avons évalué l’effet des proliférations sur le comportement alimentaire des saumons juvéniles. Grâce à l’observation en apnée du comportement, nous pouvons conclure que les saumons juvéniles effectuent une plus grande proportion de quêtes benthiques en fonction du pourcentage de recouvrement algal. Ce changement de comportement n’est pas attribuable à une diminution des proies disponibles au sein de la dérive. Notre étude confirme la grande plasticité comportementale des saumons juvéniles face aux modifications de l’habitat. Afin de vérifier l’impact des proliférations sur les ressources alimentaires et la diète des saumons juvéniles, nous avons utilisé l’approche par analyse d’isotopes stables. Cette approche permet d’établir un portrait intégré de l’utilisation des ressources par les poissons. Les signatures isotopiques divergentes entre les différents tissus des saumons confirment une modification de la diète saisonnière. Les saumons juvéniles en présence de l’algue didymo ont une diète moins diversifiée et appauvrie en carbone principalement composée de petits chironomides et de trichoptères. Malgré que l’indice de condition physique des saumons juvéniles soit similaire entre les deux sites, leur taille est plus petite dans le site avec proliférations. Les travaux futurs devront tenter de valider l’impact de la diminution de la qualité de la diète par les proliférations d’algue didymo sur le contenu en lipides des juvéniles. Suite aux diverses collaborations internationales et discussions avec les gestionnaires, nous nous sommes rendus à l’évidence qu’il devait y avoir une recommandation sur les mesures de gestion vis-à-vis cette espèce. En fonction des connaissances scientifiques développées au fil des ans et plusieurs cas de gestion dans divers pays, nous avons recommandé aux gestionnaires d’éduquer les utilisateurs à vérifier, nettoyer, sécher et congeler leurs équipements. Que l’algue didymo soit une espèce exotique ou indigène, elle peut être propagée. De plus, la mise en valeur des saines pratiques permettent de limiter la propagation d’autres organismes pouvant potentiellement être plus dévastateurs que l’algue didymo. Les résultats de cette thèse contribuent à l’avancement des connaissances sur les facteurs de contrôle de l’algue didymo tant à l’échelle microscopique que macroscopique. En plus d’avoir contribué à élaborer le modèle conceptuel, nous l’avons amélioré en l’appliquant à diverses échelles spatiales : à l’échelle du tronçon et du bassin versant ainsi qu’à l’échelle régionale. C’est d’ailleurs la première étude à élaborer un réseau de suivi des proliférations par l’implication des acteurs du milieu ainsi qu’une des seules études à avoir examiné la variabilité interannuelle sur une période de six ans. C’est également la première étude à avoir évalué l’impact de l’algue didymo sur les communautés périphytiques dans l’est du Canada. De surcroît, c’est la première étude exhaustive qui a évalué l’effet des proliférations sur l’écologie du saumon atlantique juvénile. Les recherches menées sur le comportement alimentaire est également novateur et contribue considérablement à la compréhension des mécanismes et les interactions entre les divers niveaux trophiques et l’impact sur les salmonidés. Didymosphenia geminata is mat-forming nuisance diatom. This epilithic microscopic alga can secrete copious amounts of mucilage creating thick and extensive mats covering the entire riverbed. Once considered very rare and representative of pristine water quality, it is now ubiquitous in rivers around the world. Over the past two decades, this alga has emerged as a nuisance diatom and generated much interest among freshwater ecologists and river managers alike. Nonetheless, controlling factors governing the occurrence and severity of D. geminata are still not well understood. In Quebec, the first massive proliferations of D. geminata were reported in 2006 in the Matapedia River. There was an urgency to fill this knowledge gap as managers and government agencies panicked at the lack of knowledge regarding its distribution, the causes of its onset and mostly, fear of that this alga would act as an additional stressor to Atlantic salmon populations. To better understand controlling factors of both cell division and mat formation, a conceptual model was developed with the collaboration of several researchers working in Colorado, Vancouver Island, New Zealand and Quebec to collate observations and field data. This synthesis work helped identify the factors favoring its colonization, growth and persistence in rivers. The spatiotemporal dynamics of D. geminata are dependent on various dynamic thresholds of flow, temperature, light and water chemistry within the habitat window. We can therefore test various arrays of these parameters to determine whether rivers are likely to present occasional to persistent D. geminata mats. To test and improve upon the conceptual model at various spatial scales, we developed a monitoring network for D. geminata mat presence. Twenty-two different organizations totaling 70 volunteers were trained to identify and quantify the proliferations of D. geminata. Between 2010 and 2015, 1 228 observations were made. The analysis of this database helped determine that 71% of the variability of D. geminata severity is inversely proportional to the intensity of the spring flood. At the reach scale, habitat type was determinant for presence-absence of mats with a strong significant preference for riffles. At the provincial scale, we compared the distribution of D. geminata in three regions of eastern Quebec (i.e. Gaspesie, Bas-St-Laurent and Cote-Nord) against numerous water chemistry parameters for twentynine rivers. At the broad regional scale, pH was the most important factor governing the presence-absence of cells. Diatoms have very specific pH optima and the contrasting geologies between regions confirmed that low pH and high tannins and lignin are not favorable to the survival and growth of D. geminata. Habitat preferences for D. geminata mats are identical to those of juvenile Atlantic salmon (i.e. shallow, fast, clear, cool, low nutrient and coarse substrate). To determine the extent of the impact of the presence of mats on the food web, we verified its impact on the algal community. The dense interwoven matrix creates a suitable physical environment for small diatoms, thus promoting greater taxonomic diversity. Despite an increase in the complexity of the biofilm with mat accrual, there is no additional impact on the structure and taxonomic diversity of the samples. D. geminata effects to higher trophic levels have been suspected since the structure of the habitat is modified and could alter the structure and functioning of the ecosystem. We studied the foraging behaviour of juvenile Atlantic salmon in contrasting D. geminata severities. With increasing percent cover of the alga, juvenile Atlantic salmon switch from a drift-foray to benthic-foray strategy. This change in behavior is not due to limited drifting prey availability. Our results reinforce the notion that juvenile Atlantic salmon have high behavioral plasticity in response to habitat changes. To test the impact of mats on juvenile salmon diet, we used a stable isotope analysis approach. This approach provides an integrated view of resource use by fish. Contrasting isotopic signatures between the liver and muscle tissues confirm a change in the seasonal diet. Juvenile salmon sampled in the D. geminata impacted site have a less diversified and carbon-depleted diet composed mainly of small chironomids and Trichoptera. Juvenile salmon condition factors and C:N ratios were not different between sites, though their size is smaller in the impacted site. Future work should focus on the effects of reduced prey quality on lipid content of fish. Over various international collaborations and discussions with managers, it became clear that there was a need for a clear and standardized recommendation on management measures for this nuisance species. Based on recent scientific knowledge and several management cases in various countries, we recommended that managers educate users to check, clean, dry and freeze their equipment. Regardless of whether D. geminata is an exotic or native species, it can be spread. In addition, the development of best practices limits the spread of aquatic organisms as others may be far more devastating than D. geminata. The results of this thesis contribute to the advancement of knowledge on the controlling factors of D. geminata for both cells and mats. In addition to contributing to the development of the conceptual model, we have tested and improved it by applying it to a variety of spatial scales: at the reach, watershed and regional scales. This is the first study to develop a monitoring network for mat severity with the involvement of local stakeholders. It is also the first study to evaluate the impact of D. geminata on periphytic communities in eastern Canada. Moreover, it is the first comprehensive study that has evaluated the effect D. geminata mats on juvenile Atlantic salmon ecology. Research on foraging behavior is also innovative and contributes significantly to the understanding of the mechanisms and interactions by which D. geminata impacts various trophic levels and salmonids.

Impact des changements climatiques sur la réponse des petits cours d'eau du nord de la Gaspésie, Québec - Boulet, Yan (Université du Québec à Rimouski, 2024)
RÉSUMÉ : Bien que représentant la majorité des réseaux hydrographiques à l’échelle mondiale, les petits cours d’eau de tête sont souvent mis de côté dans les analyses abordant les impacts qu’auront les changements climatiques sur leur régime hydrologique. Pourtant, ils sont d’une importance capitale pour la qualité des eaux de surface et des habitats en plus de représenter la source principale de sédiments contribuant au dynamisme des rivières qu’ils alimentent. Ce mémoire vise à utiliser des données météorologiques actuelles et de projections climatiques pour mieux comprendre la réponse hydrologique des petits bassins versants nord gaspésiens lors d’événements hydrologiques d’importance (torrentialité, crue printanière). En développant un seuil intensité – durée de déclenchement d’aléas hydrogéomorphologiques adapté au nord de la Gaspésie et en calculant des tendances climatiques, il a été observé que les événements surpassant le seuil seraient de 2 à 3 fois plus fréquents en 2100 qu’en 2011 selon les scénarios RCP4.5 et RCP8.5. Les résultats de ces analyses ont initié une réflexion sur les impacts morphologiques potentiels à prendre en compte dans une optique de gestion et d’utilisation du territoire dans une région où les cours d’eau sont particulièrement dynamiques et sensibles au déclenchement d’aléas hydrogéomorphologiques. La hausse de la fréquence des événements surpassant le seuil, le comportement hydrologique du cours d’eau instrumenté lors d’événements de crue connus et documentés et le modèle conceptuel proposé mettent en relation les changements climatiques projetés, les impacts sur la réponse hydrologique et les ajustements morphologiques qui pourraient survenir à l’intérieur des petits cours d’eau, sur leurs cônes alluviaux et dans les rivières principales dans lesquelles ils se jettent. -- Mot(s) clé(s) en français : changements climatiques, hydrogéomorphologie, petits cours d’eau, pluies torrentielles, Gaspésie, aléas. -- ABSTRACT : Even though they represent over 70% of stream length in drainage networks at the global scale, small headwater streams are often sidelined when evaluating climate change impacts on the hydrological regime of rivers. Yet, they are of capital importance in maintaining surface water and habitat quality for ecological and resource management purposes. Furthermore, they represent the main source of sediments for downstream fluvial systems, being the main contributor to their dynamics. This thesis aims to use historical meteorological data and climate projections to better understand the hydrological response of small gaspesian headwater streams to important flood events. By developing a triggering intensity – duration rainfall threshold for hydrogeomorphological hazards adapted to the region and extracting trends from precipitation projections, it has been observed that the annual number of events surpassing the threshold would at least double in 2100 in comparison to 2011. Those results initiated a reflection on potential morphological adjustments to consider for land use and management in a region where rivers are particularly mobile and sensitive to the triggering of hydrogeomorphological hazards. The increase in the frequency of triggering rainfall, the hydrological behavior of the instrumented stream during known and documented flood events and the proposed conceptual model help explain potential climate change effects on the hydrological response and morphological adjustments that could happen inside headwater streams, on their alluvial fan and in the main rivers they feed. -- Mot(s) clé(s) en anglais : climate change, hydrogeomorphology, headwater streams, torrential rainfall, Gaspesie, natural hazards.

Improving ensemble streamflow forecasts through targeted post-processing and rating curve uncertainty analysis - Askarinejad, Alireza (2024)
Abstract : Flood forecasting plays a pivotal role in effective water resource management and flood risk mitigation. Despite recent advancements, existing ensemble forecasting systems often grapple with issues of unreliability and under-dispersion. The uncertainty in ensemble forecasts can emanate from various sources, including inputs like precipitation, temperature, and streamflow, as well as initial conditions, model structure and parameters, and boundary conditions. Over the past two decades, numerous endeavors have been made to address bias and under-dispersion through the introduction of various statistical post-processing methods in meteorological and hydrological forecasts. However, a significant challenge lies in selecting the appropriate method and strategy in the forecast chain. Limited research has addressed the integration of pre-processing and post-processing in streamflow ensemble forecasting. Moreover, existing studies have generally focused on lumped hydrological models, while the performance of this integration in distributed hydrological models remains scarcely examined. On the other hand, streamflow data, often indirectly measured through rating curves, are particularly susceptible to errors. While various methods have been proposed to estimate rating curve uncertainty (RCU), the impact of RCU on streamflow forecasting system performance remains underexplored. In addition, current post-processing methods utilized in streamflow forecasting systems have disregarded the inherent uncertainty in observational streamflow data. Thus, this thesis delves into the potential and hurdles associated with considering different sources of uncertainty in flood forecasting systems and their impact on system performance. The primary objectives entail 1) assessing and identifying optimal scenarios from pre-processing of both temperature and precipitation and post-processing of streamflow forecasts approaches, or a combination thereof, and 2) evaluating the consideration of rating curve uncertainty on flood forecasting system performance through incorporating into targeted post-processing methodologies. The thesis focuses on a short-range ensemble streamflow forecasting framework spanning lead times of 1 to 5 days for the au Saumon watershed in southern Quebec, Canada. This watershed, being flood-prone, encountered significant challenges during the 2019 and 2017 flood events, including widespread inundation, road closures, and damage to property and infrastructure. Enhancing streamflow ensemble forecasts and upgrading flood forecasting systems holds the potential to greatly benefit decision-makers and the local populace. Chapter 4 (Results part 1), presented as a scientific article, thus delves into assessing and employing various pre- and post-processing strategy scenarios within the flood forecasting framework employing a spatially distributed hydrological model. By applying different statistical processing and bias correction techniques, the performance and quality of ensemble streamflow forecasts were evaluated across different scenarios. The findings highlight biases and under-dispersion as significant factors affecting raw ensemble forecasts. Pre-processing partially improves raw forecasts but doesn't fully address bias in under-dispersed forecasts. Combining pre- and post-processing enhances forecast skill and reliability, albeit with some variations compared to post-processing alone. Integrating flood events into the training dataset and optimizing its length improves the effectiveness of processing methods, underscoring the critical role of data management strategies in enhancing streamflow forecasting systems. Subsequently, Chapter 5 (Results part 2) , evaluates the consideration of rating curve uncertainty, derived from the Voting Point Method (VPM) and Bayesian Rating curve (BaRatin) estimation methods, on the performance of streamflow ensemble forecasts by integrating into a targeted post-processing approach using Weighted Ensemble Dressing (WED) and Cumulative Distribution Function Matching (CDFM) post-processing methods. Post-processing without RCU enhances forecasting system skill and reliability but overlooks the inherent uncertainty in observational data, posing concerns about its effectiveness. Conversely, integrating RCU improves forecast skill, reliability, and effectively addresses observational data uncertainty, offering a notable advantage over traditional post-processing methods. Comparing WED and CDFM post-processing methods highlighted nuanced differences in forecast outcomes, influenced by uncertainty estimation techniques. Both methods showed favorable accuracy metrics, with RCU integration, especially from VPM, notably enhancing forecast quality. However, variations in RCU from different estimation methods may lead to forecast underestimation or overestimation, warranting careful consideration. These findings collectively shed light on the potential and challenges associated with incorporating different sources of uncertainty into flood forecasting systems.

Développement d’approches statistiques multivariées pour les modèles de copules, applications en hydrologie. - Ben Nasr, Iméne (Doctorat en sciences de l'eau, 2021)
Les études portant sur les évènements hydrologiques extrêmes sont d’une grande importance vu leurs nombreux impacts socio-économiques. Ces études reposent dans une large mesure sur la capacité à estimer adéquatement les risques associés à ces évènements. Dans ce cadre, l’analyse fréquentielle (AF) est une des approches les plus utilisées pour la modélisation et l’estimation des risques associés aux évènements extrêmes. Généralement, ces évènements sont caractérisés par plusieurs variables dépendantes, comme le volume, la pointe et la durée pour les crues. Par conséquent, l'analyse de chacune de ces variables séparément ne peut pas fournir une évaluation complète des risques et peut engendrer des pertes de vies humaines ou de biens associés à une sous estimation, ou une augmentation des coûts des ouvrages hydrauliques associés à une surestimation. L’AF multivariée (AFM) permet de pallier ce problème en considérant simultanément ces variables. L’AF classique est basée sur trois hypothèses à savoir l’homogénéité, la stationnarité et l’indépendance. Par ailleurs, différentes conditions non standards telles que la complexité topographique, les perturbations par les aménagements urbains et les changements climatiques peuvent influencer la réponse hydrologique. De telles conditions rendent la prédétermination des crues, par les méthodes classiques d’AFM, un exercice non efficace et mal adapté à de tels contextes. L’objectif de cette thèse consiste à proposer de nouvelles méthodes plus prometteuses pour l'analyse et la modélisation des variables hydrologiques à la fois dans un cadre multivarié et en l’absence de l’hypothèse d’homogénéité. Ces méthodes visent à contourner les limites de celles utilisées dans la littérature. Ces nouvelles méthodes, basées sur les copules, permettent une meilleure estimation des risques des extrêmes hydrologiques en tenant compte des interactions et es dépendances entre les différentes variables. Par conséquent, les gestionnaires des ressources hydriques peuvent prendre des décisions éclairées et mieux adaptées au contexte actuel. Précisément, nous nous intéressons dans une première partie à tester l’homogénéité des séries hydrologiques multivariées. Pour ce faire, nous avons proposé un nouveau test, basé sur les L moments multivariés, capable de détecter la rupture dans la structure de dépendance des variables hydrologiques. Les résultats obtenus montrent la bonne performance du test proposé sous différents scénarios. Par la suite, dans le but de modéliser l’hétérogénéité des séries hydrologiques multivariées, un modèle de mélange de copules a été mis au point. Dans ce cadre, nous avons proposé une nouvelle méthode pour l’estimation des différents paramètres du modèle. La méthode proposée est basée sur l’utilisation des algorithmes génétiques. Sa performance est illustrée sur des séries simulées. Les résultats obtenus montrent que la méthode proposée est un outil efficace capable de fournir de bonnes estimations, en particulier dans un contexte hydrologique. Finalement, deux nouveaux tests d’adéquation pour les copules multiparamètres ont été développés. Le but de ces tests est de vérifier la qualité de l’ajustement de la copule aux données et améliorer ainsi l’estimation des risques associés aux évènements extrêmes. Les résultats révèlent que les tests proposés performent bien dans le contexte hydrologique. Studies of hydrological extreme events are of great importance given their many socio-economic impacts. These studies rely on the ability to adequately estimate the associated risk. In this context, frequency analysis (FA) is one of the most widely used approaches for modeling and estimating the risks associated with extreme events. Generally, these events are characterized by several correlated random variables. Therefore, analyzing each of these variables separately cannot provide a complete risk assessment and may result in loss of life or property associated with an underestimation, or an increase in the costs of hydraulic structure associated with an overestimation. Multivariate FA (MFA) overcomes this problem by simultaneously considering these variables. Classical FA is based on three assumptions namely homogeneity, stationarity and independence. However, different non-standard conditions such as topographic complexity, disturbances by urban development and climate change can influence the hydrological response. Such conditions make flood predetermination, by conventional MFA methods, an ineffective exercise and unsuitable to such contexts. The main objective of this thesis is to propose new and more promising methods for the analysis and modeling of hydrological variables both in a multivariate framework and in the lack of the homogeneity assumption. These methods aim to overcome the limitations of classical methods used in the literature. These new proposed methods, based on copulas, allow a better estimation of the risks associated to hydrological extremes by taking into account the dependence between the different variables. As a result, water resource managers can make informed decisions that are better suited to the current context. In the first part, we propose a novel statistical test for multivariate heterogeneity detection, based on copula and multivariate L-moments. A simulation study is conducted to evaluate the performance of the proposed test and to compare it with those of existing tests. Results show the ability of the proposed test to discriminate homogeneous and inhomogeneous series. In the second part, we propose a new model based on mixtures of copulas that take into account the heterogeneity of multivariate hydrological series. To estimate the components of this model, we propose a new parameter estimation approach, based on the maximum pseudo-likelihood using genetic algorithms. Results indicate that the proposed method estimates more accurately the parameters even with small sample sizes compared to the existing classical EM method. In the last part, we introduce new goodness of fit (GOF) tests specifically for multiparameter copulas and adapted to hydrometeorological context. More precisely, the proposed GOF tests are based on multivariate L moments. A simulation study is conducted to evaluate and compare the performances of the proposed tests. The results confirm the usefulness of the new GOF tests in comparison with some well-established ones.

Novel statistical analysis illustrates the importance of flow source for extreme variation in dissolved organic carbon in a eutrophic reservoir in the Great Plains - Baron, Anthony A. P.; Baulch, Helen M.; Nazemi, Ali; Whitfield, Colin J. (Hydrology and Earth System Sciences, 2025)
Abstract. Dissolved organic carbon (DOC) trends, predominantly showing long-term increases in concentration, have been observed across many regions of the Northern Hemisphere. Elevated DOC concentrations are a major concern for drinking water treatment plants, owing to the effects of disinfection byproduct formation, the risk of bacterial regrowth in water distribution systems, and treatment cost increases. Using a unique 30-year data set encompassing both extreme wet and dry conditions in a eutrophic drinking water reservoir in the Great Plains of North America, we investigate the effects of changing source-water and in-lake water chemistry on DOC. We employ novel wavelet coherence analyses to explore the coherence of changes in DOC with other environmental variables and apply a generalized additive model to understand predictor–DOC responses. We found that the DOC concentration was significantly coherent with (and lagging behind) flow from a large upstream mesotrophic reservoir at long (> 18-month) timescales. DOC was also coherent with (lagging behind) sulfate and in phase with total phosphorus, ammonium, and chlorophyll a concentrations at short (≤ 18-month) timescales across the 30-year record. These variables accounted for 56 % of the deviance in DOC from 1990 to 2019, suggesting that water-source and in-lake nutrient and solute chemistry are effective predictors of the DOC concentration. Clearly, climate and changes in water and catchment management will influence source-water quality in this already water-scarce region. Our results highlight the importance of flow management to shallow eutrophic reservoirs; wet periods can exacerbate water quality issues, and these effects can be compounded by reducing inflows from systems with lower DOC. These flow management decisions address water level and flood risk concerns but also have important impacts on drinking water treatability.
Keywords: Infolettre; Infolettre_Avril_2025

Disaster Risk Resilience: Conceptual Evolution, Key Issues, and Opportunities - Graveline, Marie-Hélène; Germain, Daniel (International Journal of Disaster Risk Science, 2022)
Abstract Resilience has become a cornerstone for risk management and disaster reduction. However, it has evolved extensively both etymologically and conceptually in time and across scientific disciplines. The concept has been (re)shaped by the evolution of research and practice efforts. Considered the opposite of vulnerability for a long time, resilience was first defined as the ability to resist, bounce back, cope with, and recover quickly from the impacts of hazards. To avoid the possible return to conditions of vulnerability and exposure to hazards, the notions of post-disaster development, transformation, and adaptation (build back better) and anticipation, innovation, and proactivity (bounce forward) were then integrated. Today, resilience is characterized by a multitude of components and several classifications. We present a selection of 25 components used to define resilience, and an interesting linkage emerges between these components and the dimensions of risk management (prevention, preparedness, response, and recovery), offering a perspective to strengthen resilience through the development of capacities. Despite its potential, resilience is subject to challenges regarding its operationalization, effectiveness, measurement, credibility, equity, and even its nature. Nevertheless, it offers applicability and opportunities for local communities as well as an interdisciplinary look at global challenges.

Quel regard porter sur le travail social à l’ère des changements climatiques? : le cas des inondations (2017-2019) au Québec - Hamelin, Marilou (2021)
Les changements climatiques anthropogéniques posent des défis énormes pour toutes les sociétés humaines. Ces défis majeurs mettront à l’épreuve les capacités d’adaptation des États et de ses institutions et des communautés partout dans le monde et devront se résoudre par un élan de solidarité humaine afin d’en atténuer les conséquences. Le Canada connaît déjà un réchauffement climatique important. Le pays a d’ailleurs récemment été touché par des événements climatiques extrêmes : des canicules, des feux de forêt, une sécheresse anormale et des inondations dont l’intensité est prévue d’augmenter avec les changements climatiques anthropogéniques. La province du Québec a quant à elle été touchée par de fortes inondations entre 2017 et 2019. L’objectif principal de la présente étude vise à discuter la manière dont le paradigme écosocial peut faire évoluer le travail social en tant que champ de savoir et d’intervention dans un contexte de changements climatiques. Cette étude s’est appuyée sur des données issues de groupes focus réalisés avec des intervenants suite aux inondations survenues au Québec (2017-2019). Notre analyse vise les interventions réalisées en contexte d’inondations, dans le sud de la province, mise en œuvre par le système de santé. Les données ont été collectées lors d’entrevues de groupe réalisées avec des intervenants psychosociaux et des gestionnaires de CI(U)SSS au courant des mois d’octobre et de novembre 2019. Les thèmes suivants ont émergé des analyses: les caractéristiques des inondations de 2019, les divergences d’opinions vis-à-vis des changements climatiques, l’aide et le soutien apportés durant les inondations et la participation citoyenne. J’insisterai également sur l’exacerbation possible des inégalités sociales dans ce contexte. D’autres thèmes se sont également révélés importants : l’engagement des intervenants psychosociaux, la participation et la décentralisation des décisions politiques. Enfin, mes réflexions porteront sur les conséquences sociales qu’entrainent les inondations et sur les types de pratiques sociales qui s’avèrent pertinentes à l’ère des changements climatiques et dans un contexte d’urgence.

A review of the current state of knowledge of proglacial hydrogeology in the Cordillera Blanca, Peru - Glas, Robin; Lautz, Laura; McKenzie, Jeffrey; Mark, Bryan; Baraer, Michel; Chavez, Daniel; Maharaj, Laura (WIREs Water, 2018)
The rapidly melting glaciers of Peru are posing new risks to regional dry season water supplies, and this is evident in the Cordillera Blanca, the mountain range with the world's largest concentration of tropical glaciers. Permanent ice loss is causing reductions to dry season streamflow, which is coupled with shifting demands and control over water access and entitlements in the region. A full evaluation of hydrologic inputs is required to inform future water management in the relative absence of glaciers. Over the last decade, new studies have shown groundwater to be a significant component of the regional water budget during the dry season, and it cannot be ignored when accounting for water quality and quantity downstream of the Cordillera Blanca's alpine catchments. Distinctive common features of the Cordillera Blanca's proglacial catchments are sediment‐filled valleys that were once under proglacial lake conditions. The combination of lake sediments with other alpine depositional features results in storage and interseasonal release of groundwater that comprises up to 80% of the valley's streamflow during the driest months of the year. We summarize the emerging understanding of hydrogeologic processes in proglacial headwater systems of the region's principal river, the Rio Santa, and make suggestions for future research that will more clearly characterize the spatial distribution of stored groundwater within the mountain range. As glaciers continue to recede, differences in aquifer thickness and groundwater residence time between alpine catchments in the region will increasingly control dry season water availability at the local and basin scale. This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water and Environmental Change Engineering Water > Planning Water
Keywords: Baraer_Michel

Monitoring of cyanobacterial breakthrough and accumulation by in situ phycocyanin probe system within full-scale treatment plants - Ma, Liya; Maldonado, Juan Francisco Guerra; Zamyadi, Arash; Dorner, Sarah; Prévost, Michèle (Environmental Monitoring and Assessment, 2023)
Abstract Worldwide, there has been an increase in the presence of potentially toxic cyanobacterial blooms in drinking water sources and within drinking water treatment plants (DWTPs). The objective of this study is to validate the use of in situ probes for the detection and management of cyanobacterial breakthrough in high and low-risk DWTPs. In situ phycocyanin YSI EXO2 probes were devised for remote control and data logging to monitor the cyanobacteria in raw, clarified, filtered, and treated water in three full-scale DWTPs. An additional probe was installed inside the sludge holding tank to measure the water quality of the surface of the sludge storage tank in a high-risk DWTP. Simultaneous grab samplings were carried out for taxonomic cell counts and toxin analysis. A total of 23, 9, and 4 field visits were conducted at the three DWTPs. Phycocyanin readings showed a 93-fold fluctuation within 24 h in the raw water of the high cyanobacterial risk plant, with higher phycocyanin levels during the afternoon period. These data provide new information on the limitations of weekly or daily grab sampling. Also, different moving averages for the phycocyanin probe readings can be used to improve the interpretation of phycocyanin signal trends. The in situ probe successfully detected high cyanobacterial biovolumes entering the clarification process in the high-risk plant. Grab sampling results revealed high cyanobacterial biovolumes in the sludge for both high and low-risk plants.
Keywords: Dorner_Sarah

Evidence-Based Framework to Manage Cyanobacteria and Cyanotoxins in Water and Sludge from Drinking Water Treatment Plants - Jalili, Farhad; Moradinejad, Saber; Zamyadi, Arash; Dorner, Sarah; Sauvé, Sébastien; Prévost, Michèle (Toxins, 2022)
Freshwater bodies and, consequently, drinking water treatment plants (DWTPs) sources are increasingly facing toxic cyanobacterial blooms. Even though conventional treatment processes including coagulation, flocculation, sedimentation, and filtration can control cyanobacteria and cell-bound cyanotoxins, these processes may encounter challenges such as inefficient removal of dissolved metabolites and cyanobacterial cell breakthrough. Furthermore, conventional treatment processes may lead to the accumulation of cyanobacteria cells and cyanotoxins in sludge. Pre-oxidation can enhance coagulation efficiency as it provides the first barrier against cyanobacteria and cyanotoxins and it decreases cell accumulation in DWTP sludge. This critical review aims to: (i) evaluate the state of the science of cyanobacteria and cyanotoxin management throughout DWTPs, as well as their associated sludge, and (ii) develop a decision framework to manage cyanobacteria and cyanotoxins in DWTPs and sludge. The review identified that lab-cultured-based pre-oxidation studies may not represent the real bloom pre-oxidation efficacy. Moreover, the application of a common exposure unit CT (residual concentration × contact time) provides a proper understanding of cyanobacteria pre-oxidation efficiency. Recently, reported challenges on cyanobacterial survival and growth in sludge alongside the cell lysis and cyanotoxin release raised health and technical concerns with regards to sludge storage and sludge supernatant recycling to the head of DWTPs. According to the review, oxidation has not been identified as a feasible option to handle cyanobacterial-laden sludge due to low cell and cyanotoxin removal efficacy. Based on the reviewed literature, a decision framework is proposed to manage cyanobacteria and cyanotoxins and their associated sludge in DWTPs.
Keywords: Dorner_Sarah

Simplified tree marking guidelines enhance value recovery as well as stand vigour in northern hardwood forests under selection management - Moreau, Guillaume; Chagnon, Catherine; Cecil-Cockwell, Malcolm J L; Pothier, David; Achim, Alexis; Bédard, Steve; Guillemette, François; Caspersen, John (Forestry: An International Journal of Forest Research, 2024)
Abstract In northern hardwood forests, tree markers select the trees to be harvested during logging operations using classification systems that assign harvest priorities based on the presence of a wide range of individual defects. According to the most recent advances in our understanding of the impact of defects on both tree vigour (the risk of mortality or decline in growth) and quality (the potential for recovering valuable sawlogs), tree markers should adopt a simpler classification system that considers fewer defects than the current operational practice, and they should prioritize the removal of trees with crown dieback. Since the probability of developing defects and dying increases substantially with tree diameter, tree markers should also favour the removal of larger trees that have maintained their quality. However, these recommendations were developed based on tree-level analyses. To provide further validation at the stand scale, we compared stand improvement and value recovery under three tree marking regimes: a new, simplified regime based on the recommendations above, and two regimes used in the province of Quebec, Canada. To do so, we conducted tree marking simulations and value recovery assessments in 14 managed stands distributed across the northern hardwood range of Quebec. Our results confirmed that the simplified tree marking regime not only facilitated stand improvement by removing a greater proportion of low-vigour trees, but also recovered significantly more value (17% on average) at the stand scale. By prioritizing the removal of trees with crown dieback, the simplified regime was superior at salvaging the current value of low-vigour trees before they die or decline in quality. Based on our results, we propose simplified and empirically-validated tree marking guidelines for northern hardwood forests.
Keywords: Guillemette_Francois

Quantifying the Probability of Decline in Quality: Implications for Selection Management in Northern Hardwood Forests - Moreau, Guillaume; Cecil-Cockwell, Malcolm J. L.; Achim, Alexis; Bédard, Steve; Guillemette, François; Caspersen, John (Forests, 2023)
Northern hardwoods are susceptible to a wide range of defects that can reduce the amount of sound wood with desirable qualities, such as the clear sapwood of sugar maple trees. Yet, the rate at which trees decline in quality due to the development of such defects has never been quantified in northern hardwood forests due to a dearth of repeat inventories that record the appearance of defects over time. As a result, it remains uncertain whether, and how, selection management reduces the probability of decline in quality. In this study, we quantify the rate at which trees decline in quality due to the development of defects, and we test several hypotheses regarding the influence of selection management on quality. Our results show that (1) the probability of decline in quality increases as trees grow larger; (2) crown dieback also increases the probability of decline in quality; (3) the probability of decline in quality is slightly lower in managed stands than in unmanaged stands, and (4) the probability of decline in quality increases with the mean annual temperature of the site. Finally, we combined our estimates of the probability of decline in quality with previous estimates of the probability of mortality to assess the overall risk associated with retaining trees of different species, sizes, and vigour profiles. The resulting metric can inform efforts to improve the management of northern hardwood forests by providing an integrated estimate of the risk that the value of a tree will be reduced, or eliminated, due to mortality or decline in quality.
Keywords: Guillemette_Francois

Potential for Sugar Maple to Provide High-Quality Sawlog Trees at the Northern Edge of Its Range - Guillemette, François; Bédard, Steve (Forest Science, 2019)
Abstract The management of sugar maple (Acer saccharum) at the northern edge of its range is mainly oriented toward timber production, from trees of higher grades. However, both the quality of mature trees in natural stands and how the quality may vary depending on the silvicultural treatment are unknown, especially under northern conditions. The objective of this study was to describe the variation in stem quality of mature maple trees (diameter >33 cm) according to climatic, geographic or soil variables, and to evaluate the effects of a first selection cutting cycle on this quality. Annual temperature (1.7–4.1° C) was the most important variable explaining differences in the proportion of higher-grade trees, with a 16 percent gain associated with every additional increase in degrees Celsius. The practice of a first selection cutting was associated with an 11 percent gain in this proportion. Although the actual proportion of high-quality trees was below 35 percent on the coolest sites, a proper tree selection through silviculture could likely improve this proportion in future decades, whereas the potential effects of climate change are unclear.
Keywords: Guillemette_Francois

Artefacts of disaster risk reduction: conceptualizing bottom-up initiatives of climate action in informal settlements - Lizarralde, Gonzalo; Herazo, Benjamín; Smith, David; Bornstein, Lisa; Gould, Kevin; Monsalve, Elsa; Ordoñez, Nicolás; López, Adriana; López, Oswaldo; Burdiles, Roberto; Araneda, Claudio; Olivera, Andrés (Disaster Prevention and Management: An International Journal, 2024)
Purpose Disaster risk reduction is of prime importance in informal settlements in the Global South, where several forms of vulnerability coexist. Policy and official programmes, however, rarely respond to the needs and expectations of citizens and local leaders living in these settlements. Even though these agents constantly attempt to reduce risks in their own way, we know very little about their activities, motivations and effective impact on risk reduction. Here we seek to conceptualize bottom-up initiatives to better grasp their origins, limitations and success. Design/methodology/approach Through a four-year action-research project in Colombia, Cuba and Chile, we theorize about the production of change by local agents. Through detailed case studies we explored the activism of 17 local leaders. Through narrative analysis we studied their motivations and explanations. Finally, by documenting 22 initiatives, we revealed effective changes in space. Findings In the face of risk and disasters, residents and leaders in informal settings engaged in symbolic, physical and social spaces of interaction. Their actions were guided by trust, emotions, time cycles and activism. Local agency was justified by narratives about risk and climate change that differ from those of authorities and scholars. Research limitations/implications There is still limited understanding of bottom-up initiatives in informal settings. It is crucial to conceptualize their origins, limitations and success. The focus on three specific countries necessitates further research for broader applicability and understanding. Practical implications A better comprehension of bottom-up actions is crucial for informing policies and programmes aimed at reducing risk in informal settings. Stakeholders must recognize the political, social and cultural roles of these actions for more impactful climate action. Originality/value We borrow Simon’s concept of “artefact” to introduce the notion of “Artefacts of Disaster Risk Reduction”, providing insights into the multifaceted nature of bottom-up initiatives. We also emphasize the simultaneous political and phenomenological character of these actions, contributing to a deeper understanding of their origins and impact.
Keywords: Infolettre; Infolettre_Ete_2024; Lizarralde_Gonzalo

The diffusion of climate change adaptation policy - Schoenefeld, Jonas J.; Schulze, Kai; Bruch, Nils (Wiley Interdisciplinary Reviews: Climate Change, 2022)
Adapting to some level of climate change has become unavoidable. However, there is surprisingly limited systematic knowledge about whether and how adaptation policies have diffused and could diffuse in the future. Most existing adaptation studies do not explicitly examine policy diffusion, which is a form of interdependent policy-making among jurisdictions at the same or across different levels of governance. To address this gap, we offer a new interpretation and assessment of the extensive adaptation policy literature through a policy diffusion perspective; we pay specific attention to diffusion drivers and barriers, motivations, mechanisms, outputs, and outcomes. We assess the extent to which four motivations and related mechanisms of policy diffusion—interests (linked with learning and competition), rights and duties (tied to coercion), ideology, and recognition (both connected with emulation)—are conceptually and empirically associated with adaptation. We also engage with adaptation policy characteristics, contextual conditions (e.g., problem severity) and different channels of adapation policy diffusion (e.g., transnational networks). We demonstrate that adaptation policy diffusion can be associated with different mechanisms, yet many of them remain remarkably understudied. So are the effects of adaptation policy diffusion in terms of changes in vulnerability and resilience. We thus identify manifold avenues for future research, and provide insights for practitioners who may hope to leverage diffusion mechanisms to enhance their adaptation efforts. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Vulnerability and Adaptation to Climate Change > Institutions for Adaptation

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America - Lizarralde, Gonzalo; Páez, Holmes; Lopez, Adriana; Lopez, Oswaldo; Bornstein, Lisa; Gould, Kevin; Herazo, Benjamin; Muñoz, Lissette (Disaster Prevention and Management: An International Journal, 2020)
Purpose Few people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and authorities place under the resilience framework? Design/methodology/approach Three longitudinal case studies in Yumbo, Salgar and San Andrés (Colombia) serve to investigate narratives of disaster risks and responses to them. Methods include narrative analysis from policy and project documents, presentations, five workshops, six focus groups and 24 interviews. Findings The discourse adopted by most international scholars and local authorities differs greatly from that used by citizens to explain risk and masks the politics involved in disaster reduction and the search for social justice. Besides, narratives of social change, aspirations and social status are increasingly masked in disaster risk explanations. Tensions are also concealed, including those regarding the winners and losers of interventions and the responsibilities for disaster risk reduction. Originality/value Our findings confirm previous results that have shown that the resilience framework contributes to “depoliticize” the analysis of risk and serves to mask and dilute the responsibility of political and economic elites in disaster risk creation. But they also show that resilience fails to explain the type of socioeconomic change that is required to reduce vulnerabilities in Latin America.
Keywords: Lizarralde_Gonzalo

Development and validation of an index to measure progress in adaptation to climate change at the municipal level - Jacob, Johann; Valois, Pierre; Tessier, Maxime (Ecological Indicators, 2022)
Background Given the important role that municipalities must play in adapting to climate change, it is more than ever essential to measure their progress in this area. However, measuring municipalities’ adaptation progress presents its share of difficulties especially when it comes to comparing (on similar dimensions and over time) the situation of different municipal entities and to linking adaptation impacts to local actions. Longitudinal studies with recurring indicators could capture changes occurring over time, but the development of such indicators requires great emphasis on methodological and psychometric aspects, such as measurement validity. Therefore, this study aimed to develop and validate an index of adaptation to heatwaves and flooding at the level of municipal urbanists and urban planners. Methods A sample of 139 officers working in urbanism and urban planning for municipal entities in the province of Quebec (Canada) completed an online questionnaire. Developed based on a literature review and consultation of representatives from the municipal sector, the questionnaire measured whether the respondent’s municipal entity did or did not adopt the behaviors that are recommended in the scientific and gray literature to adapt to heatwaves and flooding. Results Results of the various metrological analyses (indicator reliability analysis, first order confirmatory factor analysis, concurrent validity analysis, and nomological validity assessment analysis) confirmed the validity of the index developed to measure progress in climate change adaptation at the municipal level. The first dimension of the index corresponds to preliminary measures that inform and prepare stakeholders for action (i.e., groundwork adaptation initiatives), whereas the second refers to measures that aim to concretely reduce vulnerability to climate change, to improve the adaptive capacity or the resilience of human and natural systems (i.e., adaptation actions). Conclusion The results of a series of psychometric analyses showed that the index has good validity and could properly measure the adoption of actions to prepare for adaptation as well as adaptation actions per se. Municipal and government officials can therefore consider using it to monitor and evaluate adaptation efforts at the municipal level.
Keywords: Infolettre; Infolettre_Avril_2022; Site_internet_RIISQ

Hydrological behaviour of an ice‐layered snowpack in a non‐mountainous environment - Paquotte, Andrea; Baraer, Michel (Hydrological Processes, 2022)
Abstract The increased frequency of mild rain‐on‐snow (R.O.S.) events in cold regions associated with climate change is projected to affect snowpack structure and hydrological behaviour. The ice layers that form in a cold snowpack when R.O.S. events occur have been shown to influence flowthrough processes and liquid water retention, with consequences for winter floods, groundwater recharge, and water resources management. This study explores interconnections between meteorological conditions, ice layer formation, and lateral flows during R.O.S. events throughout the 2018–2019 winter in meridional Quebec, Canada. Automated hydro‐meteorological measurements, such as water availability for runoff, snow water equivalent, and snowpit observations, are used to compute water and energy balances, making it possible to characterize a snowpack's internal conditions and flowthrough regimes. For compatibility assessment, water and energy balances‐based flowthrough scenarios are then compared to different hydro‐meteorological variables', such as water table or streamlet water levels. The results show an association between highly variable meteorological conditions, frequent R.O.S. events, and ice layer formation. Lateral flows were mainly observed during the early stage of the ablation period. The hydrologically significant lateral flows observed in the study are associated with winter conditions that are predicted to become more frequent in a changing climate, stressing the need for further evaluation of their potential impact at the watershed scale.
Keywords: Baraer_Michel; Infolettre; Infolettre_Ete_2023

Espace de liberté: un cadre de gestion intégrée pour la conservation des cours d’eau dans un contexte de changements climatiques - Biron, P.; Buffin-Bélanger, T.; Larocque, M.; Demers, S.; Olsen, T.; Ouellet, M.-A.; Choné, G.; Cloutier, C.-A.; Needelman, M. (OURANOS, 2013)
Les changements climatiques anticipés produiront des crues plus fréquentes et des étiages plus prononcés qui menaceront la sécurité publique et l’état des écosystèmes fluviaux. L’espace de liberté des cours d’eau est un cadre de gestion intégrée considérant l’hydrogéomorphologie des rivières. Il vise à identifier des espaces d’inondabilité et de mobilité du cours d’eau où on accepte de le laisser évoluer plutôt que de le contraindre dans un tracé façonné par les interventions anthropiques. Cette approche apparaît prometteuse pour une gestion durable dans un climat changeant, car elle maintient les fonctions physiques naturelles des cours d’eau (transport de l’eau et des sédiments), ce qui augmente leur résilience. L’espace de liberté reconnaît aussi le rôle majeur de la connectivité entre la rivière et la nappe phréatique, notamment par l'entremise des milieux humides qui contribuent à l’atténuation des crues et des étiages et à une amélioration de la qualité de l’eau. Les objectifs de ce projet consistent à 1) développer l’approche de gestion des cours d’eau basée sur les concepts d’espace de liberté pour les cours d’eau du Québec et examiner sa mise en œuvre pour renforcer la capacité de résilience des rivières dans un contexte de changements climatiques; 2) évaluer la connectivité entre la rivière et la nappe afin de mieux comprendre le rôle des milieux humides dans l'espace de liberté des cours d’eau et 3) effectuer une analyse avantages-coûts de l’implantation d’un espace de liberté. L’espace de liberté a été déterminé par l’approche hydrogéomorphologique et cartographié pour trois cours d’eau contrastés du Québec (rivières de la Roche et Yamaska Sud-Est en Montérégie et rivière Matane en Gaspésie). La démarche consiste 1) d’une analyse de photographies historiques anciennes, de modèles numériques d’altitude et d’observations sur le terrain; 2) de mesures simultanées des niveaux et des températures de la nappe phréatique et du cours d’eau et 3) de simulations numériques pour estimer l’impact des changements climatiques sur la mobilité et l’inondabilité des cours d’eau. La méthodologie développée pour définir l’espace de liberté est robuste et s’applique tant pour les cours d’eau agricoles (rivière de la Roche et Yamaska Sud-Est) que pour les rivières à saumon plus dynamiques comme la rivière Matane. L’espace de liberté inclut trois niveaux d’inondabilité (N1 : très fréquente et/ou avec forts courants, N2 : fréquente de faible courant, N3 : peu fréquente), deux niveaux de mobilité (M1 : à court terme (50 ans) et M2 : basée sur l’amplitude des méandres), ainsi que les milieux humides. Les analyses de sensibilité par simulation numérique révèlent que les limites de l’espace de liberté intègrent adéquatement la mobilité et l’inondabilité attendues dans un climat futur. Une cartographie simplifiée de l’espace de liberté, à deux niveaux, est également produite. L’espace de liberté minimal (L1) inclut les inondations très fréquentes (N1), les milieux humides riverains ainsi que la mobilité à court terme (M1). C’est une zone où il ne devrait pas y avoir d’aménagement. La zone L2 représente quant à elle l’espace fonctionnel de la rivière (N2 et M2) qui devrait être protégé afin que la dynamique naturelle de la rivière puisse opérer en climat actuel et futur. Les aménagements dans cette zone devraient tenir compte des risques d’érosion et d’inondation. Les résultats de l’analyse avantages-coûts suggèrent que l’aménagement d’espaces de liberté serait économiquement avantageux pour les trois cours d’eau. Malgré la perte du droit de construire et de cultiver dans l’espace de liberté, accompagnée par une compensation financière pour les agriculteurs, des gains nets variant entre 0,7 et 3,7 millions de dollars sont estimés sur une période de 50 ans. Ceci est dû aux réductions des coûts de protection des berges déjà stabilisées et qui le seraient à l’avenir, mais aussi aux services écologiques rendus par les milieux humides et les bandes riveraines. Une gestion par espace de liberté des cours d’eau du Québec exige un changement majeur dans nos perceptions et nos représentations des rivières qui, jusqu’à maintenant, ont été considérées comme des entités relativement statiques dans le paysage. Une telle approche apportera notamment comme avantage de faciliter l’adaptation aux risques liés à une plus grande variabilité des débits en climat futur par une gestion proactive qui améliore la santé des cours d’eau tout en étant avantageuse économiquement à moyen et à long terme. Elle contribuera également à diminuer les risques pour les infrastructures et la sécurité publique en utilisant une cartographie basée sur la dynamique des cours d’eau pour déterminer les zones où les aménagements devraient être interdits à l’avenir.
Keywords: Ouvrage_Collectif_Numéro1

Dynamics of household welfare change and analysis of coping strategies during floods: an empirical investigation - Senapati, Sibananda (International Journal of Social Economics, 2024)
Purpose This study aims to understand the socioeconomic impact of flood events on households, especially household welfare in terms of changes in consumption and coping strategies to deal with flood risk. This study is based on Bihar, one of the most frequently flood-affected, most populous and economically backward states in India. Design/methodology/approach Primary data were collected from 700 households in the seven most frequently flood-affected districts in Bihar. A total of 100 individuals from each district were randomly selected from flood-affected villages. Based on a detailed literature review, an econometric (probit) model was developed to test the null hypothesis of the availability of consumption insurance, and the multivariate probability approach was used to analyze the various coping strategies of these households. Findings The results of this study suggest that flood-affected households maintain their consumption by overcoming various losses, including income, house damage and livestock loss. Households depend on financial transfers, borrowings and relief, and migrate to overcome losses. Borrowing could be an extra burden as the government compensates for house damage and crop loss late to the affected households. Again, there is no compensation to overcome livelihood loss and deal with occurrences of post-flood diseases, which further emphasizes the policy implications of strengthening the health infrastructure in the state and generating alternative livelihood opportunities. Originality/value This study discusses flood risk in terms of changes in household welfare, identifies the most effective risk-coping capabilities of rural communities and contributes to the shortcomings of the government insurance and relief model. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-07-2023-0569

Flood impact on income inequality in the Itapocu River basin, Brazil - Silva Araújo, Rafael; Ohara, Miho; Miyamoto, Mamoru; Takeuchi, Kuniyoshi (Journal of Flood Risk Management, 2022)
Abstract Disasters worldwide tend to affect the poorest more severely and increase inequality. Brazil is one of the countries with high income‐inequality rates and has unplanned urbanization issues and an extensive disaster risk profile with little knowledge on how those disasters affect people's welfare. Thus, disasters often hit the poorest hardest, increasing the country's income inequality and poverty rates. This study proposes a method to assess the impact of floods on households spatially based on their income levels by conducting flood analysis and income analysis. The method is applied to the Itapocu River basin (IRB) located in Santa Catarina State, Brazil. The flood is assessed by conducting rainfall analysis and hydrological simulation and generating flood inundation maps. The income is evaluated using downloaded 2010 census data and a dasymetric approach. Flood and income information is combined to analyze flood‐impacted households by income level and flood return period. The results confirm the initial assumption that flood events in the IRB are more likely to affect the lowest‐income households rather than the highest‐income levels, thus, increasing the income inequality.

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

Urban form and structure explain variability in spatial inequality of property flood risk among US counties - Ma, Junwei; Mostafavi, Ali (Communications Earth & Environment, 2024)
Abstract Understanding the relationship between urban form and structure and spatial inequality of property flood risk has been a longstanding challenge in urban planning and emergency management. Here we explore eight urban form and structure features to explain variability in spatial inequality of property flood risk among 2567 US counties. Using datasets related to human mobility and facility distribution, we identify notable variation in spatial inequality of property flood risk, particularly in coastline and metropolitan counties. The results reveal variations in spatial inequality of property flood risk can be explained based on principal components of development density, economic activity, and centrality and segregation. The classification and regression tree model further demonstrates how these principal components interact and form pathways that explain spatial inequality of property flood risk. The findings underscore the critical role of urban planning in mitigating flood risk inequality, offering valuable insights for crafting integrated strategies as urbanization progresses.

Natural and imposed injustices: the challenges in implementing 'fair' flood risk management policy in England - Johnson, Clare L.; Penning-Rowsell, Edmund C.; Parker, Dennis J. (The Geographical Journal, 2007)
This paper examines the challenges facing English flood risk management (FRM) policy and practice when considering fair decision-making processes and outcomes at a range of spatial scales. It is recognised that flooding is not fair per se : the inherent natural spatial inequality of flood frequency and extent, plus the legacy of differential system interventions, being the cause. But, drawing on the three social justice models – procedural equality, Rawls’ maximin rule and maximum utility – the authors examine the fairness principles currently employed in FRM decision-making. This is achieved, firstly, in relation to the distribution of taxpayer’s money for FRM at the national, regional and local levels and, secondly, for non-structural strategies – most notably those of insurance, flood warnings and awareness raising, land use control, home owner adaptation and emergency management. A case study of the Lower Thames catchment illustrates the challenges facing decision-makers in ‘real life’: how those strategies which appear to be most technically and economically effective fall far short of being fair from either a vulnerability or equality perspective. The paper concludes that if we are to manage flood risk somewhat more fairly then a move in the direction of government funding of nationally consistent non-structural strategies, in conjunction with lower investment decision thresholds for other local-level FRM options, appears to offer a greater contribution to equality and vulnerability-based social justice principles than the status quo.

Turkmen women’s traditional craft skills in post-disaster recovery: the case of the 2019 Northeast floods in Iran - Hassani, Atoosa; Fayazi, Mahmood; Mottaki, Zoheir; Adib, Morteza; Dehbandi, Ramin; Khalili Gheidari, Yasamam; Seraji, Fatemeh (Disaster Prevention and Management: An International Journal, 2025)
Purpose This study investigates why Turkmen women’s traditional handicraft skills have declined and explains how the local, traditional craft skills accelerated the post-flood recovery of Turkmen women in the aftermath of the 2019 Northeast floods in Iran. Design/methodology/approach The research adopts a case study approach, employing reflective thematic analysis. Findings Post-disaster recovery spurred a shift from traditional to modern lifestyles through new housing designs, enhanced female literacy and greater economic participation. However, this transition devalued traditional crafts due to heightened household chores, material scarcity and reduced market demand. Nonetheless, women with craft skills played a pivotal role in household recovery by repairing damaged items and crafting dowries for their daughters, illustrating their contribution to social and economic resilience. Social implications These research findings shed light on the importance of traditional craft skills in enabling the female household member, in particular, to recover from disasters and contribute to the recovery of their households and communities. Originality/value The originality of this study lies in its focus on the specific context of Turkmen women’s traditional craft skills and their role in post-disaster recovery, particularly after the 2019 Northeast floods in Iran. While there is existing research on post-disaster recovery mechanisms, this study uniquely examines the under-researched impact of traditional craft skills on the recovery process, specifically for female household members.
Keywords: Infolettre; Infolettre_Fevrier_2025

Long-term consequences of flooding: a case study of the 2011 Queensland floods - Fitzgerald, Gerard; Toloo Sheikhzadeh Yazd, Sam; Baniahmadi, Sara; Crompton, David; Tong, Shilu (Australian Journal of Emergency Management, 2019)
Devastating floods in southeast Queensland in 2011 were the combination of flash flooding in the Lockyer Valley with riverine flooding in the Brisbane metropolitan area. While there is considerable information about the immediate impact on those affected, there is less understanding of the long-term health effects that follow such events. This study explored the perceptions of health effects and support received by people affected by the 2011 southeast Queensland flood six years after the event. A cross-sectional survey of 327 people was conducted in areas affected by the floods. The questionnaire sought information about the ongoing social, economic, demographic and self-declared physical and mental health effects. The data were analysed through comparison of those unaffected with those directly affected by the floods. Residents whose households were flooded were more likely to score their health negatively than non-affected residents and had higher reported rates of trauma, injury and mental illness. Twenty-six per cent of this group reported that they still experience some adverse health effects from the floods. Managing the long-term health implications of a flood-affected population is an important public policy task. Dissatisfaction with recovery operations and perceived injustices associated with insurance and compensation arrangements may aggravate health consequences. Early recognition and intervention may assist with reducing secondary effects.
Keywords: Ouvrage_Collectif_Numéro1

Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...

La portée et les limites des approches participatives pour la gestion intégrée des inondations - Massé, Simon; Buffin-Bélanger, Thomas; Biron, Pascale; Ruiz, Julie (Revue des sciences de l’eau, 2019)
La gestion intégrée des risques d’inondation (GIRI) fait appel à la coordination de tous les niveaux et secteurs du gouvernement et de la société civile. Afin de favoriser la responsabilisation et l’appropriation des plans de GIRI par les communautés, l’implication des acteurs non gouvernementaux et des citoyens est de plus en plus valorisée. D’abord, l’émergence des approches participatives est exacerbée par l’optimisme face à la possibilité d’améliorer substantiellement la qualité et la portée des décisions, de gérer les conflits, de faciliter l'implantation des mesures non structurelles et de renforcer les capacités sociales au sein des communautés. Toutefois, certains avancent que l'intégration des non-experts dans le processus décisionnel brime l'impartialité de la procédure technocratique et que leur manque d’intérêt et de compétences limite la portée des démarches participatives. Des lacunes dans la représentativité des parties prenantes affectées et concernées au sein des instances peuvent aussi biaiser les aboutissants de la participation. De plus, la réticence des autorités à partager le pouvoir décisionnel limite l’institutionnalisation des approches participatives, tandis que la rigidité de l’appareil gouvernemental freine les élans participatifs des collectivités. Considérant l’intérêt grandissant des chercheurs, des décideurs et de la société civile envers les approches participatives dans le contexte de la gestion des inondations, cet article propose une synthèse de la littérature pour démêler les principales retombées et les limites de la participation. , In order to promote community accountability for flood risks, the involvement of non-governmental actors and citizens is increasingly valued. The emergence of participatory approaches is consolidated by optimism about the possibility of improving the quality and scope of decisions, managing conflicts, facilitating the implementation of non-structural measures and strengthening social capacity within communities. However, some argue that the integration of non-experts undermines the impartiality of the decision-making process and that their lack of interest and expertise limits the scope of participatory approaches. Moreover, the authorities’ reluctance to share decision-making power limits the institutionalization of participatory approaches, whereas the rigidity of the governmental framework hampers participatory impulses within communities. Lack of stakeholder representativeness within the decision-making framework may also bias the outcome of participation. In addition, the reluctance of the authorities to share decision-making power limits the institutionalization of participatory approaches, while the rigidity of the government apparatus hinders the participatory momentum of communities. Considering the growing interest of researchers, policymakers and civil society in participatory approaches in the context of flood management, this article provides a synthesis of the literature to unravel the major benefits and limitations of participation.
Keywords: Ouvrage_Collectif_Numéro1

Défis de l’action intersectorielle et pistes de réflexion pour renforcer la concertation dans les milieux ruraux du Québec en contexte de pandémie - Richard, Julie; Bergeron, Dave A.; Lessard, Lily; Toupin, Isabelle; Ouellet, Nicole; Bédard, Emmanuelle (Global Health Promotion, 2021)
La présente pandémie nécessite le recours aux mécanismes qui favorisent l’action intersectorielle entre les autorités et les partenaires de différents secteurs de la santé et de la société civile pour coordonner et adapter la réponse socio-sanitaire en fonction des particularités des milieux et de l’évolution de la pandémie. Ce commentaire propose de mettre en lumière quelques défis qui se posent actuellement dans la mise en œuvre d’actions intersectorielles dans les milieux ruraux du Québec. Des pistes de réflexion en faveur du renforcement des mécanismes de concertation nécessaires à la gestion de la pandémie sont proposées.
Keywords: Lessard_Lily

Les stratégies d’intervention déployées lors des inondations de 2019 : le point de vue d’intervenants de première et de deuxième lignes sur les avenues prometteuses - Maltais, Danielle; Lansard, Anne-Lise; Généreux, Mélissa (2021)
Au printemps 2017 et 2019, plus 300 municipalités du Québec ont été confrontées à de graves inondations qui ont provoqué d’importants dommages aux propriétés, aux biens personnels de milliers de citoyens et à plusieurs infrastructures municipales. Dans le contexte des inondations de 2019, il faut toutefois souligner l’importante différence entre celles vécues par la municipalité de Sainte-Marthe-sur-le-Lac et celles survenues dans les autres municipalités du Québec. À Sainte-Marthe-sur-le-Lac, les inondations ont été soudaines, et rapides, car elles ont été provoquées par la rupture d’une digue. Ce sinistre, de nature anthropique, a occasionné la relocalisation d’urgence de plusieurs centaines de familles. Quant aux autres municipalités, c’est la crue printanière qui a généré des inondations fluviales, un sinistre de cause naturelle, dont l’ampleur et la durée ont dépassé les précédents évènements historiques, y compris ceux de 2017. Lors de ces inondations, les municipalités et divers partenaires gouvernementaux (CIUSSS/CISSS, MSP, SQ…) et certains organismes bénévoles en sécurité civile (Croix-Rouge Canadienne, Armée du Salut, Ambulance St-Jean, etc.), ont déployé leurs intervenants afin d’apporter leur aide et leur soutien aux municipalités et aux personnes sinistrées. Des centaines de policiers, pompiers, employés municipaux, gestionnaires, chefs d’équipe, militaires, intervenants psychosociaux, bénévoles spécialisés en recherche et sauvetage ou en soutien émotionnel ont alors travaillé sans relâche pour assurer la sécurité des personnes et des biens, mais pour aussi amortir, autant que possible, les impacts psychosociaux inévitablement causés par ce type de sinistre. Ce rapport synthèse présente le point de vue d’une centaine d’intervenants, provenant de différentes régions du Québec qui ont contribué à la gestion et la coordination des efforts pour orchestrer la réponse nécessaire lors des inondations de 2019. Ils ont été invités à documenter les stratégies mises en place à court et à moyen terme qui, selon leurs observations, ont contribué à : •Augmenter le sentiment de sécurité des sinistrés ; •Diminuer leur niveau d’anxiété et d’isolement ; et •Prévenir la détérioration de leur état de santé physique et psychologique.
Keywords: Généreux_Mélissa

The 2023 wildfire season in Québec: an overview of extreme conditions, impacts, lessons learned and considerations for the future - Boulanger, Yan; Arseneault, Dominique; Bélisle, Annie Claude; Bergeron, Yves; Boucher, Jonathan; Boucher, Yan; Danneyrolles, Victor; Erni, Sandy; Gachon, Philippe; Girardin, Martin P.; Grant, Eliane; Grondin, Pierre; et al. (Canadian Journal of Forest Research, 2024)
The 2023 wildfire season in Québec set records due to extreme warm and dry conditions, burning 4.5 million hectares and indicating persistent and escalating impacts associated with climate change. This study reviews the unusual weather conditions that led to the fires, discussing their extensive impacts on the forest sector, fire management, boreal caribou habitats, and particularly the profound effects on First Nation communities. The wildfires led to significant declines in forest productivity and timber supply, overwhelming fire management resources, and necessitating widespread evacuations. First Nation territories were dramatically altered, facing severe air quality issues and disruptions. While caribou impacts were modest across the province, the broader ecological, economical, and social repercussions were considerable. To mitigate future extreme wildfire seasons, the study suggests changes in forest management practices to increase forest resilience and resistance, adapting industrial structures to changes in wood type harvested, and enhancing fire suppression and risk management strategies. It calls for a comprehensive, unified approach to risk management that incorporates the lessons learned from the 2023 fire season and accounts for ongoing climate change. The studyunderscores the urgent need for detailed planning and proactive measures to reduce the growing risks and impacts of wildfires in a changing climate.
Keywords: Gachon_Philippe; Guillemette_Francois

Development of tree recruitment models for 10 species groups in the sugar maple-dominated mixed forests of eastern Canada - Rijal, Baburam; Power, Hugues; Auger, Isabelle; Guillemette, François; Bédard, Steve; Schneider, Robert (Canadian Journal of Forest Research, 2023)
Individual tree recruitment is an important element needed to understand stand dynamics, as it influences both stand composition and productivity. Forest growth simulators usually include recruitment models. The quality of recruitment predictions can have long-term impacts on estimations of forest growth, ecosystem health and the commercial utility of managed forests. The main objective of this study was to develop a recruitment model for commercial-size trees (i.e., trees with a diameter at breast height > 9 cm) of 10 species groups using different dendrometric and environmental variables. The resulting model will be included in a growth simulator used to support forest management planning. We hypothesized that accounting for sapling density as a covariate would improve the recruitment model's predictive performance. Using empirical data from periodically measured permanent sample plots (1982–2019) located throughout the managed mixed hardwood forests of Quebec, we constructed models with and without sapling-related covariates and compared them on the basis of cross-validation model performance statistics. Our results show that including sapling density significantly improved model performance. From this, we conclude that adding sapling density as a covariate can significantly improve a recruitment model's predictive power for eastern mixed hardwood forests.
Keywords: Guillemette_Francois

Supply and Transport Limitations on Phosphorus Losses from Agricultural Fields in the Lower Great Lakes Region, Canada - Plach, Janina M.; Macrae, Merrin L.; Ali, Genevieve A.; Brunke, Richard R.; English, Michael C.; Ferguson, Gabrielle; Lam, W. Vito; Lozier, Tatianna M.; McKague, Kevin; O'Halloran, Ivan P.; Opolko, Gilian; Van Esbroeck, Christopher J. (Journal of Environmental Quality, 2018)
Phosphorus (P) mobilization in agricultural landscapes is regulated by both hydrologic (transport) and biogeochemical (supply) processes interacting within soils; however, the dominance of these controls can vary spatially and temporally. In this study, we analyzed a 5‐yr dataset of stormflow events across nine agricultural fields in the lower Great Lakes region of Ontario, Canada, to determine if edge‐of‐field surface runoff and tile drainage losses (total and dissolved reactive P) were limited by transport mechanisms or P supply. Field sites ranged from clay loam, silt loam, to sandy loam textures. Findings indicate that biogeochemical processes (P supply) were more important for tile drain P loading patterns (i.e., variable flow‐weighted mean concentrations ([ C f ]) across a range of flow regimes) relative to surface runoff, which trended toward a more chemostatic or transport‐limited response. At two sites with the same soil texture, higher tile [ C f ] and greater transport limitations were apparent at the site with higher soil available P (STP); however, STP did not significantly correlate with tile [ C f ] or P loading patterns across the nine sites. This may reflect that the fields were all within a narrow STP range and were not elevated in STP concentrations (Olsen‐P, ≤25 mg kg −1 ). For the study sites where STP was maintained at reasonable concentrations, hydrology was less of a driving factor for tile P loadings, and thus management strategies that limit P supply may be an effective way to reduce P losses from fields (e.g., timing of fertilizer application). Core Ideas We used metrics to evaluate controls on edge‐of‐field phosphorus losses. We examined a 5‐yr database of stormflow events (all seasons, including winter). Tile P runoff trended toward being more supply limited than surface runoff.

Changes in floodplain regimes over Canada due to climate change impacts: Observations from CMIP6 models - Mohanty, Mohit Prakash; Simonovic, Slobodan P. (Science of The Total Environment, 2021)
Abstract With the recent Coupled Model Intercomparison Project Phase 6 (CMIP6), water experts and flood modellers are curious to explore the efficacy of the new and upgraded climate models in representing flood inundation dynamics and how they will be impacted in the future by climate change. In this study, for the first time, we consider the latest group of General Circulation Models (GCMs) from CMIP6 to examine the probable changes in floodplain regimes over Canada. A set of 17 GCMs from Shared Socioeconomic Pathways (SSPs) 4.5 (medium forcing) and 8.5 (high end forcing) common to historical (1980 to 2019), near-future (2021 to 2060), and far-future (2061 to 2100) time-periods are selected. A comprehensive framework consisting of hydrodynamic flood modelling, and statistical experiments are put forward to derive high-resolution Canada-wide floodplain maps for 100 and 200-yr return periods. The changes in floodplain regimes for the future periods are analyzed over drainage basin scale in terms of (i) changes in flood inundation extents, (ii) changes in flood hazards (high and very-high classes), and (iii) changes in flood frequency. Our results show a significant rise (>30%) in flood inundation extents in the future periods; particularly intense over western and eastern regions. The flood hazards are expected to cover ~16% more geographical area of Canada. We also find that large areas in northern and western Canada and a few spots in the eastern parts of Canada will be getting flooded more frequently compared to the historical period. The observations derived from this study are vital for enhancing flood preparedness, optimal land-use planning, and refurbishing both structural and non-structural flood control options for improved resilience. The study instills new knowledge on revamping the existing flood management approaches and adaptation strategies for future protection.

A Comprehensive Approach for Floodplain Mapping Through Identification of Hazard Using Publicly Available Data Sets Over Canada - Mohanty, M.P.P; Simonovic, Slobodan P. (2022)
Flood events and their associated damages have escalated significantly in the last few decades. To add to the gruesome situation, many reports and studies warn that flood risk would aggravate significantly in future periods due to significant alterations in the climate patterns and socio-economic dynamics. Floodplain mapping is looked upon as a viable option to tackle this global issue as it provides both quantitative and qualitative information on flood dynamics. Moreover, with the increasing availability of global data and enhancement in computational simulations, it has become easier to simlate flooding patterns at large scales. This study deter-mines the usability of publicly available datasets in capturing flood hazards over Canada. Run-off data set from the North American Regional Reanalysis (NARR), along with a few other rele-vant inputs are fed to CaMa-Flood, a robust global hydrodynamic model to generate flooding patterns for 1 in 100 and 1 in 200-yr return period events over Canada . The simulated maps are compared and validated with the existing maps of a few flood-prone regions in Canada, thereby establishing their performance over both regional and country-scale. Later, the simulated flood-plain maps are used in conjunction with property related information at 34 cities (within the top 100 populous cities in Canada) to determine the degree of exposure due to flooding in 1991, 2001, and 2011. The results indicate that around 80 percent of inundated spots belong to high and very-high hazard classes in a 200-yr event, which is roughly 4 percent more than simulated for 100-yr event. NARR derived floodplain maps perform very well while compared over the six flood-prone regions. While analyzing the exposure of properties to flooding, we notice an in-crease in the number during the last three decades, with the maximum rise observed in Toronto, followed by Montreal, and Edmonton. To disseminate the extensive flood-related information, a web-based public tool, Flood Map Viewer (http://www.floodmapviewer.com/) is developed. The development of the tool was motivated by the commitment of the Canadian government to provide $63 M over the next three years for the completion of flood maps for higher-risk areas. The study reaches out to demonstrate how publicly available datasets can be utilized with a lesser degree of uncertainty in representing flooding patterns over large regions. The flood re-lated information derived from the study can be used along with vulnerability for quantifying flood risk, which will help in developing appropriate pathways for resilience building for long-term sustainable benefits.

Using the theory of planned behavior to identify key beliefs underlying flood-related adaptive behaviors in the province of Québec, Canada - Jacob, Johann; Valois, Pierre; Tessier, Maxime; Talbot, Denis; Anctil, François; Cloutier, Geneviève; Renaud, Jean-Sébastien (Journal of Flood Risk Management, 2023)
Given that flooding episodes are occurring at a greater rate due to climate change, individuals must adopt certain adaptation behaviors to prevent or mitigate the anticipated or negative impact of such events. However, few studies have assessed if and how households and individuals have actually taken action in this regard. Because some individual beliefs can be linked to facilitating factors and barriers to action, a better understanding of the adoption of adaptive behaviors requires a combined analysis of individual psychosocial factors. The purpose of this study was to develop a better understanding of the reasons underlying the adoption of behaviors related to structural adaptation to flooding by people living in or near flood-prone areas in the Province of Québec (Canada). Results of a series of structural equation modeling showed that behavioral, normative and control beliefs were all significant predictors of the respondents' intention to adopt structural flood protective behaviors, with normative beliefs being the strongest. By identifying the best psychosocial predictors of the adoption of such behaviors, the results of this study provide valuable insights regarding the most effective factors to be used in public health messages to promote the adoption of behaviors related to structural adaptation to flooding.
Keywords: Infolettre; Infolettre_Mai_2023

Morphological and Habitat Quality of Salmonid Streams and their Relationship with Fish-Based Indices in Aotearoa New Zealand and Ontario (Canada) - Foote, Kyleisha J.; Biron, Pascale M.; Grant, James W. A. (Environmental Management, 2024)
Keywords: Infolettre; Infolettre_Janvier_2024

La réduction des risques de désastres : défis et possibilités pour le Québec et le Canada. Université du Québec à Montréal, Chaire de recherche UQAM sur les risques hydrométéorologiques liés aux changements climatiques - Boyer-Villemaire, U.; Gachon, P.; Boucher, E.; Germain, D.; Raphoz, M.; Doré, M. C.; Martin, J. P. (2017)
En marge de la Cinquième Plateforme régionale pour la Réduction des risques de catastrophes des Amériques (PRA), le gouvernement du Canada a approché l’Institut des sciences de l’environnement(ISE) de l’Université du Québec à Montréal(UQAM) afin d’organiser un forum public. Les échanges de ce dernier devaient servir à alimenter les discussions de la PRA. Au total, 21 experts ont discuté avec une centaine de participants lors de panels organisés à l’UQAM sous les thèmes de la santé, de la sécurité civile et de l’aménagement du territoire. Plusieurs thèmes transversaux ont aussi émergé tout au long du forum. Il importe de pérenniser le rôle de la recherche et d’améliorer les capacités de formation technique et universitaire afin de former des spécialistes en mesure d’appréhender la complexité de la gestion du risque dans un contexte de changements environnementaux et climatiques. Ceci est également essentiel pour l’identification des facteurs de risque (multisources ou multidimensionnels), pour tirer des leçons apprises des événements majeurs passés et récents, et pour développer ou mettre à jour la connaissance sur les tendances en cours et à venir des aléas météorologiques, ainsi que des facteurs de vulnérabilité et d’exposition. Tous les panels ont discuté de l’importance de favoriser le décloisonnement intra/interorganisationnel pour promouvoir la transsectorialité et les retours d’expériences systématiques. Pour ce faire, il faut s’inspirer des modèles internationaux, notamment du système d’alertes hydrométéorologiques présenté par Météo-France. Celui-ci inclut une vigilance météorologique qui cible des populations et des autorités publiques, et les informe des comportements et des règles à suivre lors d’alertes plus problématiques (vigilance aux stades orange et rouge). Finalement, l’amélioration de la communication et le libre accès à l’information sont des éléments essentiels pour protéger les individus et développer une société plus résiliente.
Keywords: Gachon_Philippe

Exploring local risk managers' use of flood hazard maps for risk communication purposes in Baden-Württemberg - Kjellgren, S. (Natural Hazards and Earth System Sciences, 2013)
Abstract. In response to the EU Floods Directive (2007/60/EC), flood hazard maps are currently produced all over Europe, reflecting a wider shift in focus from "flood protection" to "risk management", for which not only public authorities but also populations at risk are seen as responsible. By providing a visual image of the foreseen consequences of flooding, flood hazard maps can enhance people's knowledge about flood risk, making them more capable of an adequate response. Current literature, however, questions the maps' awareness raising capacity, arguing that their content and design are rarely adjusted to laypeople's needs. This paper wants to complement this perspective with a focus on risk communication by studying how these tools are disseminated and marketed to the public in the first place. Judging from communication theory, simply making hazard maps publicly available is unlikely to lead to attitudinal or behavioral effects, since this typically requires two-way communication and material or symbolic incentives. Consequently, it is relevant to investigate whether and how local risk managers, who are well positioned to interact with the local population, make use of flood hazard maps for risk communication purposes. A qualitative case study of this issue in the German state of Baden-Württemberg suggests that many municipalities lack a clear strategy for using this new information tool for hazard and risk communication. Four barriers in this regard are identified: perceived disinterest/sufficient awareness on behalf of the population at risk; unwillingness to cause worry or distress; lack of skills and resources; and insufficient support. These barriers are important to address – in research as well as in practice – since it is only if flood hazard maps are used to enhance local knowledge resources that they can be expected to contribute to social capacity building.
Keywords: Ouvrage_Collectif_Numéro1

Standardised indicators for “resilient cities”: the folly of devising a technical solution to a political problem - Chmutina, Ksenia; Lizarralde, Gonzalo; Von Meding, Jason; Bosher, Lee (International Journal of Disaster Resilience in the Built Environment, 2023)
Purpose Driven by the New Urban Agenda and the Sustainable Development Goals, decision makers have been striving to reorientate policy debates towards the aspiration of achieving urban resilience and monitoring the effectiveness of adaptive measures through the implementation of standardised indicators. Consequently, there has been a rise of indicator systems measuring resilience. This paper aims to argue that the ambition of making cities resilient does not always make them less vulnerable, more habitable, equitable and just. Design/methodology/approach Using an inductive policy analysis of ISO standard 37123:2019 “Sustainable cities and communities — Indicators for resilient cities”, the authors examine the extent to which the root causes of risks are being addressed by the urban resilience agenda. Findings The authors show that the current standardisation of resilience fails to adequately address the political dimension of disaster risk reduction, reducing resilience to a management tool and missing the opportunity to address the socio-political sources of risks. Originality/value Such critical analysis of the Standard is important as it moves away from a hazard-centric approach and, instead, permits to shed light on the socio-political processes of risk creation and to adopt a more nuanced and sensitive understanding of urban characteristics and governance mechanisms.
Keywords: Infolettre; Infolettre_Juin_2023; Lizarralde_Gonzalo

Pratiques et approches déployées pour la prévention des risques liés aux inondations au Québec : Le cas des territoires concernés par les inondations du lac des Deux Montagnes - Fournier, Catherine (Université du Québec, Institut national de la recherche scientifique, 2022)
Les politiques québécoises de prévention des risques liés aux inondations ont été sujettes à débat ces dernières années, avec une remise en cause du modèle centralisé et uniforme à travers le Québec, pour une approche plus intégrée. Celle-ci fait notamment la promotion de mesures axées sur la vulnérabilité et d’une participation plus active des acteurs territoriaux. On en sait toutefois très peu sur les déclinaisons locales de l’approche intégrée dans le contexte québécois. Ce mémoire propose d’interroger les différentes approches locales de la prévention et de soulever les enjeux qu’elles posent du point de vue des autorités qui y participent. L’étude se penche sur le cas des territoires concernés par les inondations du lac des Deux Montagnes (Région hydrographique de l'Outaouais et de Montréal). Le cadre d’analyse met de l’avant l’approche des instruments d’action publique pour comprendre leur appropriation par les acteurs locaux et une approche pragmatique qui consiste à centrer notre regard sur les pratiques et les stratégies de réduction des risques d’inondation. La recherche s’appuie sur trois sources de données : une analyse documentaire des régimes provinciaux de régulation des risques d’inondation, un recensement des pratiques de prévention déployées par les autorités locales concernées par les inondations du lac des Deux Montagnes et une série de 15 entretiens réalisés avec les personnes travaillant au sein de ces différentes autorités. Le cas illustre la difficulté et le faible engagement de prévenir les risques autrement que par l’approche de réduction de l’exposition aux risques imposée par la Politique de protection des rives, du littoral et des plaines inondables (PPRLPI). Toutefois, après les inondations de 2017 et de 2019, des approches alternatives propres aux contextes territoriaux ont été envisagées par différentes organisations. Celles-ci devraient davantage être documentées et mises en débat afin d’envisager un régime provincial de la gestion des risques plus flexible et ouvert à leur coexistence. Uniformed and centralized model of Quebec's flood prevention policies have been recently debated. Integrated approach to flood risk prevention is now put forward, which focus more on vulnerability and foster an active participation of local authorities. Local declinations of the approach are relatively unknown in Quebec. This study presents different local approaches to flood risk prevention and raise issues they pose from the perspective of local authorities involved. It is based on the authority’s concerns by Lac des Deux Montagnes flooding (Outaouais and Montreal hydrographic region). Combining a political sociology approach to policy instruments and a pragmatic approach, we focus on risk regulation regimes, practices and risk reduction strategies. Three sources of data were used: an analysis of flood risk regulation regimes, an inventory of prevention practices deployed by local authorities and 15 interviews conducted with professionals among these authorities. Results show the difficulty and low commitment to implement local distinct approaches apart from prohibiting and discouraging exposure to flood risk enforced by the Protection Policy for Lakeshores, Riverbanks, Littoral Zones and Floodplains. However, after the floods of 2017 and 2019, alternative strategies specific to different territorial contexts were considered. These should be better documented and debated in order to consider a more flexible and coexistence provincial policy.
Keywords: Site_internet_RIISQ

Urban flood resilience, a multi-level institutional analysis of planning practices in the Metropolitan City of Naples - Vitale, Corinne; Meijerink, Sander; Moccia, Francesco Domenico (Journal of Environmental Planning and Management, 2023)
Keywords: Ouvrage_Collectif_Numéro1

Disrupting the riskscapes of inequities: a case study of planning for resilience in Canada’s Metro Vancouver region - Yumagulova, Lilia (Cambridge Journal of Regions, Economy and Society, 2020)
Abstract The analysis across spatial, temporal and governance scales shows an inequitable distribution of risk across Canada’s Metro Vancouver region. For First Nation communities in this region, this risk is rooted in the colonial history of land dispossession. This article makes a contribution by expanding our understanding of historic creation of riskscapes and a discussion of its implications as a multiscale governance issue that persists across space and time. This article also situates the impacts of projected sea level rise on Indigenous communities in the context of regional, provincial and federal settler-colonial flood risk management regime.

Justice and Resilience in Flood Risk Management: What Are the Socio-Political Implications? - Thaler, Thomas (2021)
Flood risk management requires to comprehensively assess how policy strategies may affect individuals and communities. However, policy development and implementation often downplay or even increase social inequality. Analysis of the social and societal implications of strategies and implementation projects to manage flood hazards is still in its infancy. To close this gap, this chapter critically questions the roles of social justice and their political implications for flood risk management with regard to resilience. The chapter discusses and argues how different theoretical concepts as well as different perspectives on justice (e.g. social, environmental and climate justice) and resilience in flood risk management are related. There is a strong need to have a broader and more in-depth discussion about the role of justice in the current resilience debate. Finally, the chapter presents the outline of a future research agenda.

Assessment of the Dynamics towards Effective and Efficient Post-Flood Disaster Adaptive Capacity and Resilience in South Africa - Nyide, Sindisiwe; Simatele, Mulala Danny; Grab, Stefan; Adom, Richard Kwame (2023)
Government employees, municipal officials, and communities in South Africa have grappled with post-apartheid environmental challenges, such as floods, droughts, severe storms, and wildfires. These disasters are a result of both natural and human activities. The government implemented different policies and strategies after 1994 to address these issues. While acknowledging some success in managing these disasters with the current adaptive measures, the frequency and intensity of disasters have increased, causing significant damage to life and property, particularly among the vulnerable population. This paper uses qualitative and quantitative data collection approaches to explore possible systematic and structural weaknesses in addressing post-disaster situations in South Africa. Floods appear to be the most frequent natural disaster in South Africa. The paper uncovered the fact that disaster management is a multi-sectoral and multidisciplinary field. Although various institutional arrangements exist, they do not seem appropriate for assisting vulnerable groups. While officials have made some progress in implementing post-disaster projects, challenges still hinder sustainability. Furthermore, regrettably, despite the level of success in addressing disasters, most measures have failed to achieve the intended results for a variety of reasons. The consolidated long-term measures suggested by the participants yielded a proposed ‘South African Floods Post-Disaster Checklist or Model’, which was non-existent in South Africa. By implementing more effective and efficient post-disaster measures, the proposed tool can help policymakers and strategic partners standardise post-disaster resilience and adaptive capacity in various sectors’ sustainability contexts.

Programme de résilience et d’adaptation face aux inondations (PRAFI) – volet Aménagements résilients - Ministère des Affaires municipales et de l’Habitation (MAMH) (Gouvernement du Québec., 2020)
Keywords: Ouvrage_Collectif_Numéro1

Dependence of tropical cyclone damage on maximum wind speed and socioeconomic factors - Ye, Mengqi; Wu, Jidong; Liu, Wenhui; He, Xin; Wang, Cailin (Environmental Research Letters, 2020)
© 2020 The Author(s). Published by IOP Publishing Ltd.Tropical cyclones (TCs) have devastating impacts and are responsible for significant damage. Consequently, for TC-induced direct economic loss (DEL) attribution all factors associated with risk (i.e. hazard, exposure and vulnerability) must be examined. This research quantifies the relationship between TC-induced DELs and maximum wind speed, asset value and Gross Domestic Product (GDP) per capita using a regression model with TC records from 2000 to 2015 for China's mainland area. The coefficient of the maximum wind speed term indicates that a doubling of the maximum wind speed increases DELs by 225% [97%, 435%] when the other two variables are held constant. The coefficient of the asset value term indicates that a doubling of asset value exposed to TCs increases DELs by 79% [58%, 103%]; thus, if hazard and vulnerability are assumed to be constant in the future, then a dramatic escalation in TC-induced DELs will occur given the increase in asset value, suggesting that TC-prone areas with rapid urbanization and wealth accumulation will inevitably be subject to higher risk. Reducing the asset value exposure via land-use planning, for example, is important for decreasing TC risk. The coefficient of GDP per capita term indicates that a doubling in GDP per capita could decrease DELs by 54% [39%, 66%]. Because accumulated assets constantly increase people's demand for improved security, stakeholders must invest in risk identification, early warning systems, emergency management and other effective prevention measures with increasing income to reduce vulnerability. This research aims to quantitatively connect TC risk (expected DELs, specifically) to physical and socioeconomic drivers and emphasizes how human dimensions could contribute to TC risk. Moreover, the model can be used to estimate TC risk under climate change and future socioeconomic development in the context of China.

Vulnerable Waters are Essential to Watershed Resilience - Lane, Charles R.; Creed, Irena F.; Golden, Heather E.; Leibowitz, Scott G.; Mushet, David M.; Rains, Mark C.; Wu, Qiusheng; D’Amico, Ellen; Alexander, Laurie C.; Ali, Genevieve A.; Basu, Nandita B.; Bennett, Micah G.; et al. (Ecosystems, 2023)
Abstract Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Urban resilience implementation: A policy challenge and research agenda for the 21st century - Coaffee, Jon; Therrien, Marie‐Christine; Chelleri, Lorenzo; Henstra, Daniel; Aldrich, Daniel P.; Mitchell, Carrie L.; Tsenkova, Sasha; Rigaud, Éric; the participants (Journal of Contingencies and Crisis Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Risk and Resilience: A Case of Perception versus Reality in Flood Management - Agrawal, Nirupama; Elliott, Mark; Simonovic, Slobodan P. (Water, 2020)
Canada’s vast regions are reacting to climate change in uncertain ways. Understanding of local disaster risks and knowledge of underlying causes for negative impacts of disasters are critical factors to working toward a resilient environment across the social, economic, and the built sectors. Historically, floods have caused more economical and social damage around the world than other types of natural hazards. Since the 1900s, the most frequent hazards in Canada have been floods, wildfire, drought, and extreme cold, in terms of economic damage. The recent flood events in the Canadian provinces of Ontario, New Brunswick, Quebec, Alberta, and Manitoba have raised compelling concerns. These include should communities be educated with useful knowledge on hazard risk and resilience so they would be interested in the discussion on the vital role they can play in building resilience in their communities. Increasing awareness that perceived risk can be very different from the real threat is the motivation behind this study. The main objectives of this study include identifying and quantifying the gap between people’s perception of exposure and susceptibility to the risk and a lack of coping capacity and objective assessment of risk and resilience, as well as estimating an integrated measure of disaster resilience in a community. The proposed method has been applied to floods as an example, using actual data on the geomorphology of the study area, including terrain and low lying regions. It is hoped that the study will encourage a broader debate if a unified strategy for disaster resilience would be feasible and beneficial in Canada.

Paradoxes of financial schemes for resilient flood recovery of households - Slavíková, Lenka; Hartmann, Thomas; Thaler, Thomas (Wiley Interdisciplinary Reviews: Water, 2020)
Flood resilience (resilient flood risk management), which has been repeatedly demanded, can be achieved through the phases of the risk management cycle. There is a vast body of literature on adaptation, disaster risk reduction measures, and effectiveness of prevention, seen through the lens of postdisaster recovery, but oftentimes the existing literature seems to underestimate the impact of financial flood recovery schemes on resilient recovery of individual households in particular. This contribution focuses on how financial schemes for flood damage compensations—their sources, design, and timing—shape the resilience of recovery of individual households. It discusses the dilemma of recovery of whether recovery schemes should be used strategically to increase resilience, or rather serve early restoration needs, equality access issues, and so on. This contribution seeks to unify the current fragmented academic debate on household resilient recovery by focusing on the ambiguous role of financial recovery schemes. This article is categorized under: Engineering Water > Planning Water Human Water > Value of Water.

Snow particles physiochemistry: feedback on air quality, climate change, and human health - Rangel-Alvarado, Rodrigo; Li, Houjie; Ariya, Parisa A. (Environmental Science: Atmospheres, 2022)
During the last several decades, numerous researchers have provided evidence that physical and biogeochemical processes at air-snow/ice-water interfaces are very complex, and, in many cases, interlinked. , During the last several decades, numerous researchers have provided evidence that physical and biogeochemical processes at air-snow/ice-water interfaces are very complex, and, in many cases, interlinked. This review focuses on the current state of knowledge regarding snow-borne particles. It integrates snow science from different angles: from the formation of snow and precipitation to transformations through natural and anthropogenic processes and impacts and snow management in urban areas sites. We discuss the physical, chemical, and biological characteristics of particles in snow, such as their composition, abundance, size distribution, ice nucleation properties, genomic features, and microphysical processes, in urban settings, remote areas of the Arctic, and remote industrial regions (oil sands). We explore physicochemical processes of snow particles: from microbial to emerging contaminants, like nano/microplastics, light-absorbing carbonaceous organics, halogenated and nanometals particles. We review the possible contributions of snow particles to atmospheric radiation and climate, biogeochemistry, human health, and urban snow management. We propose further research directions to improve understanding of air-snow feedback, and sustainable snow management in urban areas, in the age of emerging contaminants in a changing climate.

Modeling the Impacts of Urban Flood Risk Management on Social Inequality - Moulds, Simon; Buytaert, Wouter; Templeton, Michael R.; Kanu, Ishmael (Water Resources Research, 2021)
Abstract The exposure of urban populations to flooding is highly heterogeneous, with the negative impacts of flooding experienced disproportionately by the poor. In developing countries experiencing rapid urbanization and population growth a key distinction in the urban landscape is between planned development and unplanned, informal development, which often occurs on marginal, flood‐prone land. Flood risk management in the context of informality is challenging, and may exacerbate existing social inequalities and entrench poverty. Here, we adapt an existing socio‐hydrological model of human‐flood interactions to account for a stratified urban society consisting of planned and informal settlements. In the first instance, we use the model to construct four system archetypes based on idealized scenarios of risk reduction and disaster recovery. We then perform a sensitivity analysis to examine the relative importance of the differential values of vulnerability, risk‐aversion, and flood awareness in determining the relationship between flood risk management and social inequality. The model results suggest that reducing the vulnerability of informal communities to flooding plays an important role in reducing social inequality and enabling sustainable economic growth, even when the exposure to the flood hazard remains high. Conversely, our model shows that increasing risk aversion may accelerate the decline of informal communities by suppressing economic growth. On this basis, we argue for urban flood risk management which is rooted in pro‐poor urban governance and planning agendas which recognize the legitimacy and permanence of informal communities in cities. , Key Points The distribution of flood risk in urban areas is uneven, with the negative impacts experienced disproportionately by the urban poor Our model shows that reducing the vulnerability of informal residents to flooding can reduce inequality, even when their exposure is high Based on the model results, we argue that urban flood risk management should be rooted in pro‐poor urban governance and planning agendas

Advancing Performance Measurement for Public Health Emergency Preparedness: An Integrated Knowledge Translation Approach - Khan, Yasmin; O’Sullivan, Tracey; Brown, Adalsteinn; Gibson, Jennifer; Henry, Bonnie; Généreux, Mélissa; Schwartz, Brian (Prehospital and Disaster Medicine, 2019)
Introduction:Public health emergency management involves the timely translation of relevant evidence and effective coordination of diverse actors. In practice, this can be challenging in the absence of a common framework for action among diverse actors.Aim:To apply an Integrated Knowledge Translation (iKT) approach throughout the development of a conceptual framework and performance measurement indicators for public health emergency preparedness (PHEP), to ensure knowledge generated is relevant and useful to the field.Methods:The iKT approach was initiated by identifying a research question based on priorities from the field. The two phases of the study used participatory research methods as well as active engagement with potential end users at key study milestones. The Structured Interview Matrix (SIM) facilitation technique for focus groups and an expert panel using Delphi methodology were used to define the PHEP framework and performance measurement indicators, respectively. An advisory committee was assembled consisting of potential end-users of the research, in senior positions in applied and decision-making roles.Results:iKT was an essential component for this applied public health project, contributing to and enhancing the relevance of the knowledge generated. iKT contributed to the following: broad national engagement and interest in the study, successful recruitment in both phases, and engagement with decision-makers. This multi-dimensional participatory approach successfully generated knowledge that was important to the field demonstrated by relevance to practice and policy in jurisdictions across Canada. Furthermore, the approach fostered building resilience in local and national communities through collaboration.Discussion:The iKT approach was essential to generating knowledge that is relevant and useful to the field, mainly to promote health system preparedness and resilience. Future research to study the implementation of knowledge will be important to continue addressing the knowledge-to-action gap in health emergency management research.
Keywords: Généreux_Mélissa

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ

Intersectoral research and multi-risk approaches in Québec: systemic risk management and its psychosocial consequences - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Contribution paper to the Global Assessment Report on Disaster Risk Reduction, 2022)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Lessard_Lily; Site_internet_RIISQ

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Psychosocial Management Before, During, and After Emergencies and Disasters—Results from the Kobe Expert Meeting - Généreux, Mélissa; Schluter, Philip J.; Takahashi, Sho; Usami, Shiori; Mashino, Sonoe; Kayano, Ryoma; Kim, Yoshiharu (International Journal of Environmental Research and Public Health, 2019)
Emergencies and disasters typically affect entire communities, cause substantial losses and disruption, and result in a significant and persistent mental health burden. There is currently a paucity of evidence on safe and effective individual- and community-level strategies for improving mental health before, during, and after such events. In October 2018, the World Health Organization (WHO) Centre for Health Development (WHO Kobe Centre) convened a meeting bringing together leading Asia Pacific and international disaster research experts. The expert meeting identified key research needs in five major areas, one being “Psychosocial management before, during, and after emergencies and disasters”. Experts for this research area identified critical gaps in observational research (i.e., the monitoring of long-term psychological consequences) and interventional research (i.e., the development and evaluation of individual- and community-level interventions). Three key research issues were identified. First, experts underscored the need for a standardized and psychometrically robust instrument that classified the mental health/psychosocial risk of people within both a clinical and community setting. Then, the need for a standardization of methods for prevention, screening, diagnosis, and treatment for affected people was highlighted. Finally, experts called for a better identification of before, during, and after emergency or disaster assets associated with greater community resilience.
Keywords: Généreux_Mélissa

B’ the Change you Want to See: How Commensurating Water Health Impedes Collective Action - Couture, Fannie; Le, Jane Kirsten (Academy of Management Proceedings, 2023)

Health Effect on and Adaptation of the Elderly Affected by Floods - Chompunud, Somjinda; Inkaew, Wanpen (Health Emergency and Disaster Nursing, 2019)
Aim: The aim of the study was to investigate the health effect on and adaptation of the elderly affected by floods in the Lat Krabang District, Bangkok, Thailand in 2011.Methods: A cross-sectional descriptive study was conducted. Data were collected from 290 elderly participants who were affected by the floods using questionnaires.Results: The elderly participants had previous experience with flooding, but the massive flooding in 2011 was the most severe compared to any other experiences in the past. Physical health effects included muscle pain (35.2%), athlete’s foot (28.3%), and skin rash (23.1%). The psychological health effects (24.3%) encountered included insomnia, constant stress and tension, attention deficit, and discontentment. Most elderly (89.3%) decided not to relocate thinking they could still live at home, but they were concerned about the safety of their property. In regards to preparation for the flood, they prepared consumer goods, medication, and emergency kits. In addition, they kept abreast with news on television and public announcements in the community. They also helped clear the drainage system and prepared contact information of children, relatives, and government offices in case they needed assistance. Finally, to reduce possible damage to the property, they moved their belongings to high places, built sandbag walls, raised the house level, and prepared a water pump.Conclusion: The 2011 Thailand floods had adverse effects on physical and psychological health of the elderly people. To ensure better management for this vulnerable group, plans to respond to possible disasters need to be devised by relevant agencies to reduce flood-related health impacts.
Keywords: Ouvrage_Collectif_Numéro1; adaptation; elderly; flood; health effect

La réforme Barrette et sa mise en oeuvre dans les services sociaux : perceptions des travailleuses sociales - Bourque, Mélanie; Barbe, Mylène; Leroux, Maxime; Grenier, Josée; St-Amour, Nathalie (Intervention, 2024)
Cet article vise à partager les résultats préliminaires du projet de recherche « Les travailleuses sociales cinq ans après l’implantation de la réforme Barrette : standardisation de la pratique ou nouvelles normes locales des établissements? ». Ce projet de recherche a pour but de mieux comprendre la mise en oeuvre de la réforme du système de santé et des services sociaux de 2015 au Québec. De juin à décembre 2022, près de 60 personnes participantes ont accepté de répondre à un entretien semi-dirigé. La très grande majorité d’entre elles détiennent plus de dix ans d’expérience, ce qui permet de comprendre l’avant et l’après réforme Barrette et de saisir les effets de cette réforme sur les équipes de travail, mais aussi sur la prestation des services fournis à la population. L’analyse initiale des données met en lumière la poursuite, voire l’accentuation, de la perspective descendante (top down) du processus décisionnel, de la reddition de comptes par le biais de mesures quantitatives et de l’harmonisation des services s’illustrant en standardisation des pratiques, en dépit des particularités territoriales inhérentes aux différentes régions du Québec. Par rapport à notre recherche précédente, force est de constater que les méthodes de la nouvelle gestion publique se sont accentuées au sein du réseau de la santé et des services sociaux, qualifié de « maison des fous » par plusieurs personnes participantes.
Keywords: StAmour_Nathalie

La santé des Canadiens et des Canadiennes dans un climat en changement. Faire progresser nos connaissances pour agir - Berry, Peter; Blagden, Phil; Campagna, Céline; Egyed, Marika; Gosselin, Pierre; Harper, Sherilee; Hayes, Katie; Ogden, Nicholas; Schnitter, Rebekka; Takaro, Tim (Ottawa (Ontario), gouvernement du Canada, 2022)

Mental health and retirement savings: Confounding issues with compounding interest - Bogan, Vicki L.; Fertig, Angela R. (Health Economics, 2018)
Summary The questionable ability of the U.S. pension system to provide for the growing elderly population combined with the rising number of people affected by depression and other mental health issues magnifies the need to understand how these household characteristics affect retirement. Mental health problems have a large and significant negative effect on retirement savings. Specifically, psychological distress is associated with decreasing the probability of holding retirement accounts by as much as 24 percentage points and decreasing retirement savings as a share of financial assets by as much as 67 percentage points. The magnitude of these effects underscores the importance of employer management policy and government regulation of these accounts to help ensure households have adequate retirement savings.
Keywords: Ouvrage_Collectif_Numéro1

From Policy Challenge to Implementation Strategy: Enabling Strategies for Network Governance of Urban Resilience - Therrien, Marie‐Christine; Normandin, Julie‐Maude (Risk, Hazards & Crisis in Public Policy, 2020)
What transformations do municipal administrations implement to enact a resilience policy? This article responds to this question from a comparative perspective by analyzing enabling and impeding mechanisms developed in the cities of Montreal (Canada) and London (UK) as they establish their strategies. Collaborative network governance and institutional work mechanisms used in Montreal and London are analyzed in connection with the influence of macro‐ and micro‐contextual elements under which a network can resiliently manage risk and crises. In both cases, the development of resilience emerges from their emergency management structures, as units in charge try to animate their new area of responsibility through collaborative governance. As a siloed approach this is embedded in daily routines, organizations with limited resources focused on shared motivation and values, collaboration across organizational boundaries and creation of joint capacity to implement resilience. This transformative process concerns the organization in charge of resilience in the municipal administration and the wider network that they build and animate. , 从政策挑战到落实战略: 为都市韧性网络管理创造战略 自治政府为颁布一项韧性政策会经历哪些转型?本文透过比较视角, 通过分析蒙特利尔(加拿大)和伦敦(英国)在建立各自战略时开发的推动机制和阻碍机制, 对该疑问进行了回应。分析了蒙特利尔和伦敦所使用的协作网络治理及机构工作机制与“宏观和微观情境元素的影响”之间的关系, 在这些情境元素中网络能发挥韧性管理风险和危机。在这两个案例中, 当应急管理结构中各主管单位试图通过协作治理开启新的责任区时, 韧性便得以发展。作为一项孤立的措施, 其被应用于日常活动中、应用于在共享动机和价值观方面资源有限的机构中、还被用于跨组织界限的协作以及为发挥韧性而创造的共同行动。该转型过程与负责自治政府韧性建设的机构有关, 还与后者建立和推动的更广网络有关。 , Del desafío político a la estrategia de implementación: estrategias habilitantes para la gobernanza de la red de resiliencia urbana ¿Qué transformaciones implementan las administraciones municipales para promulgar una política de resiliencia? Este artículo responde a esta pregunta desde una perspectiva comparativa analizando los mecanismos habilitadores e impedidores desarrollados en las ciudades de Montreal (Canadá) y Londres (Reino Unido) a medida que establecen sus estrategias. La gobernanza de la red colaborativa y los mecanismos de trabajo institucional utilizados en Montreal y Londres se analizan en relación con la influencia de elementos macro y micro contextuales bajo los cuales una red puede gestionar de manera resiliente los riesgos y las crisis. En ambos casos, el desarrollo de la resiliencia surge de sus estructuras de gestión de emergencias, ya que las unidades a cargo intentan animar su nueva área de responsabilidad a través de la gobernanza colaborativa. Como un enfoque aislado, esto se integra en las rutinas diarias, las organizaciones con recursos limitados se centraron en la motivación y los valores compartidos, la colaboración a través de los límites de la organización y la creación de capacidad conjunta para implementar la resiliencia. Este proceso transformador concierne a la organización a cargo de la resiliencia en la administración municipal y la red más amplia que construyen y animan.

A review of the flood risk management governance and resilience literature - Morrison, A.; Westbrook, C.J.; Noble, B.F. (Journal of Flood Risk Management, 2018)
The environmental management literature suggests that resilience is key to managing complex systems and reducing vulnerability resulting from uncertainty and unexpected change. Yet, flood risk management (FRM) has emerged largely from a culture of resistance. This paper takes the pulse of the current state of FRM research, with a focus on how the scholarly community has approached governance for flood resilience. Our analysis of the FRM journal literature identified 258 articles addressing governance and flooding, resilience and adaptation. Five main research themes emerged from these articles, addressing a variety of issues, but mostly lacking the degree of integration needed to address the social‐ecological complexity of FRM. Overall, research supporting the governance of FRM for resilience lacks integration, and methods of mitigating this lack of integration are poorly studied. We conclude with a discussion about the nature and scope of FRM research for resilience, and identify opportunities for more integrative FRM research that is more tightly coupled with policy and practice.
Keywords: Ouvrage_Collectif_Numéro1

The challenge of SMBs resilience in urban governance. The case of SMBs and climate change - Robert, Benoît; Hémond, Y. (Co-constructing knowledge for urban resilience implementation workshop, 2017)
Keywords: Hémond_Yannick

Improving flood resilience through governance strategies: Gauging the state of the art - Matczak, Piotr; Hegger, Dries (WIREs Water, 2021)
Abstract There has been an upsurge in studies of flood risk governance (FRG): steering and decision‐making by public and private actors as a complement to risk assessments and technical management options. The scholarly debate is, however, highly fragmented, complicating the production of cumulative insights. To address this knowledge gap, we used six governance strategies for achieving flood resilience that previously have been put forward as a conceptual framework to review 121 articles published between 2016 and 2019, complemented with insights contained in recent overview articles, to gauge the state‐of‐the‐art in FRG literature: to (a) diversify flood risk management strategies; (b) align the strategies; (c) adequately involve private actors, including citizens; (d) put an adequate rule system in place; (e) cater for sufficient monetary and non‐monetary resources; (f) inspire an open and inclusive normative debate. We found, first, that literature is producing insights on increasingly technically advanced risk assessments and agent‐based models but societal debate on justice in flood risk governance is getting attention. A clearly emerging topic is that of citizen engagement in flood risk governance. Second, the geographical focus of the studies is still skewed toward the Global North. To make progress in understanding flood risk governance for better resilience more systematic and comparative empirical assessments of flood risk governance in order to derive generalizable lessons while better taking into account the context‐specificity of FRG. Testing flood risk governance solutions against comparative cases, by balancing the geographical scope of research efforts, and enhancing interdisciplinary and transdisciplinary working is a way to deliver knowledge for more resilience. This article is categorized under: Human Water > Water Governance Engineering Water > Planning Water
Keywords: Ouvrage_Collectif_Numéro1

Changes in flood risk governance in France: a David and Goliath story? - Fournier, M.; Larrue, C.; Schellenberger, T. (Journal of Flood Risk Management, 2018)
When analysing flood risk governance in France since the beginning of the 1980s, central government appears as a predominant actor. However, to understand contemporary French flood risk governance ( FRG ), it is also important to highlight how this domination has progressively been undermined since 1982. First, a decentralisation movement has been initiated whose main characteristics are an increasing involvement of local governments and a difficulty for national authorities to maintain their predominant role. The second main change is a diversification in flood risk strategies going together with a diversification in the definition of the flood risk issue. FRG is not a sole matter of protection through defence, preparation, and recovery strategies anymore. Both prevention and mitigation strategies have progressively gained in legitimacy. It is in the latter that local governments and stakeholders have increasingly got involved and have taken up responsibilities and initiatives. The paper focuses on the explanatory factors behind both stability and change, and especially on the ongoing tension, between path dependency factors (i.e. state power and role) and organisational capability of local actors.
Keywords: Ouvrage_Collectif_Numéro1

Scoping review: understanding the barriers and drivers of risk management in local governments - Bourgeois, Eve; Baril, Pierre-Luc; Normandin, Julie-Maude; Therrien, Marie-Christine (International Journal of Disaster Resilience in the Built Environment, 2023)
Purpose This paper aims to provide scholars with a deep understanding of the field through the identification of strengths and weaknesses in the literature and support decision-makers in the development of new practices in local risk management based on scientific data. The specific question in this review asks: what are the drivers and barriers to local risk management? Design/methodology/approach This paper provides an overview of the scientific literature produce over the past 20 years of the divers and barriers to local risk management. This paper presents a scoping review of peer-reviewed articles published between 2000 and 2019 inclusively in the fields of public policy and public administration. Findings This paper makes three main observations regarding the state of the literature. First, this paper finds that scholars mainly focus on single risk and certain regions of the world. Second, there is multiple approached used by the literature to study risk management at the local level. Third, little attention is given to the political context in which local risk management takes place. Originality/value This paper is a complete literature review of more than 500 peer-reviewed articles published in academic journals regarding risk prevention policies over the past two decades. This paper analyzed the main findings of the current literature to provide a general view of the scholarship and improve the collective understanding of risk management at the local level by providing future research avenues.
Keywords: Infolettre; Infolettre_Mars_2023

Resilience in the Anthropocene: governance and politics at the end of the world - Chandler, David; Grove, Kevin; Wakefield, Stephanie (Routledge research in the Anthropocene, 2020)
"This book offers the first critical, multi-disciplinary study of how the concepts of resilience and the Anthropocene have combined to shape contemporary thought and governmental practice. Faced with the climate catastrophe of the Anthropocene, theorists and policymakers are increasingly turning to 'sustainable', 'creative' and 'bottom-up' imaginaries of governance. The book brings together cutting-edge insights from leading geographers, international relations scholars and philosophers to explore how the concepts of resilience and the Anthropocene challenge and transform prevailing understandings of Earth, space, time and knowledge, and how these transformations reshape governance, ethics and critique today. This book examines how the Anthropocene calls into question established categories through which modern societies have tended to make sense of the world and engage in critical reflection and analysis. It also considers how resilience approaches attempt to re-stabilize these categories - and the ethical and political effects that result from these resilience-based efforts. Offering innovative insights into the problem of how environmental change is known and governed in the Anthropocene, this book will be of interest to students in fields such as geography, international relations, anthropology, science and technology studies, sociology, and the environmental humanities"--
Keywords: Nobert_Sebastien

Methodological approach for mapping the flood physical vulnerability index with geographical open-source data: an example in a small-middle city (Ponferrada, Spain) - Tascón-González, Laura; Ferrer-Julià, Montserrat; García-Meléndez, Eduardo (Natural Hazards, 2024)
Abstract To increase the resilience of communities against floods, it is necessary to develop methodologies to estimate the vulnerability. The concept of vulnerability is multidimensional, but most flood vulnerability studies have focused only on the social approach. Nevertheless, in recent years, following seismic analysis, the physical point of view has increased its relevance. Therefore, the present study proposes a methodology to map the flood physical vulnerability and applies it using an index at urban parcel scale for a medium-sized town (Ponferrada, Spain). This index is based on multiple indicators fed by geographical open-source data, once they have been normalized and combined with different weights extracted from an Analytic Hierarchic Process. The results show a raster map of the physical vulnerability index that facilitates future emergency and flood risk management to diminish potential damages. A total of 22.7% of the urban parcels in the studied town present an index value higher than 0.4, which is considered highly vulnerable. The location of these urban parcels would have passed unnoticed without the use of open governmental datasets, when an average value would have been calculated for the overall municipality. Moreover, the building percentage covered by water was the most influential indicator in the study area, where the simulated flood was generated by an alleged dam break. The study exceeds the spatial constraints of collecting this type of data by direct interviews with inhabitants and allows for working with larger areas, identifying the physical buildings and infrastructure differences among the urban parcels.

Trajectoires de la vulnérabilité aux inondations dans les bassins versants des rivières Cascapédia et Petite Cascapédia à l'est du Québec - Tomety, Yaovi Djivenou (Université du Québec à Rimouski, 2022)
RÉSUMÉ : Les inondations dans la MRC de Bonaventure, à l'instar des inondations de 2017 et de 2019 aux Québec, amènent à repenser les politiques de gestion préventive des inondations dans les municipalités mais il est nécessaire de revisiter le passé pour mieux anticiper le futur. A l'heure actuelle, aucune étude dans la MRC de Bonaventure n'a abordé la trajectoire de la vulnérabilité aux inondations. Le projet de recherche avait pour objectif d'évaluer l'évolution spatio-temporelle de la vulnérabilité aux inondations dans la MRC de Bonaventure plus précisément dans les bassins versants des rivières Cascapédia et petite Cascapédia. Cette recherche s'est particulièrement intéressée à : - 1) - identifier les indicateurs de vulnérabilité aux inondations les plus pertinents et leurs interactions et - 2) - comprendre la trajectoire de la vulnérabilité aux inondations dans le temps. La méthode indicielle a permis de calculer les indices de vulnérabilité par addition d'indicateurs pondérés dans l'analyse de la trajectoire de la vulnérabilité pour les années 1986, 1996, 2006 et de 2016 à partir de 43 indicateurs sélectionnés, adaptés au contexte de la zone d'étude et validés par la MRC de Bonaventure. L'évaluation de la trajectoire de la vulnérabilité aux inondations révèle que les variables socio-économiques sont les plus importantes contribuant à faire varier la vulnérabilité dans le temps dans les corridors fluviaux des rivières Cascapédia et petite Cascapédia. Cette étude expose le caractère dynamique, temporel et transformationnel de la vulnérabilité. Les cartographies de vulnérabilité générées en maillages de 200 m x 200 m et les enquêtes sur le terrain ont permis de mieux appréhender les changements globaux qui ont contribué à l'évolution de la vulnérabilité aux inondations et de comprendre la nature de la vulnérabilité aux inondations. Cette analyse permettra aux décideurs d'anticiper le futur pour une planification concrète de l'adaptation et des mesures de prévention. La trajectoire de la vulnérabilité se présente alors comme un outil de prévention et de prospection pour les décideurs. Elle permet d'appréhender la vulnérabilité du passé, comprendre la vulnérabilité du présent et anticiper sur la vulnérabilité du futur. -- Mot(s) clé(s) en français : Trajectoire, vulnérabilité, inondation, indice de vulnérabilité, gestion préventive. -- ABSTRACT : The floods in the MRC of Bonaventure, like the floods of 2017 and 2019 in Quebec, lead to a rethink of the preventive flood management policies in the municipalities, but it is necessary to revisit the past to better anticipate the future. At present, no study in the MRC of Bonaventure has addressed the trajectory of vulnerability to flooding. The objective of the research project was to assess the spatio-temporal evolution of vulnerability to flooding in the MRC of Bonaventure, more specifically in the watersheds of the Cascapedia and Petite Cascapedia rivers. This research was particularly interested in: - 1) - identifying the most relevant flood vulnerability indicators and their interactions and - 2) - understanding the trajectory of flood vulnerability over time. The index method made it possible to calculate the vulnerability indices by adding weighted indicators in the analysis of the trajectory of vulnerability for the years 1986, 1996, 2006 and 2016 from 43 selected indicators, adapted to the context of the study area and validated by the MRC of Bonaventure. The evaluation of the trajectory of vulnerability to flooding reveals that socio-economic variables are the most important contributing to varying vulnerability over time in the fluvial corridors of the Cascapedia and Petite Cascapedia rivers. This study exposes the dynamic, temporal and transformational character of vulnerability. The vulnerability maps generated in 200 m x 200 m grids and the field surveys have made it possible to better understand the global changes that have contributed to the evolution of vulnerability to floods and to understand the nature of vulnerability to floods. This analysis will allow decision-makers to anticipate the future for concrete planning of adaptation and prevention measures. The trajectory of vulnerability is then presented as a prevention and prospecting tool for decision-makers. It makes it possible to apprehend the vulnerability of the past, to understand the vulnerability of the present and to anticipate the vulnerability of the future. -- Mot(s) clé(s) en anglais : Trajectory, vulnerability, flooding, vulnerability index, preventive management.

Spatial Analysis of Social Vulnerability to Floods Based on the MOVE Framework and Information Entropy Method: Case Study of Katsushika Ward, Tokyo - Lianxiao; Morimoto, Takehiro (Sustainability, 2019)
Tokyo is located in a lowland area that is vulnerable to flooding. Due to global climate change, the scalability and frequency of flooding is increasing. On the other hand, population aging and family structural changes, as well as the lack of adaptation measures, would accelerate flooding vulnerability. The key factors involved in social vulnerability must be studied to reduce the risk of flooding. In this study, we refer to the MOVE framework (a disaster vulnerability assessment framework) and analyze it from three perspectives: Exposure to social vulnerability, susceptibility, and resilience. We subsequently develop an index system to complete the evaluation using 11 indicators. The collected data will help reveal social vulnerability to floods in the Katsushika Ward, Tokyo, using the information entropy method and GIS. We found that the western region of the Katsushika Ward is at more risk than the eastern region during flooding. Additionally, the possibility of a serious crisis erupting is greater in the southwestern region than in the northwestern region. Consequently, we conclude that the spatial distribution of flooding varies in the region. The results of this study will help in understanding social vulnerability, in selecting and combining adaptation measures suited to the characteristics of the area, and in the effective and efficient implementation of these measures by the local government’s disaster department.

On mapping urban community resilience: Land use vulnerability, coping and adaptive strategies in Ghana - Ibrahim, Abdul-Salam; Kuuire, Vincent; Kepe, Thembela (Journal of Environmental Management, 2024)

What can be said about risks, vulnerabilities, and adaptation to climate change in Caribbean small island developing states (SIDS)? The case of Dominica. A qualitative study - Cooper, Sarah; Abraham, Christiana; Ravaliere, Terrilia; Harris-Glenville, Fiona; McPherson, Nickez; Cloos, Patrick (2023)
IntroductionCaribbean Small island developing states (SIDS) are generally qualified as disproportionately vulnerable to climate change, including extreme weather events like hurricanes. While many studies already documented the impacts of climate change on health in the wealthiest countries, there is little knowledge in this field in Caribbean SIDS. Our study aims to discuss health risks and vulnerabilities in a Caribbean context to inform future adaptation measures to climate change.MethodsOur paper is based on a qualitative study that was conducted in Dominica, a Caribbean SIDS. The data come from semi-structured interviews organized between March 2020 and January 2021 with people internally displaced following an extreme climate event, either tropical storm Erika (2015) or Hurricane Maria (2017), and with some people who migrated to Guadeloupe after Hurricane Maria. Interview guides were based on conceptual frameworks on climate change, migration and health, and vulnerability to climate change. Data were analyzed deductively based on frameworks and inductively to allow new codes to emerge.ResultsOur findings suggest that current knowledge of climate change by those who have been displaced by an extreme climate event varied greatly depending on the education level, class, and socioeconomic condition of the participant. Participants experienced various negative consequences from a storm or hurricane such as increased risk of relocation, lack of access to healthcare, and food, job, and water insecurities – all circumstances know to correlate with mental health issues. Participants suggested stronger dwellings, community preparedness committees to act sooner, and climate change sensitization and awareness campaigns to foster community unity and solidarity.ConclusionThese findings contribute to the perspectives and knowledge of climate change, highlighting that existing extreme climate event committees and government officials need to address structural and social barriers that can potentially increase social inequalities and lead to maladaptation to climate change with potential consequences on public health.
Keywords: Cloos_Patrick

Physical Vulnerability and Local Responses to Flood Damage in Peri-Urban Areas of Dhaka, Bangladesh - Fatemi, Nawrose; Okyere, Seth Asare; Diko, Stephen Kofi; Kita, Michihiro; Shimoda, Motoki; Matsubara, Shigeki (Sustainability, 2020)
In Eastern Dhaka, perennial flood remains a constant threat to people and livelihoods. Learning from the micro-level experiences of the poor in the peri-urban areas of Dhaka provides insights on the intersections between physical vulnerability, flood response strategies, and adaptive capacity. Through a convergent mixed method, this study examines the physical vulnerability of residential buildings, flood damages, and local physical responses in three neighborhoods of Eastern Dhaka. Results show that the level of damage to buildings is the most important predictor of physical vulnerability to floods. Buildings that are older than 20 years old and built with natural materials are likely to experience high flood damages compared to buildings that are less than 10 years and constructed with durable materials. The study concludes that in addition to socio-economic interventions, a targeted and people-centered flood management regime that pays attention to age, material composition, and structural quality of houses is necessary to build residents’ adaptive capacities and long-term resilience to flooding. This study contributes to the emerging work on grassroots responses to flood vulnerabilities with practical insights for urban planners and disaster management professionals on particular interventions needed to improve the performance of local responses to flood risks and vulnerabilities.